Catalytic performance of metal-free ethylenediammonium salt catalysts in the thermal decomposition of ammonium perchlorate - Mei-Qing Lai; Jun Hu; Bo-Wen Fan; Wen-Jing Yang; Jian-Gang Xu; Meng Cui; Guo-Cong Guo (Fuel, 2027)

Drought weakens greenhouse gas sink of global wetlands - Longxin Qiao; Xinxin Wang; Hongyang Chen; Jihua Wu; Xiangming Xiao; Ming Nie; Rui-Ting Ju; Yuhan Zheng; Xi Zhang; Qiang He; Xutong Ru; Lijuan Cui; et al. (Environmental Impact Assessment Review, 2027)

Advanced oxidation pretreatment for lignocellulosic bioconversion: reactive species chemistry, byproduct formation, and downstream impacts - Shengqing Wang; Pengyao Wang; Bo Wu; Minhua Cui; Guoshuai Liu; Hongbo Liu; Mustafa Evren Ersahin; Hale Ozgun; Xuedong Zhang (Bioresource Technology, 2026)

AI cold storage delays winter jujube aging and preserves flavor by regulating reactive oxygen metabolism and ethanol fermentation pathways - Yujiao Zhou; Yi Xiao; Yue Qiu; Xiangrui Cui; Ye Han; Yang Li; Baijun Li; Yilong Liu; Xiaoyong Zhao; Di Wu; Bo Zhang; Kunsong Chen; et al. (Postharvest Biology and Technology, 2026)

Elucidating 6PPD-Q-induced metabolic reprogramming and systemic injury via ultrasensitive breathomics - Jiawei Dong; Bo Yang; Qirun Li; Zhen Li; Haiyan Wu; Mo Zhang; Meng Wang; Ting Lan; Zhongbing Lu; Liwei Cui; Yinwei Luo; Yi Yi; et al. (Environmental Pollution, 2026)

Disguise strategy-adjusted controlled cleavage of DNA hydrogel for precision theranostics in colorectal cancer - Bo Han; Haitao Cui; Wenhui Chen; Zixiao Ma; Dandan Liang; Dongyang Wang; Jinghui Zhang; Juan Song; Sheng Tang (Chemical Engineering Journal, 2026)

Rainfall modulates the divergent responses of bacterial and fungal communities to naphthalene contamination in soil - Yuntao Zhao; Duo Zhang; Xin Wang; Yong Cui; Ying Guo; Wei Su; Chen Hong; Wenxin Li; Mengwan Lin; Yixiang Chen; Haobo Ya; Jiayu Chen; et al. (Applied Soil Ecology, 2026)

Constructing Cu0-Cu+ sites inside carbon matrix for Fenton-like degradation of oxytetracycline and reduction of aromatic nitro compounds - Ye-Xia Li; Duo-Wei Ma; Bo Liu; Wen-Long Duan; Tian-Fang Cui; Lei Zhang; Jian Luan (Journal of Environmental Chemical Engineering, 2026)

Elucidating the thermal degradation of fish oil and algal oil: A comparative study on the evolution of flavor profiles and lipid oxidative pathways - Shuang Cui; Ran Xin; Bo Wang; Tingting Zhang; Xuhui Huang; Lei Qin (Food Research International, 2026)

High internal phase Pickering emulsions as edible inks for 3D food printing: impact of Hofmeister series ions on their functionality - Chao Wu; Tianlong Xiao; Shishuai Cui; Yichen Zheng; Bo Jiao; Xiaojie Ma; Hui Hu; Jinjin Zhu; Qiang Wang; David Julian McClements; Aimin Shi (Food Chemistry, 2026)

Carboxylate-driven interfacial regulation via polyacrylic acid additive for stable magnesium metal batteries - Bo Li; Hui Miao; Jiu-Xi Dong; Meng-Qi Zhu; Song-Lin Li; Cheng-Bao Liu; Fen Zhang; Shuo-Qi Li; Lan-Yue Cui (Chemical Engineering Journal, 2026)

A dual-functional diquaternary-ammonium-functionalized bamboo hydrochar for enhanced removal of pesticide and pharmaceutical and controlled release of pesticide - Lei Cui; Zhong-Bo Li; Jie Li; Bing Li (Chemical Engineering Journal, 2026)

Upcycling hazardous electric arc furnace dust into defect-rich ZnO/ZnFe2O4 heterojunction for in situ H2O2 electrogeneration and water purification - Lijuan Jia; Bo Liu; Guoxing Mu; Yiqiang Ji; Fang Wang; Rui Cao; Ping Ning; Shuo Cui; Jiayu Feng (Chemical Engineering Journal, 2026)

Hydrochar-derived organic fertilizers: Application potential in soil, soil-crop responses, and life cycle assessment - Ying Gao; Bo Yang; Qiang Wang; Haojie Cui; Haixin Guo (Biomass and Bioenergy, 2026)

The AtRNC1-AtWTF1 protein complex is essential for chloroplast group Ⅱ intron splicing, ribosome biogenesis, and embryo development in Arabidopsis - Yichen Zhang; Xinyun Xu; Yajuan Li; Siwen Wei; Jiayi Shen; Qing-Bo Yu; Yong-Lan Cui (Plant Molecular Biology, 2026)

Novel analytical approach for the longitudinal vibration of floating pile groups in layered soils considering partial embedment - Kun Meng; Mingchen Zhong; Bo Min; Chunyi Cui; Mirlan Muktarovich Dyldaev; Zhenguo Lu; Bo Zhu; Chunshuo Jiao; Jun Zhao (Soil Dynamics and Earthquake Engineering, 2026)

Shaking table test study on traditional Chinese multi-story pavilion-style timber structures - Li-Wei Zhang; Yu Cao; Zhao-Bo Meng; Shan-Wei Wang; Chun-Lei Wang; Lu-Yao Cui; Xian-Cai Ren (Soil Dynamics and Earthquake Engineering, 2026)

Mitigate dynamic response analysis of submerged floating tunnel (SFT) under wave and impact loads - Xiaolu Cui; Lihua Wang; Bo Huang; Wenlong Luo; Ke Li; Liang Cheng; Dan Zhong (Ocean Engineering, 2026)

Recruitment is the key process that improves trait-based predictions of tree range shifts - Yujun Feng; Yi Zheng; Jin Yin; Yue Bin; Pengcheng He; Dongxu Zhang; Honglin Cao; Ying Lei; Boao Zhang; Jinggang Zhou; Bo Cui; Wanhui Ye; et al. (Forest Ecology and Management, 2026)

Influence of enzymatic modification on the structure–function properties of wheat bran arabinoxylan enriched fractions: Interplay of molecular weight and branching degree - Mohsin Rasheed; Boli Guo; Xiangqi Fan; Yingquan Zhang; Bo Zhang; Ming Li; Yutong Cui (Food Bioscience, 2026)

Moist-heat induced interfacial co-assembly of κ-carrageenan and soy lecithin: A chemical-crosslinker-free paradigm for physically stable Pickering emulsion - Han Liu; Chengbin Sun; Xiaoyan Wu; Guimei Liu; Bin Yu; Xuemin Kang; Zisong Li; Zhengmin Li; Haiteng Tao; Bo Cui (Food Hydrocolloids, 2026)

Synergistic modification of sweet potato protein by ultrasound and succinylation: curcumin-loaded emulsion and application in meat products - Haowei Lv; Chenxi Wang; Enbo Xu; Zhengyu Jin; Haibo Zhao; Chao Yuan; Meng Zhao; Wei Gao; Jianpeng Li; Guanghua Li; Yang Liu; Zhengzong Wu; et al. (Food Hydrocolloids, 2026)

Dietary acrylamide exposure increases susceptibility to ulcerative colitis: A comprehensive analysis from network toxicology to in vivo experimental validation - Peng Cui; Bo Guo; Kangqian Yu; Yanrong Li (Food and Chemical Toxicology, 2026)

High-purity KCl prepared with K(cl, Br) solid solution via controlled-coordination of glycerol - Yali Wang; Hongbao Ren; Ruizhi Cui; Bo Zhang; Qiuye Yang; Wu Li (Chemical Engineering Journal, 2026)

Construction and expression of a transglucosidase-hexose fusion enzyme for oxidating starch: The intrinsic correlation between molecular structure and oxidation degree - Yi Yu; Dengyue Sun; Jixun Xie; Feixue Zou; Li Guo; Bo Cui (Carbohydrate Polymers, 2026)

Differential responses of selectively enriched comammox Nitrospira and ammonia-oxidizing bacteria to ammonia and copper starvation under contrasting dissolved oxygen conditions - Bowen Wang; Zimin Chai; Jin Chen; Lin Bo; Ziyan Xia; Jiaqi Cui; Maosheng Zheng (Bioresource Technology, 2026)

Complete telomere-to-telomere genome assembly of Guazuma ulmifolia uncovers evolutionary mechanisms, drought adaptation, and flavonoid biosynthesis - Tashi Dorjee; Yican Cui; Bo Liu; James E. Richardson; Fei Gao (Plant Cell Reports, 2026)

Warming and drying conditions enhance advective flux signatures in a subtropical flooded rice paddy: Insights from a 9-year eddy covariance study - Yulong Dai; Bo Liu; Jun Wei; Yuanzhi Shi; Fangping Liu; Yufeng Luo; Yuanlai Cui (Agricultural and Forest Meteorology, 2026)

CXCL12/CXCR4 signaling governs ischemic neurovascular pathophysiology and repair: a multidimensional contextual analysis - Shahram Eisa-Beygi; Hao Wu; Kui Cui; Kulandaisamy Arulsamy; Bo Zhu; Beibei Wang; Bandana Singh; Krishan Gupta; Jianing Gao; Scott Wong; Joyce Bischoff; Hanqiang Deng; et al. (Angiogenesis, 2026)

Nonexercise prediction equation for oxygen uptake at anaerobic threshold in Chinese patients with cardiovascular disease - Shiyu Wang; Jiaqi Liu; Zhongyan Li; Xiang Xie; Jing Yao; Yujie Zhu; Wei Jiang; Yang Li; Xiaojun Wu; Haoning Cui; Xianghui Zheng; Xinyu Hou; et al. (European Journal of Applied Physiology, 2026)

Apelin-12 ameliorates diabetic nephropathy via p53/JAM-A axis-mediated preservation of glomerular endothelial integrity - Yuhong Fu; Yue Liu; Bo Huang; Jingqiu Cui (Tissue and Cell, 2026)

Preparation and properties of a sodium alginate based gel for dust suppression and moisture regulation - Yanbin Yu; Sai Li; Xiaosong Hou; Bo Zhou; Wenting Cui; Lianxin Fang; Kai Li (Sustainable Chemistry and Pharmacy, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Structure evolution and dynamics of covalent kaolinite ionization under alkaline activation for strategic metal dissociation - Muyang Chen; Xi Chao; Li Cui; Yuchao Zhang; Bo Yang; Kezhou Yan; Yanxia Guo; Fangqin Cheng (Resources, Conservation and Recycling, 2026)

Valorization of proteins from food residues and By-products: Source, extraction technology, functional properties, and applications - Guangxuan Shao; Jayani Chandrapala; Mahsa Majzoobi; Charles Brennan; Yunsong Jiang; Bo Cui (Food Bioscience, 2026)

Infant-derived bifidobacterium can enhance the ability to respond to influenza virus infection by promoting type I interferon-mediated immunity - Jiaqian Shentu; Qinggang Xie; Minghui Yan; Shumin Wang; Xiaoxuan Sun; Chengcheng Zhang; Peijun Tian; Xiaomei Lv; Bo Yang; Wenwei Lu; Shumao Cui; Gang Wang; et al. (Food Bioscience, 2026)

Interfacial carbon-regulated charge transfer and ROS evolution in Ag3PO4 for enhanced photo-persulfate activation - Jiaxin Li; Chunmu Yu; Yu Zhou; Xiaojuan Chen; Yi Hu; Yuyu Chen; Nianmin Bo; Xinyu Ke; Jiahao Cui; Sha Xiao; Chunhui Cui; Ziyue Yang; et al. (Environmental Research, 2026)

Intestinal inflammation is associated with higher cadmium burden, potentially via compromised gut barriers: Evidence from NHANES and colitic mouse model - Jin-Feng Xi; Chen Li; Lei Zhou; Bing-Zi Cui; Dongmei Zhou; Hong-Bo Li (Environmental Pollution, 2026)

Lactic acid-mediated chitosan/starch complexation: A green strategy for synergistically enhancing resistant starch content and sensory quality in lotus root starch-based foods - Jihong Qu; Yi Liu; Jiadong Li; Haibo Zhao; Jianpeng Li; Die Dong; Chao Yuan; Meng Zhao; Bo Cui (Carbohydrate Polymers, 2026)

Metagenomic analysis of key methanogenic pathways in solid-state anaerobic co-fermentation of weathered coal and cattle manure - Bo Song; Cui Quan; Hongyu Guo; Ningbo Gao (Biomass and Bioenergy, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

LncRNA MNX1-AS1 drives the progression of non-small cell lung cancer and serves as a ceRNA to target COMMD8 by sponging miR-218-5p - Gao-Feng Liu; Li Zhou; Yu-Bo Zhao; Jia-Hong Tang; Qing-Yuan Li; Xiao-Yong Ding; Xiao-Zhen Zhang; Su-Juan Cui; Yong Zhang; Zhen-Wei Sun (Journal of Molecular Histology, 2026)
The role and mechanistic action of MNX1-AS1 in non-small cell lung cancer (NSCLC) remain unclear. This study aimed to investigate the function of MNX1-AS1 in the progression of NSCLC. A total of 40 paired tumor and adjacent lung tissue samples from patients with NSCLC were collected to investigate the expression of MNX1-AS1. H1299 and HCC827 cells were transfected with sh-MNX1-AS1, shRNA-NC, miR-218-5p mimic, mimic-NC, pcDNA3.1-COMMD8, or empty vector (pcDNA3.1). The expression of MNX1-AS1, miR-218-5p, and COMMD8 was detected using quantitative real-time PCR (qRT-PCR). Cell proliferation was evaluated using CCK-8 assays, while cell migration and invasion were evaluated using Transwell assays. Dual-luciferase reporter and RNA pull-down assays were performed to validate the targeting interactions between MNX1-AS1 and miR-218-5p, as well as between COMMD8 and miR-218-5p. In vivo, a nude mouse model was established: tumor volume and weight were measured after four weeks. Gene expression in tumor tissue was quantified using qRT-PCR, and Ki-67 expression was evaluated using immunohistochemistry. MNX1-AS1 expression was significantly upregulated in NSCLC tissues ( P < 0.05) and was correlated with poor prognosis in NSCLC patients. MNX1-AS1 knockdown markedly suppressed the viability, migration, and invasion of H1299 and HCC827 cells ( P < 0.05). Mechanistically, MNX1-AS1 acted as a molecular sponge for miR-218-5p, thereby relieving miR-218-5p-mediated repression of its direct target COMMD8 ( P < 0.05). Functional rescue experiments revealed that miR-218-5p silencing or COMMD8 overexpression partially reversed the inhibitory effects of MNX1-AS1 knockdown on the cell viability, migration, and invasion of H1299 and HCC827 cells. In vivo, sh-MNX1-AS1 significantly reduced tumor volume and weight ( P < 0.05). Moreover, the expression of MNX1-AS1, COMMD8, and Ki-67 were downregulated, while the expression of miR-218-5p was upregulated in sh-MNX1-AS1 tumor tissues ( P < 0.05). MNX1-AS1 promotes the progression of NSCLC by modulating the miR-218-5p/COMMD8 axis.

Enhancing GRACE/GFO spatial downscaling accuracy via graph convolutional networks: a comparative study and ecological response analysis in the Pearl River basin - Yuheng Lu; Lilu Cui; Bo Zhong; Chuanjiang Luo; Haoyang Guo; Xiaochuan Qu (Computational Geosciences, 2026)

An LC-MS–guided AI enabled serum molecule-interpretable SERS platform for exploratory metabolomic analysis in Alzheimer's disease - Yanling Wang; Chi Zhang; Tong Liu; Qingsong Li; Xue Guan; Yutian Hu; Bo Cao; Xiaohong Wu; Qin Zhou; Feiyun Cui (Analytica Chimica Acta, 2026)

Pre-adaptive resistance to acequinocyl associated with cross-resistance to bifenazate in field populations of Tetranychus urticae across China - Jin-Cui Chen; Hui-Juan Li; Ming Xue; Bo Peng; Jing-Jing Kang; Qi-Yu Chen; Shuai-Yu Wang; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2026)

CFSS strut system: A prefabricated method with low-carbon, economic and safety performance in deep excavation - Xuesong Cheng; Chenkai Li; Fan Yi; Qinghan Li; Jiqing Zhang; Peng Zhang; Tao Cui; Bo Li (Transportation Geotechnics, 2026)

An ion-mediated synergistic composite suppressant for coal dust control during transportation: Interfacial wetting mechanisms and sustained moisture retention effects - Yanan Yuan; Liang Yuan; Bingyou Jiang; Mingyun Tang; Bo Ren; Ben Ji; Hanyi Lin; Jie Wang; Leyun Cui (Process Safety and Environmental Protection, 2026)

Cenozoic uplift and paleoclimate history of the Southeastern Tibetan Plateau - Ya Cui; Lin Li; Yang Wang; Yuyang Wang; Yipeng Zhang; Bo Zhang; Jinjiang Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Waste cooking oil biodiesel alters combustion pathways to enhance volatile organic compound emissions and reduce intermediate/semi -volatile organic compounds in agricultural machinery - Fan Zhang; Bo Huang; Junfeng Cui; Yi Wang; Xinyi Wan; Lele Han; Gehui Wang; Yong Han; Yu Wang; Hai Guo; Min Cui (Journal of Hazardous Materials, 2026)

Synthesis of octenyl succinic anhydride-modified corn starch: Focusing on the C2, C3 and C6 substitution positions of anhydroglucose units - Wei Gao; Yifan Chen; Yue Cheng; Xuemin Kang; Xingtao Yu; Wenguo Wang; Bo Cui; A.M. Abd El-Aty (Food Chemistry, 2026)

Corrigendum to “Effects of fatty acids and their monoglycerides on aging, structural characteristics, and thermal stability of starch-based straws” [Carbohydrate Polymers 373 (2026) 124680] - Yandu Jiang; Tongtong Mi; Zijie Liu; Chunpeng Wang; Wei Gao; Xuemin Kang; Chao Yuan; Yang Liu; Pengfei Liu; Zhengzong Wu; Bo Cui (Carbohydrate Polymers, 2026)

Effective intensities of conservation management and ecological threats in improving ecosystem services synergies and mitigating its trade-offs - Weiwei Liu; Lijuan Cui; Rumiao Wang; Manyin Zhang; Wei Li; Wenjing Bo; Miaomiao Zhang; C. Max Finlayson (Journal of Geographical Sciences, 2026)

The antimicrobial arsenal of endophytes in Lilium pumilum: active components of Fusarium tricinctum and antifungal mechanisms - Yong-Jiao Niu; Lin-Bo Liu; Zhong-Duo Yang; Cui-Juan Xu; Tian-Kun Zhao; Lei-Lei Chen; Qian-Qian Wang; Bing Sun; Sahyun Kim (Archives of Microbiology, 2026)

Contrasting Effects of Nitrogen Input on Soil Carbon Pools in Arid and Humid Climates - Shibing Jia; Cuihuan Li; Zhenfeng Xu; Bo Tan; Xinglei Cui; Guopeng Liang; Han Li; Li Zhang; Lin Xu; Hongwei Xu; Sining Liu; Lixia Wang; et al. (Global Change Biology, 2026)
Nitrogen (N) input affects soil organic carbon (SOC) dynamics and storage by specifically influencing the light (LFOC) and heavy fractions of organic C (HFOC). While the effects of N input on SOC pools are known, its specific influence in arid and humid regions remains unresolved, although it is critically important to predict carbon–climate feedback and SOC accumulation. We conducted a meta‐analysis of 881 paired observations from 60 studies to quantify the climate‐specific responses of SOC, LFOC, and HFOC contents to N input, thereby revealing distinct effects in arid versus humid regions. N input increased the LFOC content by 25% in arid regions, whereas the HFOC and SOC contents remained unchanged. This LFOC accumulation may reflect increased plant C inputs, suppressed microbial decomposition, and strong physical protection compared with soil without N input. Conversely, in humid regions, N input increased the HFOC and SOC contents by 10%. These increases were associated with the following four mechanisms: (1) increases in plant and microbial necromass production after N input, (2) microbially‐mediated formation of the HFOC from the LFOC, (3) accelerated lignin‐derived C accumulation due to suppressed saprotrophic fungal decomposition, and (4) raised physico–chemical stabilization by various biotic and abiotic mechanisms. Specifically, increases in LFOC content in arid regions occurred under medium to high N input rates (≥ 50 kg N ha −1 year −1 ), whereas increases in HFOC and SOC contents in humid regions occurred only under medium N input (50–100 kg N ha‐1 year −1 ). These increases occurred primarily after periods of N input longer than 5 years and mainly in topsoil (

True Triaxial Directed Fracturing Experiment on Coal–Rock Complex: Investigation of Fracture–Interface Interaction Behavior - Zhen Shi; Bo Li; Junqi Cui; Yadong Bian; Aitao Zhou; Chao Xu (Rock Mechanics and Rock Engineering, 2026)

Metamorphism and chronology of Neoproterozoic granulite facies metasedimentary rock in northwestern Yangtze Block and its tectonic implications - Linfeng Feng; Haozheng Wang; Byung Choon Lee; Jinghao Fu; Yi Zhang; Heng Liu; Meimei Han; Bo Hu; Xiahong Cui; Mingguo Zhai (International Geology Review, 2026)

Divergent assembly mechanisms and network stability of microeukaryotes between water column and sediment in a marginal sea - Feilong Liu; Xiaoli Zhang; Kaiyue Lian; Yi Li; Can Wang; Chuyu Zhang; Honglei Zhang; Bo Wang; Qian Liu; Hui He; Cui Guo; Andrew McMinn; et al. (Marine Pollution Bulletin, 2026)

Polystyrene nanoplastics disrupt iron homeostasis by promoting FPN1 ubiquitination in GC-2spd(ts) cells - Xinru Cui; Yitong Shang; Liyang Ding; Zhen Zhang; Yu Deng; Tengjiao He; Bo Xu; Xufeng Fu; Xing Du; Hang Han (Toxicology, 2026)

Microbial community structures are associated with medicinal bioactive compound accumulation in Drynaria roosii Nakaike across rock and tree habitats - Bo Wang; Fuli Gong; Chunjiang Huang; Jingzhong Chen; Pengjie He; Hongyu Chen; Wenyan Cui; Qingwen Sun (Rhizosphere, 2026)

Coupled dynamics and resonance mitigation of submerged floating tunnel roadways under transient impact loads in marine environments - Xiaolu Cui; Jing Chen; Bo Huang; Wenlong Luo; Ke Li; Liang Cheng; Dan Zhong; Pupeng Ai; Shixiao Fan (Ocean Engineering, 2026)

Multi–objective optimization of dual–brick Fe–Cu zeolite catalyst for NH3–SCR via interpretable machine learning and reinforcement learning - Feng Jiang; Zhejun Li; Zijian Jiang; Chengtao Zhang; Zhiqing Zhang; Jie Hu; Shuwan Cui; Bo Cao; Zhiqiang Hu; Jiajie Yu (Journal of Environmental Chemical Engineering, 2026)

Effluent discharge drives microbial community assembly and functional potential for greenhouse gas metabolism in receiving waters: A case study in Northern China - Bo Shao; Zhengyu Wu; Haoran Peng; Qing Yang; Hongyang Cui; Xiaoyu Cui; Yindong Tong (Journal of Environmental Sciences, 2026)

Comparative study on ignition mechanism and intrinsic combustion kinetics between coal and char - Zezheng Shi; Yang Liu; Yongxiao Jia; Jiye Tao; Kuangyu Li; Zhi Wang; Xinyu Wang; Yumin Chen; Bo Yu; Shisen Xu; Dongliang Xu; Xiangping Wang; et al. (Fuel, 2026)

Formation and inhibition of associated hazardous compounds in thermal-processed foods under raw material–adapted processing conditions - Shuang Cui; Feng Zhao; Bo Wang; Xuhui Huang; Lei Qin (Food Research International, 2026)

Lactiplantibacillus plantarum CN2018 targets gut microbiota and hepatic lipogenesis to counteract diet-induced obesity - Xinkai Sun; Bo Zhang; Shumao Cui; Linsen Zhao; Gang Wang; Jianxin Zhao (Food Bioscience, 2026)

Corrigendum to “Preparation and characterization of edible oleogels from starch-based aqueous foams via foam-templated approach” [Food Hydrocolloids 173 (2026) 112307] - Yu Deng; Lirong Dai; Yazhu Yang; Jiajun Yu; Die Dong; Meng Zhao; Chao Yuan; Bo Cui (Food Hydrocolloids, 2026)

Employing L-cysteine-mediated modulation for nickel biorecovery: Bioseparation-photocatalytic upcycling from wastewater - Shunling Li; Peng Cui; Zhaosheng Zhang; Fenxiang Li; Pan Bo; Qing Qu (Environmental Research, 2026)

Enabling long-cycle-life high-voltage calcium metal batteries with fluorinated alkoxyborate-based CaNa hybrid electrolytes - Xinyue Li; Shuangshuang Cui; Bin Chen; Xiaoke Mu; Dechen Zeng; Hongkun Wang; Yang Wang; Bo Peng; Tianyu Zheng; Dianxing Ju; Aobing Du; Zhenyou Li; et al. (Chemical Engineering Journal, 2026)

Anodal HD-tDCS attenuates forearm muscle fatigue via enhanced beta-band corticomuscular coherence - Bo Zhu; Yong Li; Xiaofeng Wang; Cui Wang; Chenxin Shen (Experimental Brain Research, 2026)

Stand age drives divergent microbial metabolic limitations and ecosystem multifunctionality between rhizosphere and bulk soils in subtropical Cryptomeria japonica plantations - Shanshan Huang; Yi Jian; Jing Li; Dengjie Zhou; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Lixia Wang; et al. (Soil Ecology Letters, 2026)

Flexible SERS tape: A plasmonic hybrid of AuNPs and layered K2Ti8O17 nanowire network for on-site detection of pesticide residues - Lin Xu; Mingru Cui; Zhongqi Ge; Ruikang Zou; Cong Wang; Pengfei Ni; Xi Huang; Bo Zhong; Lijuan Wang (Analytica Chimica Acta, 2026)

Impacts of surface heterogeneity on energy partitioning in paddy ecosystems: A dual eddy covariance study - Yulong Dai; Bo Liu; Jun Wei; Yuanzhi Shi; Qilin Li; Fangping Liu; Yufeng Luo; Yuanlai Cui (Agricultural and Forest Meteorology, 2026)

Microbial Perspective: Regulatory Mechanisms of Interactions Between Microplastics and Dissolved Organic Matter on Greenhouse Gas Emissions in Aquatic Ecosystems - Mengxin Xu; Meiqi Huang; Shuang Liu; Jinze He; Feng Zhao; Bo Shao; Guangli Mu; Hongyang Cui; Panpan Cui; Yingxin Zhao; Yiwen Liu; Xiaoyu Cui; et al. (Global Change Biology, 2026)
Microplastic (MP) pollution may influence aquatic greenhouse gas (GHG) emissions by altering dissolved organic matter (DOM)–microbe coupling, yet reported effects remain inconsistent across ecosystems and exposure regimes. Here, we synthesized evidence from 16 studies to quantify the net effects of MPs on CO 2 , CH 4 , and N 2 O fluxes under ambient DOM conditions. Our meta‐analysis indicates that MP exposure significantly increases CO 2 emissions and decreases N 2 O fluxes, whereas CH 4 responses show a non‐significant positive trend with high variability. Exposure duration and polymer identity emerge as key moderators, indicating that MP effects are context‐dependent rather than uniform. Short‐term exposure tends to suppress carbon mineralization, whereas long‐term exposure is more often associated with GHG production, consistent with a time‐dependent trajectory potentially shaped by polymer aging. Mechanistically, this pattern may reflect initial DOM adsorption and humification that reduce substrate availability, followed by the release of bioavailable MP‐derived compounds that may stimulate microbial respiration, methanogenesis, and denitrification. Overall, MPs reshape aquatic carbon and nitrogen cycling within the overarching framework of DOM, which may ultimately influence GHG emissions under certain conditions. These findings provide a quantitative basis for reconciling conflicting observations and improving predictions of the climate relevance of MP pollution in aquatic ecosystems.

Efficient combined use of electroacupuncture with ordered collagen scaffolds enhances the therapeutic efficacy of human spinal cord-derived neural progenitor cells therapy in spinal cord injury rats - Yunlong Zou; Weiwei Xue; Bo Guo; Lu Li; Yannan Zhao; Xianming Wu; Zhifeng Xiao; Qi Zhang; Dezun Ma; Xinhao Zhao; Bing Chen; He Shen; et al. (Science China Life Sciences, 2026)

Talarombrevisone A, an β -aminopropionate with two polyketide units, isolated from an endophytic fungus Talaromyces brevis - Yun-He Tuo; Zhong-Duo Yang; Jian-Guo Chen; Cui-Juan Xu; Lin-bo Liu; Tian-Kun Zhao; Yue Li; Li-Bin Xia; Shuai Yu; Ai-Hong Zhao; Shuo Li (Natural Product Research, 2026)

Functional trait diversity in overstorey and understorey increases microbial carbon use efficiency in a forest plantation soil - Renping Wan; Junxi Hu; Huan Xiao; Zhe Li; Jingnan Xu; Bo He; Lanlan Song; Lifeng Wang; Jian Peng; Xiaoyan Yu; Xiaolin Li; Lihua Tu; et al. (Soil Biology and Biochemistry, 2026)

Shift in orbital-scale climate response under the coupling of ice sheet and monsoon during the Late Oligocene: Sedimentary records from the East China Sea Shelf Basin - Yingkun Cui; Fujie Jiang; Xianke He; Yichen Liu; Wenji Wang; Rui Zhang; Yinghui Liu; Zhuo Li; Zhenguo Qi; Bo Xu; Hang lv; Jiming Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Oxygen supply models shape spatiotemporal distribution of total and active bacterial communities in seawater constructed wetlands - Wenli Liu; Qiufen Li; Ying Ma; Bo Sun; Xianzhe Gong; Zhengguo Cui (Journal of Water Process Engineering, 2026)

Concurrent biodegradation of tylosin and tilmicosin by a novel Paracoccus versutus 4-B-2 - Zhengyan Chen; Anqi Liu; Junzhe Cui; Chunhui Liu; Huijuan Li; Ziyi Quan; Yaxu Liu; Xiao Guo; Xiaoyu Wang; Liling Fan; Bo Wang (Journal of Hazardous Materials, 2026)

Speciated full-volatility organic compound emissions from typical agriculture machinery in China - Yi Wang; Lele Han; Bo Huang; Xia Xu; Xinyi Wan; Yubao Chen; Yong Han; Min Cui; Yu Wang; Hai Guo; Fan Zhang; Gehui Wang (Journal of Environmental Sciences, 2026)

Study on the mechanism of fat coal compatibility driven by structure transformation - Xuhui Chen; Ruyuan Duan; Ruifang Hou; Xin Jin; Bo Wu; Yanfeng Shen; Beibei Cui; Liping Chang; Chunhao Liang; Xinjie Han; Meijun Wang (Fuel, 2026)

Exploring the mechanism of variation in 3D printing shape stability and mechanical performance of starch/gelatin printed products during dehydration process - Yue Cheng; Wei Gao; Xuemin Kang; Bo Cui (Food Research International, 2026)

A ratiometric fluorescence sensor based on starch/polyacrylamide/deep eutectic solvent hydrogel for visual and nondestructive detection of methyl parathion on foods - Xueting Li; Yajie Bo; Qichao Ye; Xuemin Kang; Lu Lu; Bo Cui; Fanfu Meng; Chenghai Li (Food Chemistry, 2026)

Mining and characterization of novel prolyl endopeptidases from human gut microbes for degrading the immunogenic gluten 33-mer peptide - Xiaojing Zhou; Pan Huang; Chuan Zhang; Chengcheng Zhang; Gang Wang; Shumao Cui; Wenwei Lu; Bo Yang; Junjun Wu; Xiaomei Lyu; Fengwei Tian; Jianxin Zhao; et al. (Food Bioscience, 2026)

Bifidobacterium breve CCFM1078 alleviates chronic diarrhea in neonatal rats by restoring intestinal motility and barrier function - Jiayi Song; Shumao Cui; Qixiao Zhai; Catherine Stanton; Paul Ross; Jianxin Zhao; Wei Chen; Bo Yang (Food Bioscience, 2026)

Esterified resistant dextrin for delivery of short-chain fatty acids: Characterization, release, and microbiota impact - Yahui Xie; Xinzhu Zhao; Guimei Liu; Haiteng Tao; Haibo Zhao; Xuemin Kang; Bin Yu; Bo Cui (Food Bioscience, 2026)

Tightknit pin joint with tapered sleeve: Behavior of connection and effect on viscous damper efficiency - Yi-Qiong Cui; Yang Xiang; Bo Yang; Shi-Li Guo; Guo-Qiang Li (Engineering Structures, 2026)

Dual-Hofmeister effect/directional alignment enabled anisotropic all-bio-based hydrogel with wide-range adjustable mechanical/electric properties for flexible electronics - Tongtong Liu; Lu Lu; Bo Cui; Xuemin Kang; Li Guo; Feixue Zou; Zhijun Zhang; Fanfu Meng; Chenghai Li; Guowei Cai (Chemical Engineering Journal, 2026)

Modulating d-d orbital coupling in bifunctional NiMo alloy for enhanced overall water splitting - Bo Zhao; Mingpeng Chen; Jin Zhang; Huachuan Sun; Boran Zhao; Dequan Li; Yuewen Wu; Tong Zhou; Feng Liu; Hao Cui; Qingju Liu (Chemical Engineering Journal, 2026)

Multifunctional starch-based eutectogels with high mechanical properties, adhesion, self-healing, fatigue resistance and degradability for flexible wearable sensing - Dadong Sun; Zhihua Xu; Li Guo; Bin Yu; Lu Lu; Bo Cui; Xuemin Kang; Zhijun Zhang; Fanfu Meng; Chenghai Li; Guowei Cai (Carbohydrate Polymers, 2026)

PfAgo-mediated a rapid and visual detection assay for porcine circovirus type 3 based on recombinase-aided amplification - Xi-Meng Chen; Jia-Qi Zhang; Hong-Bo Cui; Lan-Lan Zheng; Xue-Yan Ding; Hong-Ying Chen; Shi-Jie Ma (Analytica Chimica Acta, 2026)

Determination of dissociation constants between single-protein and multicomponents by a multi-chamber membrane separation electrophoresis system as a complementary tool - Hai-Bo Shang; Yuwei Zhu; Yonglong Liu; Lei Yang; Yanying Qu; Meiyu Cui; Meihua Dong; Xiangfan Piao; Donghao Li (Analytica Chimica Acta, 2026)

Metagenomic insights into the trophic gradient influence on nitrogen cycling microbiomes in plateau lakes - Sicen Yan; Hafiz Adeel Ahmad; Yongchao Xie; Shufeng Liu; Jiang Wu; Jiaxin Cui; Bo Yang; Lei Su; Tengda Ding; Tang Liu (Marine Pollution Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

SynPER: Synthesized prioritized experience replay for USVs formation control in island-reef waters via multi-agent reinforcement learning - Zijian Hu; Jiangyong Jin; Yani Cui; Bo Li; Jia Ren; Fan Yang (Ocean Engineering, 2026)

Early Cretaceous radiolarian assemblages in mélange of Yarlung-Tsangpo suture zone in the Saga area, southern Xizang - Zhi-Hao He; Xin Li; Ya-Lin Li; Atsushi Matsuoka; Hui Luo; Xiao-Hui Cui; Jian-Bo Cheng (Palaeoworld, 2026)

Simultaneous separation of ammonia, phosphorus and caproate in flow electrode capacitive deionization with VS4/rGO-modified electrode - Huimin Sun; Pengyao Wang; Xuedong Zhang; Bo Wu; Minhua Cui; Hongbo Liu; He Liu (Journal of Environmental Chemical Engineering, 2026)

Increased heterogeneity of sedimentary potential silicate-solubilizing bacterial communities caused by cascade damming reduces community complexity but promotes stability - Juan Chen; Qihao Nie; Chao Wang; Peifang Wang; Yuansheng Zhu; Ge Cui; Han Gao; Bo Zhang; Shunqing Zhang (Journal of Environmental Sciences, 2026)

Plantaricin-producing Lactiplantibacillus plantarum NDF28B2 as an adjunct culture enhances fermented Milk texture and suppresses Listeria monocytogenes - Nan Xiao; Yang Liu; Chengcheng Zhang; Chuan Zhang; Pan Huang; Gang Wang; Shumao Cui; Wenwei Lu; Bo Yang; Junjun Wu; Xiaomei Lyu; Fengwei Tian; et al. (Food Research International, 2026)

Paste stability of different starch modified by fusing hexose oxidase/carbohydrate-binding module 20/maltotetraose-forming amylase - Siyu Liu; Xuemin Kang; Li Guo; Bo Cui; Yanli Hu; Meng Yang; Jinpeng Wang; Chunrui Sun (Food Chemistry, 2026)

Soluble expression of a membrane-bound linoleic acid isomerase using a fusion tag strategy - Jing Cui; Lulu Chang; Bo Yang; Jianxin Zhao; Wei Chen; Haiqin Chen (Food Bioscience, 2026)

Early-life bovine colostrum supplementation alleviates atopic dermatitis through gut microbiota remodeling and enhanced immune regulation - Siya Wu; Qing Zhang; Zheng Huang; Shumao Cui; Catherine Stanton; R. Paul Ross; Jianxin Zhao; Wei Chen; Bo Yang (Food Bioscience, 2026)

Preparation and characterization of edible oleogels from starch-based aqueous foams via foam-templated approach - Yu Deng; Lirong Dai; Yazhu Yang; Jiajun Yu; Die Dong; Meng Zhao; Chao Yuan; Bo Cui (Food Hydrocolloids, 2026)

Emulsion gels fabricated by highly branched cyclic dextrin and β-Cyclodextrin: Overcoming the limitation of single-component system for low-oil food applications - Runnan Liu; Liuyan Chen; Chao Yuan; Bo Cui; Guimei Liu; Meng Zhao (Food Hydrocolloids, 2026)

Data-Driven assessment of demand response potential of residential loads based on LSTM-WGCNA and Customer directrix load - Bo Peng; Baolin Cui; Xin Ma; Che Liu (Energy and Buildings, 2026)

Targeting γ-aminobutyric acid via potassium-chelating and zinc-releasing ionic modulation to suppress spinal metastasis of lung cancer - Jiaqian Wang; Hao Qin; Annan Hu; Zhiyang Chen; Qianyi Zhang; Jian Zhou; Zonghan Xu; Wenguo Cui; Bo Tian; Jian Dong (Chemical Engineering Journal, 2026)

Multi active sites regulation of buried interface defects in n-i-p perovskite solar cells with tryptophan derivatives - Yanan Liu; Xinbao Lin; Xiaozheng Zhao; Tianci An; Wenya Zhao; Miaoran Zhang; Linfeng Cui; Taoyu Weng; Bo Liu (Chemical Engineering Journal, 2026)

Photofunctionalized commercial nonwoven Janus dressing for unidirectional exudate clearance and antibacterial healing of infected wounds - Chen Cui; Bo Wang; Borui Chen; Wei Wang; Yanling Yang; Xiang Li; Zhen Yang (Chemical Engineering Journal, 2026)

In situ cultivation and chromogenic screening: a dual approach for rapid discovery of PDE1 inhibitors from pinus-tree associated microbes - Cui-Juan Xu; Shuo Li; Zhong-Duo Yang; Lin-Bo Liu; Yun-He Tuo; Yong-Jiao Niu; Lei-Lei Chen; Jian-Guo Chen; Tian-Kun Zhao; Ai-Hong Zhao (World Journal of Microbiology and Biotechnology, 2026)

Adaptation Mechanisms of Aquatic Animals to Saline–Alkaline Water Aquaculture: Physiological, Energetic and Molecular Perspectives - Yingsha Qu; Huichen Li; Bo Zhang; Hongwu Cui; Jianlei Chen; Yong Xu; Zhengguo Cui; Keming Qu; Hao Li (Fishes, 2026)
Saline–alkaline water constitutes a vital strategic non-traditional fishery resource in China, characterized by high pH values, elevated carbonate alkalinity, and complex ionic compositions. These extreme environmental conditions impose significant stress on aquatic animals, mainly by inducing ionic toxicity and disrupting acid–base regulatory mechanisms. Such disruptions subsequently lead to osmotic imbalance, metabolic dysregulation, and immunosuppression, thus restricting the survival and growth of aquatic species in aquaculture systems. Consequently, the sustainable development of the saline–alkaline aquaculture is imperative for enhancing production efficiency and promoting the utilization of marginal land and water resources. This review comprehensively summarizes the current status of saline–alkaline aquaculture and highlights the stress-inducing impacts of salinity, alkalinity, and specific ionic ratios on teleost fishes and crustaceans. It further explores key adaptive mechanisms, including osmoregulatory and ionoregulatory strategies, bioenergetic trade-offs related to oxygen consumption and ammonia excretion, coordinated antioxidant and innate immune responses, as well as recent findings from multi-omics research. This review aims to offer a scientific foundation for the selection and breeding of saline–alkaline-tolerant strains, the precise regulation of aquaculture water environments, and the development of ecological aquaculture models in saline–alkaline regions, thereby facilitating the sustainable utilization of saline–alkaline land and water resources.

MiR-342-3p Attenuates Inflammation and Pyroptosis in Severe Community-Acquired Pneumonia by Targeting EP300 - Bo Song; Ruijuan Xu; Chenxi Cui; ShuMei Rao; Yingying Liu; Yilei Yang (Biochemical Genetics, 2026)

Dynamic approach-based assessment of debris flow susceptibility in the mountainous area of North China - Bo Liu; Xueqiang Gong; Yonghao Zhou; Xiewen Hu; Kun He; Jian Cui (Transportation Geotechnics, 2026)

Identification of key taste active compounds and potential umami peptides in soft-boiled chicken based on taste recombination and virtual screening - Shui Jiang; Xiangyuan Li; Lexin Zhao; Shuang Bai; Danni Zhang; Hengli Meng; Zhiyong Cui; Xiaoming Wang; Bo Yu; Yuan Liu (Food Chemistry, 2026)

Thermal aging treatment of starch-based straws: The role of temperature-time effects on structure and functional performance - Chuanjin Xia; Jinyu Zhang; Li Guo; Bo Cui; Yu Zhu; Meng Yang; Jinpeng Wang; Chunrui Sun (Food Chemistry, 2026)

Preparation and characterization of CaCO3-templated starch-polyphenol complexes for antioxidant Pickering emulsions - Jiajun Yu; Yu Deng; Yazhu Yang; Die Dong; Meng Zhao; Li Guo; Chao Yuan; Bo Cui (Food Hydrocolloids, 2026)

Modulation mechanism of starch gelatinization and gluten network restructuring in wheat flour during atmospheric steam treatment - Xiangqi Fan; Jikai Jiang; Mohsin Rasheed; Ming Li; Yingquan Zhang; Yutong Cui; Bo Zhang; Boli Guo (Food Hydrocolloids, 2026)

High-value utilization of hazardous solid waste for efficient electrocatalytic oxygen reduction to produce hydrogen peroxide - Bo Liu; Xiaoshuang Song; Guoxin Mu; Jiayu Feng; Fang Wang; Rui Cao; Zibin Pan; Feixiang Lu; Ping Ning; Shuo Cui; Lijuan Jia (Environmental Research, 2026)

Labile zinc in the water-level-fluctuating zone of the Three Gorges Reservoir: Remobilization and ecological risk - Moli Zhang; Meng Cui; Dongyu Xu; Wei Huang; Yueyue Zhang; Yongnan Zhu; Bo Gao (Environmental Research, 2026)

Microenvironment-responsive nanoparticle system integrating stem cell membrane derived cell-free therapy for the treatment of traumatic brain injury - Mengwen Song; Cui Wang; Jiangyi Wu; Pengchong Zhu; Shenghui Gong; Yichen Huang; Xiaowen Xing; Wenjing Ma; Qiaomi Chen; Zhifa Zhang; Xiaotong Yang; Xiaoming Zhu; et al. (Chemical Engineering Journal, 2026)

Policy for strengthening marine strategic science and technology capabilities: framework, theory, and practice - Zi Jun Hu; Wang Lai Cui; Bo Jun Gu; Xiao Yu Cui (Frontiers in Marine Science, 2026)
Policy for strengthening marine strategic science and technology capabilities have emerged as a new approach to overcoming the ‘bottleneck’ technology challenges in the marine sector, which have been exacerbated by technological blockades imposed by developed countries. This paper provides a comprehensive analysis of such policies from multiple dimensions, including their conceptual connotations, key components, main characteristics, theoretical interpretations, and practical applications. The study identifies five major policy directions that have emerged globally: breakthroughs in ‘bottleneck’ technologies, enhancement of maritime military capabilities, deep-sea resource development, marine industry innovation, and the strengthening of maritime governance and capacity building. These practices also exhibit a clear pattern of “development-stage alignment,” whereby high-income countries or regions focus on “innovation upgrading + hegemony maintenance,” while middle- and low-income countries or regions prioritize “basic capacity building + security assurance.” The core contribution of this article lies in constructing a systematic analytical framework of “concept-elements-characteristics-theory-practice” for such policies, clarifying their theoretical underpinnings and practical logic, and providing latecomer countries with a directly applicable theoretical framework and practical pathways for formulating marine strategic science and technology policies that are suited to their specific development stages.

Investigation of Emission Characteristics of Controlled-source Electromagnetic Transmitters Employing a TSC–GCSC Tunable Impedance Matching Circuit - Quan-hui Guo; Guo-qiang Xue; Qi-hui Zhen; Jun-jie Xue; Fen-xuan Zhang; Jiang-wei Cui; Yan-bo Wang; Wen-bo Guo (Applied Geophysics, 2026)

Polyoxometalate decorated Pt1-O pair for production of high-value-added fuels additive from alkylation reaction of unsaturated organic and aromatic hydrocarbons - Zhaohui Zhou; Qun Zhang; Xianglong Cui; Lu Han; Bo Zhang; Xinyuan Zou; Fan Zhang; Yuanning Yue; Jian Fan; Haoran Wang; Yibin Liu; Hao Yan; et al. (Fuel, 2026)

Construction of 3D printable native-modified corn starch composites gels as dysphagia diet: Crucial role of modified starch - Jiangkai Zeng; Yumin Duan; Zaifei Zheng; Peng Wang; Xiaoqi Ma; Lin Wang; Chong Cui; Bo Bo; Xiaoshuai Yu; Zhigang Xiao (Food Research International, 2026)

Mechanism of physicochemical changes in potato starch gel induced by citric acid-autoclaving for texture improvement and resistant starch formation - Linlin Cui; Xinzhu Wang; Shuhan Ge; Xia Li; Yu Wang; Bo Nan; Zhicheng Zhang; Yuhua Wang (Food Chemistry, 2026)

Distribution of folate synthesis genes in Lactobacillaceae and characterization of high folate production - Zhihao Chen; Chuan Zhang; Yiyi Li; Chengcheng Zhang; Pan Huang; Gang Wang; Shumao Cui; Wenwei Lu; Bo Yang; Qixiao Zhai; Fengwei Tian (Food Bioscience, 2026)

Unraveling novel pancreatic lipase and cholesterol esterase inhibitory peptides in Oryza Sativa L. and their mechanism by peptidomics, molecular dynamics simulations, and cell study - Liuyi Wei; Taoying Wu; Hao Wu; Li Wen; Bo Cui; Yunhui Cheng (Food Bioscience, 2026)

A reference inventory of Antarctic subglacial volcanoes: ANT-SGV-25 - Keying Cao; Xiangbin Cui; Wen Zhou; Bo Sun; Martin Siegert (Earth-Science Reviews, 2026)

Iron and platinum alternating active sites for efficient photocatalytic overall water splitting - Yanfei Fan; Yan Liu; Ying Liang; Kang Chen; Qingqing Li; Dongxu Pan; Shiqiu Zhang; Guanwei Cui; Bo Tang (Chemical Engineering Journal, 2026)

Hydrophilic tripeptide L-glutathione enhanced methane hydrate formation with high energy density and rapid methane uptake: implications for gas storage - Qing-Cui Wan; Yuan-Le Li; Bo Li; Gui-Cai Li; Xin-Miao Liu (Chemical Engineering Journal, 2026)

Effects of fatty acids and their monoglycerides on aging, structural characteristics, and thermal stability of starch-based straws - Yandu Jiang; Tongtong Mi; Zijie Liu; Chunpeng Wang; Wei Gao; Xuemin Kang; Chao Yuan; Yang Liu; Pengfei Liu; Zhengzong Wu; Bo Cui (Carbohydrate Polymers, 2026)

Influence of interweaving configuration and impactor rotation on the performance of flexible rockfall barriers - Junyi He; Aiguo Xing; Yufang Zhang; Jian Cui; Bo Liu; Kun Yuan; Pan Chen (Transportation Geotechnics, 2026)

Novel analytical approach of vertical vibration of closely spaced pipe pile groups considering soil plug and scattering effects - Kun Meng; Mingchen Zhong; Chunyi Cui; Xiubing Li; Zhenguo Lu; Bo Min (Soil Dynamics and Earthquake Engineering, 2026)

Occurrence characteristics and ecological risks of fluorescent whitening agents in water bodies around a landfill - Xuejing Yang; Mengfei Su; Yifei Wang; Yu Guo; Bo Yao; Shuwen Yan; Yonghui Han; Jiansheng Cui (Journal of Hazardous Materials, 2026)

Research on water-energy-carbon consumption and emission situation and nexus in iron and steel industry - Junting Cui; Yongjuan Tong; Wenzhe Ma; Jinyu Zhang; Bo Zhou (Journal of Cleaner Production, 2026)

Micro-macro progressive deterioration patterns of water-immersed coal: Non-uniform surface and pore damage - Bo Li; Zhen Shi; Zhenfeng Wang; Junxiang Zhang; Junqi Cui; Yaocai Tang; Peiliang Ren (Fuel, 2026)

Tertiary enzyme synergistic network-mediated starch-directed transformation into resistant starch - Nannan Xu; Yaru Xue; Li Guo; Bo Cui; Meng Yang; Jinpeng Wang; Chunrui Sun (Food Chemistry, 2026)

A double-package delivery system based on κ-carrageenan hydrogels and vitamin E/highly branched cyclic dextrin composites: Structural characteristics and release behavior - Wentao Ma; Wei Liu; Chao Yuan; Bo Cui; Yaqi Liu; Li Guo; Bin Yu; Meng Zhao; Feixue Zou (Food Chemistry, 2026)

The abfA gene cluster maintains microbial homeostasis by regulating the complexity and stability of the gut microbiome network - Bowen Zhu; Chengcheng Zhang; Chuan Zhang; Pan Huang; Gang Wang; Shumao Cui; Wenwei Lu; Bo Yang; Fengwei Tian; Qixiao Zhai (Food Bioscience, 2026)

Insight into the adsorption mechanism of gallium, vanadium on amidoxime resin and cascade desorption for synergistic recovery - Li Cui; Muyang Chen; Yu Zhang; Lijuan Wang; Bo Yang; Fangqin Cheng (Chemical Engineering Journal, 2026)

Targeting mGluR1-Mediated Microglial ER Stress Mitigates Copper-Induced TBI Neuroinflammation - Dan Wang; Jiawei Zhou; Zhulin Zhou; Dayong Cui; Fengkai Liu; Bo Zhang (Molecular Neurobiology, 2026)

Shifts in epidemic patterns and age dynamics of RSV, IFV, and SARS-CoV-2 in Chinese children following COVID-19 non-pharmaceutical intervention relaxation, 2017 − 2024 - Yiguo Zhou; Jian-Bo Xia; Meimei Luo; Wan-Xue Zhang; Shan-Shan Zhang; Le Ao; Han Yang; Qin-Yi Ma; Juan Du; Yu-Ting Wang; Ninghua Huang; Xing-Wen Hu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Dynamic performance of trains in submerged floating tunnels under wave loading - Linzhong Han; Bo Huang; Wenlong Luo; Cheng Cui; Jie Hou; Hao Ding; Ke Li; Liang Cheng; Dan Zhong; Jiawei Zhou (Ocean Engineering, 2025)

Corrosion behavior and mechanical property degradation of Al-Zn-Mg-Cu alloy in tropical marine atmosphere - Dongdong Song; Songtao Liu; Rongxiang Wang; Zhiyuan Cui; Fanyu Yi; Yuqian Zheng; Bo Zhang (Ocean Engineering, 2025)

Applying synchronous fluorescence spectroscopy with Gaussian band fitting and high-resolution mass spectrometry to monitor dissolved organic matter characteristics changes in pharmaceutical wastewater - Chenqiang Yang; Yujie Yu; Bo Yao; Jiansheng Cui; Haiying Yu (Journal of Environmental Chemical Engineering, 2025)

Dam construction and nutrient enrichment led to simplification of riverine micro-food webs by weakening top-down control effect - Ge Cui; Juan Chen; Chao Wang; Peifang Wang; Bo Zhang; Shunqing Zhang; Qihao Nie (Journal of Environmental Management, 2025)

Hydrological connectivity associated with salinity mediates wetland vegetation pattern and productivity in estuary - Bo Pang; Chunguang Che; Changzhi Yang; Tian Xie; Baoshan Cui; Yeling Liu; Qing Wang; Yuming Lu; Yina Li; Fang Gao (Journal of Environmental Management, 2025)

Valorization of steel slag through CO2 mineralization toward improved reactivity and cementitious performance - Bo Su; Yong Sun; Ping Jiang; Chao Zhang; Kai Cui; Yong Zheng; Jingping Qiu; Yingliang Zhao (Journal of Environmental Chemical Engineering, 2025)

Enhancement of stability and hydrogel properties of type-A gelatin-dextran mixtures via incorporation of whey protein isolate fibrils - Ling Wu; Die Dong; Zhengzong Wu; Jianpeng Li; Lu Lu; Na Wang; Yisu Yang; Meng Zhao; Bo Cui (Food Research International, 2025)

Covalent organic framework nanospheres for solid-phase extraction of pyrethroids from vegetables - Weixin Duan; Na Liu; Xuechun Fu; Na Wang; Bo Cui (Food Chemistry, 2025)

Discrimination and evaluation of commercial large yellow croaker (Larimichthys crocea): Odor and taste-active compounds - Shuang Cui; Bo Wang; Zheng Zhou; Wei Yang; Lei Qin; Xuhui Huang (Food Chemistry, 2025)

Positively charged components (chitosan most potently) combined with annealing: Modulating digestibility and viscosity of corn starch - Yi Liu; Jihong Qu; Haibo Zhao; Jianpeng Li; Die Dong; Chao Yuan; Meng Zhao; Bo Cui (Food Bioscience, 2025)

Leaves damaged by insect herbivory have consistently different biomechanical traits compared to undamaged leaves within individual plants - Yang Liu; Jifa Cui; Bo Wang (Flora, 2025)

Molecular planarity tailored hole-transporting materials for efficient perovskite solar cells - Xiaozheng Zhao; Xinbao Lin; Can Meng; Yanan Liu; Tianci An; Taoyu Weng; Linfeng Cui; Miaoran Zhang; Bo Liu (Chemical Engineering Journal, 2025)

A zero-strain P2/O3-biphasic cathode material with high comprehensive performance for sodium-ion batteries - Jing Cui; Ranran Li; Zhaojin Li; Di Zhang; Yusheng Wu; Bo Wang (Chemical Engineering Journal, 2025)

Copper sulfide catalysts facilitating zinc sulfide electro-oxidation in aqueous zinc–sulfur batteries - Peng Hei; Guangxu Hu; Lin Yu; Yulai Lin; Xueying Ning; Bo Li; Yuqing Wang; Zhaohui Chen; He Chong; Hao Cheng; Jing Wang; Weibin Cui; et al. (Chemical Engineering Journal, 2025)

Strip clearcutting and replanting effects on soil organic carbon, microbial necromass carbon, and microbial carbon use efficiency in Chinese fir plantations - Xinran Zhao; Huiling Zhou; Hongwei Xu; Lin Xu; Chengming You; Li Zhang; Bo Tan; Zhenfeng Xu; Han Li; Lixia Wang; Sining Liu; Xinglei Cui; et al. (Plant and Soil, 2025)

Health risk assessment of potentially toxic elements in a Tibetan Plateau Wetland, China, using APCS-MLR, PMF, and Monte Carlo simulation - Wei Li; Bo Yang; Ruiqing Huang; Jueyuan Yang; Jianguo Cui; Xuebin Lu; Jian Xiong (Journal of Soils and Sediments, 2025)

Main Controlling Factors of Imbricate Thrust Faults at the Frontal Edge of the Makran Accretionary Wedge–Insights from Physical Simulations - Bo Sun; Fusheng Yu; Jing Liao; Jianming Gong; Jiajie Yan; Wenhao Lei; Jiajun Qu; Haoyue Sun; Zixuan Cui; Jia Ren (Journal of Ocean University of China, 2025)
The frontal edge of the Makran accretionary wedge is characterized by the development of multiple imbricate thrust faults trending E-W and relatively parallel. However, the mechanisms underlying their formation and the factors controlling their development remain subjects of debate. This paper, based on seismic profile analysis, employs physical simulation experiments to establish a ‘wedge’ type subduction model. The study explores the influence of the initial wedge angle, horizontal sand layer thickness, and the presence or absence of a decollement layer on the structural styles of the thrust wedge. Experimental results indicate that as the initial wedge angle decreases from 11° to 8°, the lateral growth of the thrust wedge increases, whereas vertical growth diminishes. When the horizontal sand layer thickness is reduced from 4.5 cm to 3.0 cm, the spacing between the frontal thrusts decreases and the number of thrust faults increases. Both lateral and vertical growth are relatively reduced, resulting in a smaller thrust wedge. When a decollement layer is present, the structural style exhibits layered deformation. The decollement layer constrains the development of back thrusts and promotes the localized formation of frontal thrusts. In conclusion, the imbricate thrust faults at the frontal edge of the Makran accretionary wedge are primarily controlled by the characteristics of the wedge itself and the presence of the decollement layer.

Investigation on dynamic response of rockfall net fences under irregular block impact - Junyi He; Aiguo Xing; Yufang Zhang; Kun Yuan; Jian Cui; Bo Liu (Transportation Geotechnics, 2025)

The response characteristics of fault-crossing tunnel subjected to different sequential combination actions of strike-slip fault dislocation and seismic wave propagation - Xiancheng Mei; Changdong Ding; Jianhe Li; Bo Lou; Zhen Cui; Mingnan Xu; Qian Sheng; Yajie Song; Jian Chen (Soil Dynamics and Earthquake Engineering, 2025)

Dammarane triterpenoids with anti-inflammatory and promoting glucose uptake activities from the leaves of Cyclocarya paliurus - Xiaoqin Liang; Qingfang Zheng; Biqun Zou; Yanqin Li; Liwei Pan; Chenyang Ren; Jiwen Xin; Bo Yang; Ruiyun Yang; Weifeng Xu; Chaowen He; Yanling Cui; et al. (Phytochemistry, 2025)

Environmental and biological controls on ecosystem water use efficiency over paddy fields with different management practices in Southern China - Bo Liu; Yuanzhi Shi; Jun Wei; Rangjian Qiu; Bin Liao; Cheng Li; Xiaoping Chen; Yuanlai Cui (Journal of Hydrology, 2025)

River diversions profoundly impact wetland sedimentation associated with vegetation succession in the Yellow River Delta - Yi’na Li; Qing Wang; Guogui Chen; Bo Pang; Dongxue Li; Baoshan Cui; Zhonghua Ning; Tian Xie (Journal of Hydrology, 2025)

Breaking the zero-flux paradigm: an iterative surface energy balance framework for enhanced cold pixel characterization - Jun Wei; Zhiliang Zhang; Bo Liu; Yuanlai Cui; Yufeng Luo; XiaoPei Tang (Journal of Cleaner Production, 2025)

Effect of soybean peptides on structure and functional properties of soluble soybean polysaccharide edible films - Tian Gao; Chao Yuan; Bo Cui; Pengfei Liu; Zhengzong Wu; Yishan Fang; Lu Lu (Food Hydrocolloids, 2025)

Evaluation of low-temperature high-cycle fatigue life of Q500qENH based on thermodynamic entropy - Xin-bo Zhang; Chuang Cui; Qing-hua Zhang (Engineering Structures, 2025)

Surface engineering of MOF-derived hierarchical porous carbons for ultrasensitive detection and discrimination of anticancer and antibacterial drugs - Junlin He; Jun Wang; Zhonghui Luo; Jiaheng Zhang; Yongrong Deng; Bo Liu; Hui Zhao; Suisui He; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2025)

Development of biodegradable starch-based lambda-cyhalothrin microcapsules for sustainable long-term pest control and enhanced utilization efficacy - Liang Li; Long Chen; Qian Du; Xiquan Ding; Hongyan Chen; Fei Gao; Bo Cui; Haixin Cui; Zhanghua Zeng (Carbohydrate Polymers, 2025)

Starch-based biodegradable active intelligent packaging with color superimposition via emulsion electrospinning nanofiber for meat freshness monitoring and shelf-life extension - Haowei Lv; Deyun He; Enbo Xu; Zhengyu Jin; Haibo Zhao; Chao Yuan; Meng Zhao; Wei Gao; Jianpeng Li; Yang Liu; Zhengzong Wu; Pengfei Liu; et al. (Carbohydrate Polymers, 2025)

Genomic insights into the reticulate evolution of viviparous Phrynocephalus lizards on the Qinghai-Tibetan Plateau - Xianguang Guo; Zhongyi Yao; Bo Cai; Xiao Xiao; Qiwei Xu; Ying Chen; Lin Cui; Xia Qiu; Jinzhong Fu; Yin Qi; Weizhao Yang (Molecular Phylogenetics and Evolution, 2025)

Contrasting effects of different acid rain types on soil nitrogen pools - Xingyu Pan; Yi Jian; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Hongwei Xu; Sining Liu; Lixia Wang; et al. (Journal of Environmental Management, 2025)

Carbon dots-mediated metabolic optimization for acid mitigation in high-load anaerobic digestion systems - Tao Zhou; Xuanbing Chen; Jie Cui; Ting Zhang; Xufang Qian; Bo Zhang (Journal of Environmental Chemical Engineering, 2025)

Characterization of OSA-starch/tea polyphenol complexes with enhanced oil-water interfacial properties by molecular dynamics simulation and isothermal titration calorimetry - Lidan Pan; Xiaorui Liu; Die Dong; Li Guo; Meng Zhao; Bo Cui (Food Chemistry, 2025)

Water-insoluble citrus fiber enhances the textural properties and water-holding capacity of thermally generated kappa-carrageenan gels via skeletal reinforcement - Xiaoyan Wu; Zheng Zhang; Zhijun Zhang; Han Liu; Guimei Liu; Bin Yu; Haibo Zhao; Haiteng Tao; Bo Cui (Food Hydrocolloids, 2025)

Assessing ecological risk of heavy metals in sediment cores using in-situ monitoring and species sensitivity distribution - Xianqiang Lai; Songjun Guo; Meng Cui; Dongyu Xu; Bo Gao (Environmental Research, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Two-dimensional sulfonate-functionalized covalent organic frameworks for large-capacity adsorption of lithium ions - Li Cui; Hefeng Yuan; Bo Yang; Qiaowei Zhang; Hualin Zhang; Juan Li (Desalination, 2025)

Housing segregation in Chinese major cities: A K-nearest neighbor analysis of longitudinal big data - Sebastian Kohl; Bo Li; Can Cui (Computers, Environment and Urban Systems, 2025)

Excellent durability and multifunctional textiles with dual-mode evaporative and radiative cooling enabled by in-situ growth of SiO2 and electrostatic network coating - Luxuan Zhang; Bo Xu; Man Zhou; Ying Liu; Ying Zhang; Li Cui; Ping Wang; Qiang Wang; Yuanyuan Yu (Chemical Engineering Journal, 2025)

Synergistic Rb+-dual-network polymer gel electrolyte enhances stability of dendrite-free Zn2+ batteries - Xin Ye; Sisi Shang; Bo Zhao; Wei Liu; Suting Liu; Cunguo Wang; Sheng Cui; Hongqing Zhou (Chemical Engineering Journal, 2025)

An Interpretable NAO Daily Prediction Model Considering Weighted Causal Effects of Physical Processes - Shijin Yuan; Haoyu Wu; Bin Mu; Yuehan Cui; Bo Qin; Hao Li (Journal of Meteorological Research, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Genome-wide identification of aldehyde dhydrogenase (ALDH) family genes in pepper (Capsicum annuum) reveals involvement of CaALDH7B1 in heat and drought stress tolerance - Bo Yang; Yifen Shang; Lang Wen; Yijia Cui; Zixing Li; Yuan Cheng; Chaochao Liu (Plant Gene, 2025)

Metatranscriptomic insights into nitrogen loss mediated by multi-kingdom microbial interactions in periphytic biofilms under imidacloprid exposure - Zuqiang Cao; Juan Chen; Chao Wang; Peifang Wang; Han Gao; Bingbing Feng; Bo Zhang; Rong Wang; Ge Cui (Journal of Hazardous Materials, 2025)

Ultra-stretchable and subzero-healable epidermal electrodes enabled by kirigami-networked microcrack engineering for human-machine interactions - Ying Xiao; Yilu Cui; Jie Wan; Yang Yang; Xiangrong Shi; Lingui Han; Ziming Wang; Dianpeng Qi; Bo Jiang; Kuiyuan Zhang (Chemical Engineering Journal, 2025)

Balancing optical and electrical properties of CsPbl3 nanocrystals via organic covalent metal salts for enhanced LEDs performance - Wei Shen; Yanxing He; Yanfeng Chen; Suyun Liu; Wei Zhao; Zhongyi Yang; Ye Wu; Bo Cai; Junmin Xia; Zhihua Chen; Hao Cui; Lihui Liu; et al. (Chemical Engineering Journal, 2025)

Molecularly imprinted multifunctional polymer-modified single-atom-homojunctions for sensitive photoelectrochemical Escherichia coli O157:H7 sensing - Hong Zhou; Xufeng Zang; Bo Cui; Yizhong Shen; Haiteng Tao; Yishan Fang (Analytica Chimica Acta, 2025)

A NIR Isophorone-based Zinc Coordination Fluorescence Probe for the Detection of Glyphosate and Application in Environment, Food and Living Systems - Si-Yi Yao; Han-Wen Cui; Zhi-Bo Jiang; Hao Wang; Jing-Yi Li; Yu-Yang Wang; Fan-Qi Shen; Li-Xia Zhao; Ya-Tong Liu; Yue-Li Zou (Journal of Fluorescence, 2025)

Uncertainty design optimization of the main bearing in tunnel boring machine based on the Kriging model with partial least squares - Xinqi Wang; Lintao Wang; Huashan Chi; Bo Yuan; Qingchao Sun; Wei Sun; Yunhao Cui (Tunnelling and Underground Space Technology, 2025)

Resilience-based restoration sequence optimization of disrupted transportation networks: A novel matheuristic approach - Xinhao Cui; Bo Li; Siyue Zhang; Ziguang Ji; Shitao Wang; Rui Luo; Yi Ren; Yiyong Xiao (Transportation Research Part D: Transport and Environment, 2025)

Feldspar dissolution controlled by coal-measure fluids and the impacts on pore structure of tight sandstone reservoirs: The case of the Jurassic Badaowan Formation in the Junggar Basin, Northwestern China - Zhi-Cheng Cui; Ke-Lai Xi; Ying-Chang Cao; Xiang Shan; Wei-Kai Huang; Hua-Jun Guo; Bo Peng; Nian-Ming Zan (Marine and Petroleum Geology, 2025)

Directed evolution of Escherichia coli Nissle 1917 functioning as a methylotrophic chassis - Li-Hua Liu; Zhiqian Zhang; Bo Xu; Gangzhu Yang; Hua Cui; Lijun Su; Yu Zhang; Baoqing Sun; Yi-Rui Wu; Ao Jiang (Chemical Engineering Journal, 2025)

Exploring the role of the rhizosphere in soil carbon cycling: impacts on pools and components of SOC along a chronosequence of Cryptomeria japonica plantations in subtropical China - Dengjie Zhou; Yaling Yuan; Jing Li; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Lin Xu; Li Zhang; Hongwei Xu; Lixia Wang; Sining Liu; et al. (Plant and Soil, 2025)

A Channel-Aware AUV-Aided Data Collection Scheme Based on Deep Reinforcement Learning - Lizheng Wei; Minghui Sun; Zheng Peng; Jingqian Guo; Jiankuo Cui; Bo Qin; Jun-Hong Cui (Journal of Marine Science and Engineering, 2025)
Underwater sensor networks (UWSNs) play a crucial role in subsea operations like marine exploration and environmental monitoring. A major challenge for UWSNs is achieving effective and energy-efficient data collection, particularly in deep-sea mining, where energy limitations and long-term deployment are key concerns. This study introduces a Channel-Aware AUV-Aided Data Collection Scheme (CADC) that utilizes deep reinforcement learning (DRL) to improve data collection efficiency. It features an innovative underwater node traversal algorithm that accounts for unique underwater signal propagation characteristics, along with a DRL-based path planning approach to mitigate propagation losses and enhance data energy efficiency. CADC achieves a 71.2% increase in energy efficiency compared to existing clustering methods and shows a 0.08% improvement over the Deep Deterministic Policy Gradient (DDPG), with a 2.3% faster convergence than the Twin Delayed DDPG (TD3), and reduces energy cost to only 22.2% of that required by the TSP-based baseline. By combining a channel-aware traversal with adaptive DRL navigation, CADC effectively optimizes data collection and energy consumption in underwater environments.

3D Dubins Curve-Based Path Planning for UUV in Unknown Environments Using an Improved RRT* Algorithm - Feng Pan; Peng Cui; Bo Cui; Weisheng Yan; Shouxu Zhang (Journal of Marine Science and Engineering, 2025)
The autonomous navigation of an Unmanned Underwater Vehicle (UUV) in unknown 3D underwater environments remains a challenging task due to the presence of complex terrain, uncertain obstacles, and strict kinematic constraints. This paper proposes a novel smooth path planning framework that integrates improved Rapidly-exploring Random Tree* (RRT*) with 3D Dubins curves to efficiently generate feasible and collision-free trajectories for nonholonomic UUVs. A fast curve-length estimation approach based on a backpropagation neural network is introduced to reduce computational burden during path evaluation. Furthermore, the improved RRT* algorithm incorporates pseudorandom sampling, terminal node backtracking, and goal-biased exploration strategies to enhance convergence and path quality. Extensive simulation results in unknown underwater scenarios with static and moving obstacles demonstrate that the proposed method significantly outperforms state-of-the-art planning algorithms in terms of smoothness, path length, and computational efficiency.

Soil disturbance induced by urban shield tunnelling in sandy pebble soil considering non-coaxiality and anisotropy - Jian Cui; Zhigang Yao; Tao Yu; Kaichen Ying; Yong Fang; Wanghao Xu; Yufang Zhang; Jian Li; Bo Liu (Tunnelling and Underground Space Technology, 2025)

A new three-dimensional peak shear strength criterion of rock joints considering true-sheared asperities - Yingchun Li; Yue Cui; Yuzong Li; Rui Yong; Bo Li (International Journal of Rock Mechanics and Mining Sciences, 2025)

Study on the ground temperature response induced by GSHP system operation under different geological conditions - Shiyu Zhou; Hanbing Jia; Bo Zhou; Jiying Liu; Ping Cui; Mingzhi Yu (Geothermics, 2025)

Rapid formation of high-energy-density methane hydrates promoted by L-cysteine: A promising approach for solidified natural gas - Bo Li; Yuan-Le Li; Xin-Miao Liu; Ting-Ting Zhang; Qing-Cui Wan; Gui-Cai Li (Gas Science and Engineering, 2025)

Gelatin bloom values affects the starch molecular structure changes and digestibility of resulting wheat starch/gelatin complexes - Yue Cheng; Yifan Chen; Wei Gao; Xuemin Kang; Bo Cui (Food Hydrocolloids, 2025)

Cobalt-doped covalent organic framework effectively enhances Fenton-like activity: radical and non-radical dual pathways enhancement - Yunchao Ma; Chuanxue You; Yuxin Yao; Shengnan Qi; Tianyu Zhou; Wei Jiang; Keyu Cui; Bo Hu; Linlin Liu (Chemical Engineering Journal, 2025)

An automated river shoreline space type identification method using remote sensing data that considers space-channel attention multi-scale features - Shijiao Qiao; Wanlai Xue; Kun Jia; Jie Li; Mu Xia; Zhulin Chen; Haiying Jiang; Bo Yuan; Guofeng Tao; Yuran Cui; Linlin Zhao; Zihang Jiang; et al. (International Journal of Remote Sensing, 2025)

Progress in the bioavailability of natural astaxanthin: Influencing factors, enhancement strategies, evaluation methods, and limitations of current research - Wei Wang; Yan Cui; Huimin Liu; Yu Wang; Bo Nan; Xia Li; Yuhua Wang (Trends in Food Science & Technology, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Structural response analysis of different submerged floating tunnel route selection conditions in the complex strait under the action of typhoon Sepat - Cheng Cui; Bo Huang; Minglin Chen; Wenlong Luo; Jianting Zhou; Hao Ding; Ke Li; Liang Cheng; Dan Zhong; Jiawei Zhou (Ocean Engineering, 2025)

Analysis of seepage and hysteresis effect mechanism of unsaturated loess based on resistivity test - Bo Cui; Tianfeng Gu; Jiading Wang; Jiacheng Li; Nannan Fan; Xin Li; Zhijie Song; Min Hao (Journal of Hydrology, 2025)

Improving gap-filling performance for CH4 fluxes of eddy covariance data by combining marginal distribution sampling and machine learning algorithm over paddy fields - Linhua Ma; Qianan Yu; Yuanlai Cui; Bo Liu; Wenxiang Tian; Bin Liao; Luguang Liu; Wei Dong; Jie Huang (Journal of Cleaner Production, 2025)

The compounding effect of re-adsorptionon on bioaccessibility of methylmercury in rice-based infant cereals digestion assessment - Xin Wang; Wenbin Cui; Yingjun Wang; Yanbin Li; Bo Meng; Genique Nicolas; Michael Ojeda; Yong Cai (Journal of Environmental Sciences, 2025)

Comprehensive assessment of carbon footprint and water footprint of ammonia synthetic process based on liquefied natural gas cold energy utilization - Qiming Wu; Yaru Zhou; Wenwu Xu; Yangyang Wang; Yangyang Liu; Yinglong Wang; Peizhe Cui; Sheng Yang; Bo Wang; Xiaolei Zhao (Fuel, 2025)

Lipid pro-oxidative reactions mediated by heat, light and microwave and the structural characteristics of their products: Revealed via multi-omics approaches - Zheng Zhou; Shuang Cui; Bo Wang; Dayong Zhou; Xuhui Huang; Lei Qin (Food Chemistry, 2025)

Comprehensive mechanisms of epigallocatechin-3-gallate (EGCG) metabolism during tea dieback disease infection in tea plant (Camellia sinensis) - Yiyong Chen; Bo Zhou; Jianlong Li; Man Zhang; Yingying Cui; Jinchi Tang (Food Bioscience, 2025)

Wide-bandgap perovskite solar cells with > 1.34 V Voc for all-perovskite tandems - Yunfei Li; Nannan Sun; Bo Feng; Wen Li; Zhengbo Cui; Wenxiao Zhang; Sheng Fu; Xiaodong Li; Junfeng Fang (Chemical Engineering Journal, 2025)

Optimized interlayer of MnO2 nanoarrays decorated carbon fibers/polyamide composites with significantly improved mechanical property and electromagnetic interference shielding - Na Sun; Quanqing Cui; Lu Liu; Bo Zhu; Bin Yu (Chemical Engineering Journal, 2025)

Type I Interferon Signalling and Ischemic Stroke: Mechanisms and Therapeutic Potentials - Pan Cui; Bo Song; Zongping Xia; Yuming Xu (Translational Stroke Research, 2025)

Integrative N-glycomics and N-glycoproteomics landscape reveals up-regulation of complex-type N-glycosylation in the tolerance of peach fruit to chilling injury - Huiwen Wang; Tonghao Cui; Jiaqi Wang; Ruohan Ou; Yilong Liu; Bo Zhang; Changjie Xu; Changqing Zhu; Miaojin Chen; Yanna Shi; Yuanjiang Pan; Kunsong Chen; et al. (Postharvest Biology and Technology, 2025)

Variation in climate and hydrological conditions in Southwest China during the mid-to-late Holocene, inferred from stalagmite multiple proxies - Hua-Yan Li; Yao Wu; Ting-Yong Li; Rong Duan; Hai-Bo Wang; Jia-Hui Cui; Chao-Jun Chen; Yue Jin; Yue-Hua Xiang; Zi-Qi Liu; Jun-Yun Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Soil nutrients determine multidimensional absorptive root traits of Cryptomeria japonica var. sinensis plantations along a chronosequence in subtropical forest - Chunran Liu; Lihua Wang; Jing Li; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Lin Xu; Hongwei Xu; Li Zhang; Lixia Wang; et al. (Journal of Environmental Management, 2025)

How to regulate retrogradation behavior of wheat starch after different amylases: Structural analysis - Yunlong Cui; Dengyue Sun; Li Guo; Bo Cui; Yu Zhu; Meng Yang; Jinpeng Wang; Chunrui Sun (Journal of Cereal Science, 2025)

Fine particulate matter components and reproductive hormones in female adults: A 15-year longitudinal cohort study - Siyi Chen; Cui Guo; Chunquan Ou; Yiling Zheng; Yufei Liu; Jun Ma; Xingcheng Lu; Bo Huang; Ta-Chien Chan (International Journal of Hygiene and Environmental Health, 2025)

Unveiling the mechanism of Gelatin's influence on starch digestibility: A focus on amylopectin chain distribution - Yifan Chen; Yue Cheng; Wei Gao; Xuemin Kang; Bin Yu; Li Guo; Meng Zhao; Chao Yuan; Bo Cui (Food Hydrocolloids, 2025)

Impact of agricultural straw open-field burning on concentrations of six criteria air pollutants in China - Hao-Neng Huang; Zhou Yang; Yuming Guo; Jia-Jun Ma; Bo-Wen Ming; Jun Yang; Cui Guo; Li Li; Chun-Quan Ou (Environmental Pollution, 2025)

Mapping of identity by descent reveals genes shaping morphology and biological traits in the cultivated lettuce varieties during the long-term crossbreeding - Qianqian Zhang; Bo Cui; Xinyu Dong; Wenjun Lv; Xueying Xie; Yujue Wang; Zhongxu Guo; Just Jensen (Theoretical and Applied Genetics, 2025)

Transglutaminase 2 reduces the polyspermy of porcine oocytes by promoting the hardening of zona pellucida - Zhaokang Cui; Jianli Zhang; Jun Zhang; Jifeng Zhong; Huili Wang; Bo Xiong (Theriogenology, 2025)

Development of a bionic jellyfish robot for collecting polymetallic nodules - He Li; Shengqi Cui; Xuan Wang; Bo Yu; Guanzhong Wang; Chaoning Cao; Yi Shen; Qingliang Zeng (Ocean Engineering, 2025)

Study on the kinetic characteristics of polyoxymethylene (POM) pyrolysis and hydrothermal conversion - Cui Wang; Peng Liu; Bo Bai; Hui Jin (Journal of Cleaner Production, 2025)

Preparation and characterization of covalent starch-protein-tea polyphenol complexes with enhanced interfacial properties - Die Dong; Tenglong Geng; Lidan Pan; Xiaorui Liu; Chenxi Yu; Chao Yuan; Li Guo; Meng Zhao; Bo Cui (Food Research International, 2025)

Eco-friendly synthesis of Arabinoxylan-Catechin conjugates: Enhanced functional and antioxidant properties via cold plasma and ultrasonic methods - Dima Atehli; Zhiyuan Xu; Xiaoyu Guo; Meng Xiao; Boyu Cheng; Xing Jia; Bo Wu; Ji Kang; Qingbin Guo; Steve W. Cui (Food Chemistry, 2025)

Prevalence and Predictors of Hemorrhagic Foci on Long-term Follow-up MRI of Recent Single Subcortical Infarcts - Shuai Jiang; Wen-Zuo Shang; Jing-Yu Cui; Yu-Ying Yan; Tang Yang; Yi Hu; Le Cao; Xun Yue; Ruo-Su Pan; Chen Ye; Jia-Yu Sun; Bo Wu (Translational Stroke Research, 2025)
Hemorrhagic foci surrounding the lacune in the long-term evolution of recent single subcortical infarcts (RSSIs) remains largely unexplored. We aimed to determine the prevalence, characteristics, and predictors of hemorrhagic foci in patients with RSSI. From a prospective, longitudinal study of RSSIs, we recruited patients who underwent multimodal MRI assessments both at baseline and approximately one year after the stroke onset. Hemorrhagic foci were identified using susceptibility-weighted imaging (SWI). Among 101 patients with RSSI, nearly half (n = 45, 44.6%) had hemorrhagic foci within the index RSSI lesions on follow-up SWI. RSSIs with hemorrhagic foci formation were associated with a longer time to follow-up imaging (median 449 versus 401 days, P = 0.005) and higher likelihood of being located in the anterior circulation compared to those without hemorrhagic foci (88.9% versus 64.3%, P = 0.003). Hemorrhagic foci were also associated with larger lesion size (P < 0.001), a higher proportion of cavitation formation (P = 0.003), higher baseline NIHSS scores (P = 0.004), and poorer functional outcomes (P = 0.001). In the subset of RSSIs in the lenticulostriate artery (LSA) territory, after adjustment for covariates, larger initial lesion volume (OR 1.80, 95% CI 1.13–2.87; P = 0.014) and greater decreases in LSA total length (OR 0.59, 95% CI 0.36–0.96; P = 0.035) were independently associated with hemorrhagic foci formation. The extent of ischemia in the initial infarct is predictive of the presence of hemorrhagic residues. Our findings contribute to the current understanding of the mechanisms underlying the evolution of RSSIs.

Correction to: Efficient capture of U(VI) by magnetic Zr(IV)‑ethylenediamine tetramethylene phosphonic acid inorganic‑organic hybrid - Qie Luo; Wenzheng Cui; Huan Wang; Bo Xiao; Lei Chen; Youqun Wang; Zhibin Zhang; Yunhai Liu; Xiaohong Cao (Environmental Science and Pollution Research, 2025)

Semantic segmentation-based observation pose estimation method for tomato harvesting robots - Lizhong Dong; Licheng Zhu; Bo Zhao; Ruixue Wang; Jipeng Ni; Suchun Liu; Kaikang Chen; Xuezhi Cui; Liming Zhou (Computers and Electronics in Agriculture, 2025)

Parallel RepConv network: Efficient vineyard obstacle detection with adaptability to multi-illumination conditions - Xuezhi Cui; Licheng Zhu; Bo Zhao; Ruixue Wang; Zhenhao Han; Weipeng Zhang; Lizhong Dong (Computers and Electronics in Agriculture, 2025)

Study on the sliding mechanism of slopes along railways in loess regions of China under the coupling effect of extreme rainfall and train vibration - Kai Han; Jiading Wang; Peng Xiao; Dengfei Zhang; Bo Cui; Tao Xiao (Transportation Geotechnics, 2025)

Seismic stability of anchored slopes considering tension-shear coupling effect by modiﬁed pseudo-dynamic approach - Xiaolei Wu; Zhengnan Cui; Bo Yang; Bo Lian (Soil Dynamics and Earthquake Engineering, 2025)

Environmental DNA metabarcoding: Current applications and future prospects for freshwater fish monitoring - Shuaishuai Liu; Juan Chen; Ge Cui; Bo Zhang; Bingcheng Yan; Qihao Nie (Journal of Environmental Management, 2025)

Enhancing germination and growth in Malania oleifera Chun & S. K. Lee seeds through gibberellic acid priming - Xuelin Su; Xuying Wang; Nan Cui; Hailing Xu; Ting Tian; Bo Wei (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Microstructure and characteristics of phase-separated gels of Type-A gelatin and hydroxypropyl starch: pH responsiveness - Xuedi Ma; Zheng Zhang; Zhao Li; Zhengzong Wu; Lu Lu; Katsuyoshi Nishinari; Meng Zhao; Bo Cui (Food Hydrocolloids, 2025)

Bio-inspired porous adsorbents with lotus-leaf-like hierarchical structures and mussel adhesive surfaces for high-capacity removal of toxic dyes - Bo Cui; Zhuojun Yan; Naishun Bu; Lijuan Liang; Wanting Yao; Suri Wang; Jingbo Cui; Weihan Yan; Lini Yang; Yajie Yang; Ye Yuan; Lixin Xia (Environmental Research, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Synergistic modulation of iron phosphide and phosphorus-doped carbon to boost ammonia electrosynthesis from nitrate - Zihao Fan; Bo Pang; Wanting Chen; Fujun Cui; Xinhong Qi; Xuemei Wu; Ning Wang; Weiming Yu; Gaohong He (Chemical Engineering Journal, 2025)

An innovative approach to evaluate debris flow scale-activity across diverse aridity zones: Fusion of image recognition and geomorphometric analysis - Zhenni Jiang; Jiao Wang; Guotao Zhang; Peng Cui; Can Yang; Yifan Zhang; Bo Zhang; Chaoyue Li; Hao Wang; Jie Liu; Zhiwei Yang (CATENA, 2025)

Flow-electrode capacitive deionization for enhanced selective separation of ammonia, phosphorus, and caproate from sewage sludge fermentation: Performance and mechanistic insights - Huimin Sun; Pengyao Wang; Xuedong Zhang; Bo Wu; Minhua Cui; Hongbo Liu; Mustafa Evren Ersahin; Hale Ozgun; He Liu (Bioresource Technology, 2025)

The impact of aflatoxin B1 on animal health: Metabolic processes, detection methods, and preventive measures - Tianyang Wang; Runzi Cui; Hai-Fan Yu; Dian Yang; Shuting Zhang; Yuzhe Nie; Chun-Bo Teng (Toxicon, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Discovery of a polyester polyurethane-degrading bacterium from a coastal mudflat and identification of its degrading enzyme - Liting Zhang; Kaixun Cao; Hao Liu; Yuwei Wang; Bo Zhang; Heming Han; Zhongli Cui; Hui Cao (Journal of Hazardous Materials, 2025)

Electrospun dibenzo-18-crown-6 polyimide dendritic nanofiber membranes for efficient adsorption separation of cesium - Jian Xiao; Feidong Yang; Jintao He; Junyuan Hua; Bo Dong; Xiaohua Ma; Zhenyu Cui; Jianxin Li (Journal of Environmental Chemical Engineering, 2025)

Ag modification and defect engineering optimization on three-dimensional coral-like high-entropy oxides to trigger effective oxygen evolution reaction - Bo Zhang; Mengzhao Liu; Meiqin Cui; Wenxue Lu; Ping Geng; Weiming Yi (Journal of Environmental Chemical Engineering, 2025)

Effects of different ratios of water and glycerol on the physicochemical properties of starch-based straws - Pengfei Liu; Yue Li; Deyin Wang; Ruoxuan Xu; Yandu Jiang; Xinyu Qiao; Wei Gao; Bin Yu; Bo Cui (Food Chemistry, 2025)

In-situ preparation of CeO2@MIL-88B nanocomposite for improving “turn-on” fluorescent sensing toward Thiabendazole - Yan Fan; Bo Hou; Fang Lu; Dao Liu; Xiang Cui (Food Chemistry, 2025)

Effects of different ratios of glycerol to erythritol on the structure and properties of starch straws during long term storage - Chenyu Ma; Guoqing Wang; Chuanjin Xia; Li Guo; Bo Cui; Xianfeng Du; Jinpeng Wang; Chunrui Sun (Food Chemistry, 2025)

Enhancement in stability and reusability: Immobilization and characterization of inulin fructotransferase from Paenarthrobacter aurescens QL1.001 in calcium alginate microcapsules - Jiaxin Cui; Tengchao Li; Yuyu Zhao; Chao Yuan; Die Dong; Jianpeng Li; Meng Zhao; Bo Cui (Food Bioscience, 2025)

Synergistic effect of 2′-Fucosyllactose or galactooligosaccharide with Bifidobacterium bifidum DNG6 improves the intestinal barrier by modulating the SCFAs-TLR4/NF-κB cascade response in DSS-induced colitis in mice - Cui-Cui Sun; Yu-Qi Wang; Xin-Yu Wang; Guo-Fang Zhang; Hong-Fang Cao; Ge Song; Li-Bo Liu; Chun Li; Irina Valeryevna Boyarineva; Peng Du (Food Bioscience, 2025)

Chitosan/pre-gelatinized waxy corn starch composite edible orally disintegrating film for taurine delivery - Yuhang Li; Chao Yuan; Bo Cui; Pengfei Liu; Yishan Fang; Zhengzong Wu; Haibo Zhao; Jiawen Liu (Food Hydrocolloids, 2025)

Structural and physicochemical properties of corn starch modified by phosphorylase b, hexokinase and alkaline phosphatase - Shuo Sun; Dengyue Sun; Li Guo; Bo Cui; Feixue Zou; Jinpeng Wang; Chunrui Sun; Yu Zhu; Xueling Li (Carbohydrate Polymers, 2025)

Assessing the impact of 2022 extreme drought on the Yangtze River basin using downscaled GRACE/GRACE-FO data obtained by partitioned random forest algorithm - Lilu Cui; Yu Li; Bo Zhong; Jiachuan An; Jiacheng Meng; Haoyang Guo; Chuang Xu (International Journal of Remote Sensing, 2025)

Mechanism of Non-blasting Supercritical CO2 Fracturing in Rocks Under Reverse Fault Conditions: Dynamic and Quantitative Monitoring Using Coda Waves - Chao Zhu; Jie Chen; Yuanyuan Pu; Bo Liu; Jianing Zhang; Yi Cui (Rock Mechanics and Rock Engineering, 2025)

Unveiling the global dynamics of dissolved organic carbon in aquatic ecosystems: Climatic and anthropogenic impact, and future predictions - Yuexia Guo; Haoran Peng; Qirui Wang; Jiaqi Wang; Zhengyu Wu; Bo Shao; Guodong Xing; Zhao Huang; Feng Zhao; Hongyang Cui; Xiaoyu Cui; Yindong Tong (Science of The Total Environment, 2025)

Bioenhanced remediation of dibutyl phthalate contaminated black soil by immobilized biochar microbiota - Yue Tao; Yao Wang; Yunhe Cui; Rui Sun; Bo Zhang; Jianhua Qu; Hongguang Cai; Ying Zhang (Journal of Environmental Management, 2025)

Fe, Cu dual-atom catalysts assisted molecularly imprinted electrochemiluminescence sensor for ultrasensitive detection of trichlorfon - Xinran Wang; Xufeng Zang; Hong Zhou; Na Wang; Yishan Fang; Bo Cui (Food Chemistry, 2025)

Spatial exposure and oxidative accumulation of reactive hydroxyl groups in starch retrogradation through transglucosidase and hexose oxidase - Yunlong Cui; Dengyue Sun; Li Guo; Bo Cui; Jinpeng Wang; Chunrui Sun; Xianfeng Du (Food Chemistry, 2025)

Improving paste stabilities of cassava starch through molecular density after maltogenic amylase and transglucosidase - Shuo Sun; Ruobing Li; Dengyue Sun; Li Guo; Bo Cui; Feixue Zou (Food Chemistry, 2025)

The interaction between maize resistant starch III and Bifidobacterium adolescentis during in vitro fermentation - Xinzhu Zhao; Shuyu Jia; Haibo Zhao; Pengfei Liu; Zhengzong Wu; Haiteng Tao; Bin Yu; Bo Cui (Food Chemistry, 2025)

Adjusting the hydrophobicity of recombinant microgels to improve interfacial activity: Using a promising pickering emulsion stabilizer with a dense cubic structure - Han Liu; Xiaoyan Wu; Fuying Wang; Hongxun Tao; Bin Yu; Haibo Zhao; Jianpeng Li; Minwei Xu; Haiteng Tao; Bo Cui; Yuxiao Wang (Food Hydrocolloids, 2025)

Superior broadband sound absorption in hydrophobicity and mechanical enhancing Poly(urethane-imide)/Melamine aerogels via ambient drying - Enyuan Hu; Yingwen Zhu; Haiyun Li; Cheng Deng; Bo Cui; Lei Zhao; Jinhui Wu; Xinmiao Wang; Mengfu Zhu (Chemical Engineering Journal, 2025)

Zinc-induced photocrosslinked konjac glucomannan/glycyrrhizic acid hydrogel promotes skin wound healing in diabetic mice through immune regulation - Jian Li; Deguang Wu; Zhiwen Su; Jiayi Guo; Luyang Cui; Hao Su; Yan Chen; Bo Yu (Carbohydrate Polymers, 2025)

Starch/polyacrylamide hydrogels with flexibility, conductivity and sensitivity enhanced by two imidazolium-based ionic liquids for wearable electronics: Effect of anion structure - Ziling Zhang; Lu Lu; Bingbing Hong; Qichao Ye; Li Guo; Chao Yuan; Bo Liu; Bo Cui (Carbohydrate Polymers, 2025)

Investigation of the solar activity and QBO effects on the near-space environment - Bo Li; Ruifei Cui; Libin Weng (Acta Geophysica, 2024)
Based on the wavelet method, we investigate the solar activity and quasi-biennial oscillation (QBO) signals in the near-space environment by using the modern-era retrospective analysis for research and applications, version-2 data and sounding of the atmosphere using broadband emission radiometry (SABER) onboard the thermosphere, ionosphere, mesosphere energetics, and dynamics satellite (TIMED/SABER). The results indicate that the annual variation mainly dominates from stratosphere to mesosphere at middle latitudes, which is more significant and stable in the southern hemisphere. Moreover, the temperature of top near space is affected by the solar activity, and it can vary over 5 K inner one solar cycle. The QBO signal is obviously seen in the stratospheric zonal wind and temperature, which is obviously existed only at a narrow latitude band between 10°S and 10°N, and its altitude range above the equator region is 20–40 km, while it turns to be 20–30 km over 10°S and 10°N, but seemly not existed in the mesosphere. Generally, our results would help to understand the influence of solar activity and QBO.

StraTracker: A dynamic counting method for growing strawberries based on multi-target tracking - Qilin An; Yongzhi Cui; Wenyu Tong; Yangchun Liu; Bo Zhao; Liguo Wei (Computers and Electronics in Agriculture, 2024)

Effects of microplastics separate exposure and co-exposure to 17β-estradiol on the productive performance of juvenile female Chinese mitten crab (Eriocheir sinensis) - Yang Fu; Jian Zhang; Yilong Cui; Bo Li; Siming Huo; Jiayu Du; Yanfei Li (Science of The Total Environment, 2024)

Influence of spectral and molecular composition of dissolved organic matter on labile Cd mobility in riparian soils in the Three Gorges Reservoir, China - Meng Cui; Dongyu Xu; Xiaobo Liu; Xianqiang Lai; Moli Zhang; Bo Gao (Science of The Total Environment, 2024)

Formation and evolution of thermokarst landslides in the Qinghai-Tibet Plateau, China - Tao Wei; Hao Wang; Peng Cui; Yan Wang; Bo Zhang; Rui-Long Wei; Zhen-Xing Liu; Chao-Yue Li (Science of The Total Environment, 2024)

A comprehensive genetic variant reference for the Chinese population - Tao Jiang; Hongzhe Guo; Yadong Liu; Gaoyang Li; Zhe Cui; Xinran Cui; Yue Liu; Yang Li; Anqi Zhang; Shuqi Cao; Tianyi Zhao; Liran Juan; et al. (Science Bulletin, 2024)

Protecting celtuce (Lactuca sativa L. var. augustana) slices against storage-induced oxidative stress and discoloration by using diode laser exposure - Bo Wen; Yinghui Xiao; Weiyan Zhang; Shijiang Cui; Junbing Li; Xueren Yin; Suriyan Supapvanich (Postharvest Biology and Technology, 2024)

Effects of steady flow and side hull layouts on motions and added resistance of a trimaran sailing in waves - Zhifei Wu; Bo Zhou; Yu Wang; Jiahe Zou; Xiaohui Cui; Guiyong Zhang (Ocean Engineering, 2024)

Metabolic variation and oxidative stress responses of clams (Ruditapes philippinarum) perturbed by ofloxacin exposure - Bo Zhang; Xiaotong Wang; Fanping Meng; Shuhao Du; Haiping Li; Yufan Xia; Yu Yao; Ping Zhang; Jiali Cui; Zhengguo Cui (Journal of Hazardous Materials, 2024)

Conservation implications of climatically heterogeneous areas for species diversity in a biodiversity hotspot - Feng Liu; Zhiyuan Liang; Jin Ye; Jie Li; Feiling Yang; Zuocheng Li; Dongsheng Cui; Lingyan Yan; Bo Li; Jinming Hu (Journal of Environmental Management, 2024)

Construction of Bi5O7I/Bi3O4Br heterojunction with abundant oxygen vacancies to enhance photocatalytic performance - Jian Feng; Xia Ran; Li Wang; Bo Xiao; Keqin Zhang; Jinming Zhu; Zuoji Liu; Chaozhong Li; Xinai Cui; Rong Li; Guangwei Feng (Journal of Environmental Chemical Engineering, 2024)

Comprehensive review of plant-derived anti-hyperlipidemia peptides: Production, anti-hyperlipidemia mechanism, and structure-activity relationship study - Liuyi Wei; Hao Wu; Xufeng Wang; Li Wen; Bo Cui; Yunhui Cheng (Food Chemistry, 2024)

Integrated volatolomics and lipidomics analysis reveal the characteristic flavor formation mechanism in steamed large yellow croaker (Pseudosciaena crocea) - Shuang Cui; Bo Wang; Zheng Zhou; Yuying Zhang; Dayong Zhou; Xuhui Huang; Lei Qin (Food Bioscience, 2024)

Roles of mTOR-p70S6K signaling pathway and HO-1 in ethylbenzene-induced hepatoxic effects in L02 cells - Siyu Liu; Linlin Chen; Hui Peng; Qiang Zhang; Qiang Zeng; Bo Cui; Ming Zhang (Food and Chemical Toxicology, 2024)

Starch/ionic liquid/hydrophobic association hydrogel with high stretchability, fatigue resistance, self-recovery and conductivity for sensitive wireless wearable sensors - Jingmin Shen; Lu Lu; Rongtong He; Qichao Ye; Chao Yuan; Li Guo; Meng Zhao; Bo Cui (Carbohydrate Polymers, 2024)

Identification of the synonymous variant c.3141G > A in TNRC6B gene that altered RNA splicing by minigene assay - Feiyu Zhou; Hongping Zhong; Bo Wu; Yaqiong Cui; Jiaci Li; Xiaodong Jia; Changshun Yu; Dong Li; Jianbo Shu; Chunquan Cai (Molecular Biology Reports, 2024)

Screening the characteristic hyperspectral wavelength variables of peanut leaves based on coupled algorithms to predict SPAD value in peanut - Tao Su; Xinbei Liu; Bo Lei; Zongyou Cao; Junnan Di; Liangquan Xu; Xingyuan Cui (International Journal of Remote Sensing, 2024)

Effect of alfalfa downy mildew (Peronospora aestivalis) infection on the growth and development of Therioaphis trifolii (Homoptera: Aphidiidae) - Lin-bo Xu; Liang-bin Yu; Fang-zheng Yue; Dan-yang Wang; Wen-long Li; Ba-teer Wulan; Yan-wei Cui (Crop Protection, 2024)

Interspecific competition enhances microcystin production by Microcystis aeruginosa under the interactive influences of temperature and nutrients - Xiaoyu Cui; Ning Yang; Hongyang Cui; Qing Yang; Zhengyu Wu; Bo Shao; Yingxin Zhao; Yindong Tong (Water Research, 2024)

Deteriorating wintertime habitat conditions for waterfowls in Caizi Lake, China: Drivers and adaptive measures - Xiudi Zhu; Bo Cheng; Hongqing Li; Lizhi Zhou; Fengling Yan; Xiaoyuan Wang; Qiang Zhang; Vijay P. Singh; Lijuan Cui; Bo Jiang (Science of The Total Environment, 2024)

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

Analysis of dissolved organic matter characteristics in pharmaceutical wastewater via spectroscopy combined with Fourier-transform ion cyclotron resonance mass spectrometry - Chenqiang Yang; Ruixue Sun; Jiansheng Cui; Bo Yao; Yankai Guo (Journal of Hazardous Materials, 2024)

Influences of released humic acids during thermal hydrolysis on sludge anaerobic digestion: New insights from the molecular weight of humic acids - Yaya Sun; Hongbo Liu; Jiaxin Wen; Hang Xiao; Mingze Shi; Xinlei Lu; Kai Shen; Xuedong Zhang; Bo Fu; Minhua Cui; Yajie Li; Salma Tabassum; et al. (Journal of Environmental Management, 2024)

How G4-amylase and hexose oxidase synergistically improve the qualities and inhibit the retrogradation of steamed breads: A comprehensive study on molecular mechanisms and quality characteristics - Yunlong Cui; Dengyue Sun; Li Guo; Bo Cui; Yu Zhu; Meng Yang; Jinpeng Wang; Chunrui Sun (Journal of Cereal Science, 2024)

The action mechanism of annealing temperatures after rapid cooling of mung bean starch-based drinking straws - Kun Wang; Chuanjin Xia; Lu Lu; Li Guo; Bo Cui; Feixue Zou; Jinpeng Wang; Chunrui Sun (Journal of Cereal Science, 2024)

Kinetic study on the effect of ice nucleation and generation on methane hydrate dissociation below the quadruple point - Ting-Ting Zhang; Bo Li; Wen-Na Wei; Jing-Chun Feng; Qing-Cui Wan (Gas Science and Engineering, 2024)

The intensification of moisture resistance over MFI zeolite via heteroatom incorporation for diluted CO2 capture - Quanli Ke; Pengyun Pan; Mei Lu; Guonan Fang; Wei Zhang; Ruina Zhang; Guokai Cui; Xiaopo Niu; Feng Xiong; Ying Zhou; Bo Zhao; Hanfeng Lu (Fuel, 2024)

Molecularly imprinted Photoelectrochemical sensor for Escherichia coli based on Cu:ZIF-8/KZ3TTz heterojunction - Xiaoqing Wang; Xufeng Zang; Laiyi Deng; Fei Tan; Xingbo Liu; Zhiguo Zhang; Bo Cui; Yishan Fang (Food Chemistry, 2024)

Changes in the properties of the corn starch glycerol film in a time-dependent manner during gelatinization - Jiarui Wang; Xin Xu; Bo Cui; Bin Wang; A.M. Abd El-Aty (Food Chemistry, 2024)

The dispersibility of biphasic stabilized oil-in-water emulsions improved by the interaction between curdlan and soy protein isolate - Fuying Wang; Jianpeng Li; Yuxiao Wang; Han Liu; Bin Yu; Haibo Zhao; Rentang Zhang; Haiteng Tao; Xin Ren; Bo Cui (Food Chemistry, 2024)

Improvement of O/W emulsion stability and rheological properties by highly branched cyclic dextrin and preparation of a novel emulsion gel - Wei Liu; Chao Yuan; Bo Cui; Bin Yu; Pengfei Liu; Wei Gao; Jiawen Liu (Food Hydrocolloids, 2024)

Physicochemical and digestible properties of corn starch/gelatin complexes: Effect of pH, type of gelatin, and gelatin/starch ratio - Yi Liu; Furun Zheng; Haibo Zhao; Jianpeng Li; Die Dong; Chao Yuan; Kangyi Zhang; Katsuyoshi Nishinari; Meng Zhao; Bo Cui (Food Hydrocolloids, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Chitin nanocrystal Pickering emulsions for sustainable release pesticide microencapsulation with superior leaf adhesion and enhanced safety - Long Chen; Liang Li; Hongyan Chen; Bo Cui; Fei Gao; Jinming Gao; Xiang Zhao; Yan Wang; Haixin Cui; Zhanghua Zeng (Chemical Engineering Journal, 2024)

Molecularly imprinted electrochemiluminescence-colorimetric dual-mode sensor based on Mn@NC nanozyme amplification for the detection of phoxim - Xinran Wang; Xufeng Zang; Xin Wang; Wenjie Zhang; Yishan Fang; Bo Cui (Chemical Engineering Journal, 2024)

Efficient sodium ion transport enhanced by anionophilic sites in polymer-supported plastic crystal electrolyte for high performance sodium metal anode - Mengyang Cui; Yiyang Li; Bo Jin; Shitong Sun; Qing Jiang (Chemical Engineering Journal, 2024)

In situ growth of hydrophobic 3D porous Zn@Ag electrode in achieving excellent performance for eCO2RR - Shenglin Yan; Xinyu Zhang; Samah A. Mahyoub; Bo Zhang; Xiangbei Wan; Yanran Cui; Pengfei Xie; Qiong Wang; Zhenmin Cheng; Zhenglong Li (Chemical Engineering Journal, 2024)

Octenylsuccinylation strategy to construct high-amylose maize starch–myristic acid complexes with high thermal stability, complexation efficiency and anti-retrogradation ability - Wenmin Duan; Yifan Dong; Xinyu Qiao; Wei Gao; Chao Yuan; Pengfei Liu; Zhengzong Wu; Bo Cui (Carbohydrate Polymers, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

Autophagy activation ameliorates the fibrosis of trabecular meshwork cells induced by TGFβ2 through the promotion of fibrotic proteins degradation - Gang Wang; Rumeng Zhao; Zhenyang Guo; Huiling Cui; Di Wang; Jing Ren; Shichao Zhu; Ke Zhang; Bo Tang; Jingyi Zhang; Peng Li; Shichao Duan; et al. (Human Cell, 2024)

Dynamic Response Prediction Model for Jack-Up Platform Pile Legs Based on Random Forest Algorithm - Xiaohui Cui; Hui Liu; Xiang Lin; Jiahe Zou; Yu Wang; Bo Zhou (Journal of Marine Science and Engineering, 2024)
Jack-up offshore platforms are widely used in many fields, and it is of great importance to quickly and accurately predict the dynamic response of platform pile leg structures in real time. The current analytical techniques are founded upon numerical modelling of the platform structure. Although these methods can be used to accurately analyze the dynamic response of the platform, they require a large quantity of computational resources and cannot meet the requirements of real-time prediction. A predictive model for the dynamic response of the pile leg of a jack-up platform based on the random forest algorithm is proposed. Firstly, a pile leg dynamic response database is established based on high-fidelity numerical model simulation calculations. The data are subjected to cleaning and dimensional reduction in order to facilitate the training of the random forest model. Cross-checking and Bayesian optimization algorithms are used for the selection of random forest parameters. The results show that the prediction model is capable of outputting response results for new environmental load inputs within a few milliseconds, and the prediction results remain highly accurate and perform well at extreme values.

Energy saving technology design and multiple performance evaluation for the extractive distillation process to recover benzene and isopropanol from wastewater by mixed entrainer - Qiming Wu; Zhen Wang; Bo Wang; Wenwu Xu; Jiuxu Ruan; Ruoyu Hu; Jianhui Zhong; Leilei Xin; Zhaoyou Zhu; Yinglong Wang; Peizhe Cui (Process Safety and Environmental Protection, 2024)

Wake characteristics of a cylinder attached with a perforated spoiler immersed in turbulent boundary layer - Jie Wang; Bo Zhou; Xiaohui Cui; Guiyong Zhang; Xikun Wang (Ocean Engineering, 2024)

Characteristics of biofilms on polylactic acid microplastics and their inhibitory effects on the growth of rice seedlings: A comparative study of petroleum-based microplastics - Yizhuo Chen; Bo Cui; Yuhang Dou; Huiyu Fan; Yanjun Fang; Lei Wang; Zhenghua Duan (Journal of Hazardous Materials, 2024)

Potentially toxic element source apportionment and risk assessment in agricultural soils around a large-scale Pb-Zn mine in Southwest China - Heng Wei; Xuekui Niu; Minmin Li; Canwen Cui; Zhonghua Wei; Wei Long; Man Tang; Hong Yu; Peng Zhang; Liping He; Bo Pan (Journal of Environmental Chemical Engineering, 2024)

Eco-friendly synthesis of magnetic zeolite A from red mud and coal gasification slag for the removal of Pb2+ and Cu2+ - Kai-bo Cui; Jing-wei Lyu; Hao-ze Liu; Jing-lei Yang; Zheng-qing Yan; Wei Yang; Xiao Liu; Jun Qiu (Journal of Environmental Chemical Engineering, 2024)

Source apportionment and specific-source-site risk of quinolone antibiotics for effluent-receiving urban rivers and groundwater in a city, China - Yu Zhao; Yuanmeng Song; Lulu Zhang; Bo Zhao; Mengqi Lu; Jiansheng Cui; Wenzhong Tang (Journal of Environmental Sciences, 2024)

A novel mathematical method to estimate rice phenological parameters across spatial scales for the ORYZA model - Qianan Yu; Linhua Ma; Yuanlai Cui; Luguang Liu; Bo Liu (European Journal of Agronomy, 2024)

Study on the applicability of FAI linear fitting model in the extraction of cyanobacterial blooms - Tao Su; Liangquan Xu; Xinbei Liu; Xingyuan Cui; Bo Lei; Junnan Di; Tian Xie (Environmental Monitoring and Assessment, 2024)

Developments in molecular docking technologies for application of polysaccharide-based materials: A review - Ruikang Lin; Jihui Zhang; Ruoxuan Xu; Chao Yuan; Li Guo; Pengfei Liu; Yishan Fang; Bo Cui (Critical Reviews in Food Science and Nutrition, 2024)

Induced production of defensive secondary metabolites from Aspergillus fumigatiaffinis by co-culture with Aspergillus alabamensis - Zhibo Hu; Haishan Cui; Qiang Wang; Cheng Li; Senhua Chen; Zhizeng Gao; Lan Liu; Bo Peng; Jing Li (Phytochemistry, 2024)

Coastal bridges with a box-girder superstructure under the action of solitary waves: Study on the optimization of bearings, dynamic characteristics and failure mechanism - Minglin Chen; Bo Huang; Cheng Cui; Zechen Xue; Zhiying Yang; Yong Xiao; Bing Zhu (Ocean Engineering, 2024)

Prediction of DEDI index for meteorological drought with the VMD-CBiLSTM hybrid model - Tao Su; Dan Liu; Xingyuan Cui; Xianshen Dou; Bo Lei; Xu Cheng; Mengning Yuan; Renjie Chen (Journal of Hydrology, 2024)

Ancestral sequence reconstruction of the prokaryotic three-domain laccases for efficiently degrading polyethylene - Bo Zeng; Yishan Fu; Jiacai Ye; Penghui Yang; Shixiu Cui; Wenxuan Qiu; Yangyang Li; Taoxu Wu; Haiyun Zhang; Yachan Wang; Guocheng Du; Song Liu (Journal of Hazardous Materials, 2024)

Occurrence, migration and health risks of fluorescent whitening agents and phthalates in bottled water - Ruiyao Guo; Xiaoge Liang; Mengfei Su; Bo Yao; Shuwen Yan; Yonghui Han; Jiansheng Cui (Journal of Hazardous Materials, 2024)

Simultaneous optimization of water and nitrogen management demonstrates effective and robust performance in nitrogen footprint reduction within the double-season rice system - Zenglin Peng; Bin Liao; Junzhe Luo; Yang Chen; Qianan Yu; Bo Liu; Yuanlai Cui; Fangping Liu; Liangsheng Shi (Journal of Cleaner Production, 2024)

The structural-mechanical damage behavior of rice bran layer under tensile processing for moderate milling - Zilong Xu; Liu Yang; Pingan Huang; Bo Cui; Can Shu; Yang Luo; Xuan Xiao; Shaoyun Song; Houchang Pei; Yonglin Zhang (Journal of Cereal Science, 2024)

Hapten synthesis, monoclonal antibody production and immunoassay development for analyzing spiropidion residues - Yaqi Jin; Zihui Jin; Di Sun; Yifan Liu; Bo Xu; Qiyang Zhao; Yue He; Lei Gong; Jing Li; Yaohai Zhang; Yongliang Cui (Food Chemistry, 2024)

Improving the stability, foliar utilization and biological activity of imidacloprid delivery systems: Size effect of nanoparticles - Qian Du; Fei Gao; Bo Cui; Tingyu Wang; Fangyuan Chen; Zhanghua Zeng; Changjiao Sun; Xinhua Zhou; Haixin Cui (Environmental Research, 2024)

Causes and dynamic change characteristics of the 2022 devastating floods in Pakistan - Huayong Chen; Jiang Xiong; Peng Cui; Xiaoqing Chen; Yonggang Ge; Congxi Fang; Bo Zhang; Tao Yang; Inamullah Khan (Natural Hazards, 2024)

Genomic profiling of biosynthetic potentials of medicinal secondary metabolites for ‘Aliisedimentitalea scapharcae’ KCTC 42119T, isolated from ark shell - Jin-Cheng Rong; Lin-Lin Cui; Na Li; Mao-Li Yi; Bo-Tao Huang; Qi Zhao (Marine Genomics, 2024)

Retrogradation inhibition of starches in staple foods with maltotetraose-forming amylase - Yunlong Cui; Xueting Li; Dengyue Sun; Li Guo; Bo Cui; Feixue Zou; Jinpeng Wang; Chunrui Sun (Food Chemistry, 2024)

Photothermal graphite phase carbon nitride membrane intercalated with polyoxovanadate for efficient solar steam generation - Qing Hu; Mohamed K. Albolkany; Congyan Liu; Tian Zhang; Songlin Cui; Fei Ye; Bo Liu (Desalination, 2024)

Active prelithiation strategies for advanced lithium storage systems: A perspective from electrochemical mechanism to structural design and application - Bo Jin; Keyu Zhang; Geng Gao; Qing Zhao; Xinyu Jiang; Dingfang Cui; Keqi Chen; Xiang Lin; Liuliu Liu; Rui Yan; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Parameterized atmospheric oxidation capacity during summer at an urban site in Taiyuan and implications for O3 pollution control - Bo Shao; Yang Cui; Qiusheng He; Lili Guo; Jianrong Gao; Jing Zhao; Xinming Wang (Atmospheric Pollution Research, 2024)

Maize tassel number and tasseling stage monitoring based on near-ground and UAV RGB images by improved YoloV8 - Xun Yu; Dameng Yin; Honggen Xu; Francisco Pinto Espinosa; Urs Schmidhalter; Chenwei Nie; Yi Bai; Sindhuja Sankaran; Bo Ming; Ningbo Cui; Wenbin Wu; Xiuliang Jin (Precision Agriculture, 2024)

Dissecting the Implications of Calumenin in Malignancy and Heterogeneity of the Microenvironment of Clear Cell Renal Cell Carcinoma Using Multi-Omics Data - Xin-Qiang Wu; Zhi Shang; Cui Xiong; Wen-Hao Xu; Bo Dai; Yu-Ling Chen; Yu-Yang Feng; Yue Wang; Jia-Qi Su; Jian-Yuan Zhao; Hai-Liang Zhang; Yan Shi; et al. (Phenomics, 2024)

Effect and Mechanism of Curdione Combined with Gemcitabine on Migration and Invasion of Bladder Cancer - Bao-Jin Chi; Zhong-Lei Duan; Al-Kamel Haithm Ali Mohammed Hasan; Xing-Zhong Yin; Bo-Yang Cui; Fang-Fang Wang (Biochemical Genetics, 2024)

Impact of the COVID-19 pandemic on daily travel: Findings from New South Wales, Australia - Bo Du; Cheng Zhang; Tianyang Qu; Qi Wang; Quan Spring Zhou; Tingru Cui; Pascal Perez; Thomas Astell-Burt (Travel Behaviour and Society, 2024)

Biomass power generation: A pathway to carbon neutrality - Wei Du; Zhanpeng Cui; Jinze Wang; Yiming Qin; Jianhuai Ye; Nan Lin; Yuanchen Chen; Wenyan Duan; Zhaofeng Chang; Hao Li; Peng Zhang; Bo Pan (Science of The Total Environment, 2024)

The first detection of mpox virus DNA from wastewater in China - Jin Xu; Chao Liu; Qun Zhang; Haining Zhu; Feng Cui; Zhiqiang Zhao; Mingfang Song; Bo Zhou; Yunxiao Zhang; Peilong Hu; Lei Li; Qin Wang; et al. (Science of The Total Environment, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

Inorganic flocculant-based soybean urease extraction and its effect on biomineralization - Han-Jiang Lai; Hui Liu; Ming-Juan Cui; Jun-Jie Zheng; Zhi-Bo Chen; Zhi-Chao Zhang (Journal of Cleaner Production, 2024)

Impact of rice friction milling on the bran layer and on kernel structure - Zilong Xu; Liu Yang; Xuan Xiao; Bo Cui; Jin Zhou; Qianmai Peng; Shaoyun Song; Houchang Pei; Yonglin Zhang (Journal of Cereal Science, 2024)

Preparation of limonin monoclonal antibody and establishment of a sensitive icELISA for analyzing limonin in citrus and herbal samples - Di Sun; Yifan Liu; Zihui Jin; Bo Xu; Yaqi Jin; Qiyang Zhao; Yue He; Jing Li; Yaohai Zhang; Yongliang Cui (Food Chemistry, 2024)

Effect of vegetable oils on the thermal gel properties of PSE-like chicken breast meat protein isolate-based emulsion gels - Ke Li; Lin-Meng Wang; Bing-Bing Cui; Bo Chen; Dian-Bo Zhao; Yan-Hong Bai (Food Chemistry, 2024)

Novel a-linolenic acid emulsions stabilized by octenyl succinylated starch -soy protein-epigallocatechin-3-gallate complexes: Characterization and antioxidant analysis - Tenglong Geng; Lidan Pan; Xiaorui Liu; Die Dong; Bo Cui; Li Guo; Chao Yuan; Meng Zhao; Haibo Zhao (Food Chemistry, 2024)

Physicochemical properties and cell viability comparison of two Lactiplantibacillus plantarum DNZ-4 microcapsules and its application in beverages - Cui-Cui Sun; Ming Yi; Yu Miao; Yan Song; Guo-Fang Zhang; Peng Du; Ai-Li Li; Li-Bo Liu; Chun Li (Food Hydrocolloids, 2024)

Promoting effect and microscopic mechanism of train-induced vibration on loess disintegration - Shan Li; Jiading Wang; Kai Han; Li Wang; Dengfei Zhang; Haoyu Dong; Bo Cui (Engineering Geology, 2024)

Study on strain localization of frozen sand based on uniaxial compression test and discrete element simulation - Dongyong Wang; Bo Shao; Jilin Qi; Wenyu Cui; Shengbin Jiang; Liyun Peng (Cold Regions Science and Technology, 2024)

Research on Landsat 8 land surface temperature retrieval and spatial–temporal migration capabilities based on random forest model - Wenhao Zhang; Zhiyang Jia; Bo Li; Qiyue Liu; Xia Zhu; Cui Jia; Xingfa Gu; Tao Yu (Advances in Space Research, 2024)

Role of low-proportion, hydrophobic dissolved organic matter components in inhibiting methylmercury uptake by phytoplankton - Zhike Li; Zhengyu Wu; Shao Bo; Jie Chi; Xiaoyu Cui; Wei He; Xiaomei Cui; Yiwen Liu; Yingxin Zhao; Yindong Tong (Chemosphere, 2024)

Application research of intelligent system based on BIM and sensors monitoring technology in construction management - Wei Cui; Ying Chen; Bo Xu (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Carbon nanotube incorporated quaternized lignin-based loose nanofiltration membrane toward dye/salt separation - Zhenyu He; Na Zhang; Li Zhao; Zhenghua Li; Wanling Cui; Yuangang Zhu; Yi Wang; Huining Deng; Chengrun Si; Wen Bo; Jie Zhou; Shicai Xu; et al. (Journal of Environmental Chemical Engineering, 2024)

Encapsulation of apigenin into β-cyclodextrin metal-organic frameworks with high embedment efficiency and stability - Yaqi Liu; Chao Yuan; Bo Cui; Meng Zhao; Bin Yu; Li Guo; Pengfei Liu; Yishan Fang (Food Chemistry, 2024)

Gold-copper-doped lanthanide luminescent metal-organic backbone induced self-enhanced molecularly imprinted ECL sensors for ultra-sensitive detection of chlorpyrifos - Yishan Fang; Yanping Li; Xufeng Zang; Yingxue Chen; Xinran Wang; Na Wang; Xiangying Meng; Bo Cui (Food Chemistry, 2024)

Anti-counterfeiting applications of antimony-doped zero-dimensional indium halide with temperature-responsive broad emission - Yue Wu; Xin Zhang; Liu-Di Xin; Cui-Mi Shi; Bo Zhang; Liang-Jin Xu (Chemical Engineering Journal, 2024)

Effects of different oil additives on water resistance of corn starch straws - Jinyu Zhang; Xueting Li; Kun Wang; Yu Zhu; Li Guo; Bo Cui; Lu Lu (Carbohydrate Polymers, 2024)

Application of multiple strategies to enhance oleanolic acid biosynthesis by engineered Saccharomyces cerevisiae - Xu Cheng; Yaru Pang; Yali Ban; Shuai Cui; Tao Shu; Bo Lv; Chun Li (Bioresource Technology, 2024)

Mitochondria-Related Gene MAOB is a Key Biomarker of Osteoarthritis and Inhibition of Its Expression Reduces LPS-induced Chondrocyte Damage - Shiqi Bi; Bo Han; Hongjuan Fan; Yongming Liu; Xuewen Cui (Biochemical Genetics, 2024)

The key factors of solid nanodispersion for promoting the bioactivity of abamectin - Xiquan Ding; Fei Gao; Bo Cui; Qian Du; Zhanghua Zeng; Xiang Zhao; Changjiao Sun; Yan Wang; Haixin Cui (Pesticide Biochemistry and Physiology, 2024)

Microbial community structure in a constructed wetland based on a recirculating aquaculture system: Exploring spatio-temporal variations and assembly mechanisms - Wenjie Tian; Qiufen Li; Zijun Luo; Chao Wu; Bo Sun; Danting Zhao; Saisai Chi; Zhengguo Cui; Ailing Xu; Zhiwen Song (Marine Environmental Research, 2024)

Photoelectrochemical sensor for the detection of Escherichia coli O157:H7 based on TPA-NO2 and dual-functional polythiophene films - Xiaoqing Wang; Huiyi Chen; Jihui Zhang; Hong Zhou; Xiangying Meng; Na Wang; Yishan Fang; Bo Cui (Food Chemistry, 2024)

Overall quality changes and deterioration mechanism of fragrant rapeseed oils during 6-Month storage - Chen Chen; Ping-Ping Ye; Feng-Jie Cui; Ming Tan; Hai-Bo Zhang; Tong-Lin Zhou; Jian-Cheng Shi; Xue-Quan Shu; Zhi-Wei Chen (Food Chemistry, 2024)

Recombinant microgels utilized to formulate green Pickering emulsions - Han Liu; Li Guo; Fuying Wang; Hongxun Tao; Bin Yu; Haibo Zhao; Jianpeng Li; Minwei Xu; Haiteng Tao; Bo Cui; Yuxiao Wang (Food Hydrocolloids, 2024)

Development of novel variable building skin with solar concentrating technology for obtaining energy benefits and optimizing indoor daylighting - Bo Wang; Xinshuo Zhang; Mengli Zhang; Yong Cui; Ying He (Energy and Buildings, 2024)

In situ confined growth of Cu2-xSe nanoparticles in highly defective nitrogen-doped carbon for high-rate sodium-ion battery anodes - Hui Peng; Wenxing Miao; Shuzhen Cui; Zhiyuan Liu; Xin Wang; Bo Tao; Wenbo Hou; Zhe Zhang; Guofu Ma (Chemical Engineering Journal, 2024)

Effects of different water and nitrogen treatments on greenhouse tomato yield, water use efficiency, and physiological responses - Jiajun Cui; Wenhe Liu; Bo Li; Mingze Yao; Lizhen Mao; Mingyu Zhao; Hongfei Niu; Zhanyang Xu; Feng Zhang; Tieliang Wang; Jingkuan Wang (Irrigation Science, 2024)

Author Correction: Porphyromonas gingivalis promotes the progression of oral squamous cell carcinoma by stimulating the release of neutrophil extracellular traps in the tumor immune microenvironment - Zhi-chen Guo; Si-li Jing; Xin-yu Jia; Sadam Ahmed Elayah; Lin-yang Xie; Hao Cui; Jun-bo Tu; Si-jia Na (Inflammation Research, 2024)

Porphyromonas gingivalis promotes the progression of oral squamous cell carcinoma by stimulating the release of neutrophil extracellular traps in the tumor immune microenvironment - Zhi-chen Guo; Si-li Jing; Xin-yu Jia; Sadam Ahmed Elayah; Lin-yang Xie; Hao Cui; Jun-bo Tu; Si-jia Na (Inflammation Research, 2024)

Using the paddy eco-ditch wetland system to reduce nitrogen non-point source pollution discharge from paddies: A consecutive six-year study in the Yunnan Plateau, China - Huanhao Han; Xinru Wang; Haili Zheng; Bo Liu; Rong Gao; Yuanlai Cui; Xiaogang Liu; Shixiang Gu; Bochao Zhang; Ming Yang (Agriculture, Ecosystems & Environment, 2024)

A new diterpenoid from the leaves and twigs of Croton lachnocarpus Benth - Xiao-Qing Zhan; Qian Wu; Mei-Jie Wang; Li Liu; Wen-Bo Cui; Feng-Li An; Feng-Ming Qi; Dong-Qing Fei; Zhan-Xin Zhang (Natural Product Research, 2024)

Synthesis, antifungal activity, 3D-QSAR, and molecular docking study of novel anethole-derived hydroxamate compounds - Yucheng Cui; Rong Li; Wengui Duan; Bo Cen; Guishan Lin; Kaiyue Wu (Phytochemistry Letters, 2024)

Activation of peroxymonosulfate by a CuCo-NC diatomic catalyst on N-doped graphene for selective generation of 1O2 towards efficient organic pollutant treatment - Yuxuan Sun; Jie Yu; Xuan Guo; Yuhang Cui; Zijian Zhang; Xiaoyuan Zhang; Shiming Hu; Chenghao Yang; Bo Chi; Kosuke Noborio; Song Han (Journal of Environmental Chemical Engineering, 2024)

β-Cyclodextrin based Pickering emulsions for α-tocopherol delivery: Antioxidation stability and bioaccessibility - Caiyun Cheng; Chao Yuan; Bo Cui; Jianpeng Li; Guimei Liu (Food Chemistry, 2024)

Effect of mixture microstructure/compatibility on the properties of type-A gelatin-dextran edible films - Ling Wu; Bo Cui; Die Dong; Zhengzong Wu; Jianpeng Li; Lu Lu; Na Wang; Katsuyoshi Nishinari; Meng Zhao (Carbohydrate Polymers, 2024)

Cryogenian and Ediacaran integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Lang Sun; Malik Muhammad Saud Sajid Khan; Chuan Yang; Zhixin Sun; Bing Pan; Shehryar Ahmed; Lanyun Miao; Weichen Sun; Chunlin Hu; Xiaojuan Sun; Cui Luo; Bo Chen; et al. (Science China Earth Sciences, 2024)

Investigating the spatio–temporal characteristics of lower atmospheric ducts across the China seas by performing a long–term simulation using the WRF model - Qi Liu; Xiaofeng Zhao; Jing Zou; Tong Hu; Zhijin Qiu; Bo Wang; Zhiqian Li; Chaoran Cui; Rui Cao (Frontiers in Marine Science, 2024)
In this work, a diagnostic scheme for lower atmospheric ducts was established based on the Weather Research and Forecasting (WRF) model. More specifically, a 10-year simulation test was conducted for the China seas to investigate the spatio-temporal characteristics of the lower atmospheric ducts phenomenon. Compared with the sounding data, the long-term simulations showed a high temporal correlation and the root mean square error of the modified atmospheric refractivity remained between 4 M and 7 M. Based on the simulations, significant regional differences in the occurrence probability of lower atmospheric ducts were detected from south to north. Among them, the surface ducts near the sea surface exhibited the highest occurrence probability, with higher probabilities being recorded in autumn and winter, and the probability gradually increased with the decreasing latitude. The spatio-temporal characteristics of duct height, thickness, and strength were generally consistent. In the seas at mid-latitudes, strong ducts mostly occurred in the spring and autumn, with the single-layer ducts being predominant and the first layer duct showing stronger characteristics than the second layer. In the lower latitude regions, the situation was exactly the opposite. The first duct layer, which existed throughout the year, exhibited weaker characteristics with less pronounced seasonal variations. On the other hand, the second duct layer demonstrated stronger features.

How do earthworms affect the pathway of sludge bio-stabilization via vermicomposting? - Xuyang Lei; Guangyu Cui; Hongxin Sun; Suxia Hou; Hongying Deng; Bo Li; Zhengzheng Yang; Qiushi Xu; Xueyu Huo; Jiaxuan Cai (Science of The Total Environment, 2024)

Scouring development and self-burial of a subsea pipeline attached with porous/flexible spoilers - Bo Zhou; Jie Wang; Xiaohui Cui; Chaodong Hu; Hui Liu; Xikun Wang (Ocean Engineering, 2024)

The role of fungi in the formation and instability of halophilic aerobic granular sludge in a continuous flow reactor - Hui-Kai Liang; You-Wei Cui; Jin-Lei Yan; Hui-Juan Yan; Zhen-Ying Li; Yu-Bo Cui (Journal of Water Process Engineering, 2024)

A ground-independent method for obtaining complete time series of in situ evapotranspiration observations - Wangyipu Li; Zhaoyuan Yao; Xiaoduo Pan; Zhihao Wei; Bo Jiang; Jing Wang; Ming Xu; Yaokui Cui (Journal of Hydrology, 2024)

Differential response of Hg-methylating and MeHg-demethylating microbiomes to dissolved organic matter components in eutrophic lake water - Zhengyu Wu; Zhike Li; Bo Shao; Ji Chen; Xiaomei Cui; Xiaoyu Cui; Xianhua Liu; Ying Xin Zhao; Qiang Pu; Jiang Liu; Wei He; Yiwen Liu; et al. (Journal of Hazardous Materials, 2024)

Evolution of the sedimentary environment on the continental shelf of southeastern Hainan Island under the influences of sea level and climate during the Holocene - Fangjian Xu; Yongwei Zhang; Bangqi Hu; Ruyong Cui; Lin Zhang; Wenhe Huang; Bo Chen (Journal of Asian Earth Sciences, 2024)

Bamboo classification based on GEDI, time-series Sentinel-2 images and whale-optimized, dual-channel DenseNet: A case study in Zhejiang province, China - Bo Wang; Hong Zhao; Xiaoyi Wang; Guanting Lyu; Kuangmin Chen; Jinfeng Xu; Guishan Cui; Liheng Zhong; Le Yu; Huabing Huang; Qinghong Sheng (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Effects of starch–fatty acid complexes with different fatty acid chain lengths and degrees of saturation on the rheological and 3D printing properties of corn starch - Yue Cheng; Wei Gao; Xuemin Kang; Jianfei Wang; Bin Yu; Li Guo; Meng Zhao; Chao Yuan; Bo Cui (Food Chemistry, 2024)

Highly-branched cyclic dextrin for improvement in mechanical properties and freeze-thaw stability of κ-carrageenan gels - Wentao Ma; Chao Yuan; Bo Cui; Tian Gao; Li Guo; Bin Yu; Meng Zhao; Feixue Zou (Food Hydrocolloids, 2024)

The structural and functional properties of a novel enzyme-modified starch as an alternative to hydroxypropyl starch ether - Ruobing Li; Haiteng Tao; Congping Tan; Fang Yuan; Li Guo; Bo Cui; Yu Zhu; Feixue Zou; Pengfei Liu; Lu Lu (Food Hydrocolloids, 2024)

Enhancing safety through the biodegradable pesticide microcapsules produced via melt emulsification and interfacial polymerization - Long Chen; Weiqun Zhang; Huan Du; Xiquan Ding; Liang Li; Hongyan Chen; Fei Gao; Bo Cui; Jinming Gao; Haixin Cui; Yishan Yao; Zhanghua Zeng (Chemical Engineering Journal, 2024)

ZIFs material-derived bimetallic oxide heterojunctions activate perodisulfate to degrade chlortetracycline rapidly: The synergistic effects of oxygen vacancies and rapid electron transfer - Jiahao Cui; Xiaolong Gao; Bo He; Yong Yao; Yifan Zhao; Tiecheng Wang; Xianqiang Yin (Chemical Engineering Journal, 2024)

Self-growing micro/nano hexagonal cyclodextrins based on dual enzyme synergism and low-temperature induction - Ruikang Lin; Xufeng Zang; Chao Yuan; Bing Yu; Pengfei Liu; Yishan Fang; Bo Cui (Chemical Engineering Journal, 2024)

Effect of different screw speeds on the structure and properties of starch straws - Kun Wang; Congping Tan; Haiteng Tao; Fang Yuan; Li Guo; Bo Cui (Carbohydrate Polymers, 2024)

Quantifying the spatial inhomogeneity of ice concentration in mixed-phase stratiform cloud using airborne observation - Yuting Deng; Jing Yang; Yan Yin; Shiqi Cui; Bo Zhang; Xinghua Bao; Baojun Chen; Junxia Li; Wei Gao; Xiaoqin Jing (Atmospheric Research, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Experimental and numerical exploration of a new application of coal slag to treat loose sand foundation - Kaiwen Liu; Ruizhe Qiu; Jie Gou; Bo Ning; Chunyi Cui; Yang Chen; Tengfei Wang (Journal of Cleaner Production, 2024)

Petroleum-like fuels with substantially enriched branched iso-paraffins and benzenes via boehmite-assisted pyrolysis of oil shale - Guojing Xu; Zhaoyang Ren; Zhenpeng Wang; Lijie Cui; Jian-Zheng Su; Xiang-Long Meng; Penglei Chen; Peng Li; Nannan Wang; Xiang Hao; Bo Guan (Fuel, 2024)

Synergistic effect of enzymatic pre-treatment and amylose–lipid complex construction on the physicochemical properties of maize starch - Mengmeng Cui; Tongtong Mi; Zhengzong Wu; Wei Gao; Xuemin Kang; Bo Cui; Pengfei Liu (Food Chemistry, 2024)

Characterizations of corn starch edible films reinforced with whey protein isolate fibrils - Furun Zheng; Qianwen Yang; Chao Yuan; Li Guo; Zhao Li; Jiantao Zhang; Katsuyoshi Nishinari; Meng Zhao; Bo Cui (Food Hydrocolloids, 2024)

Two-phase modelling of erosion and deposition process during overtopping failure of landslide dams using GPU-accelerated ED-SPH - Mingjun Zhou; Zhenming Shi; Chong Peng; Ming Peng; Kahlil Fredrick E. Cui; Bo Li; Limin Zhang; Gordon G.D. Zhou (Computers and Geotechnics, 2024)

Antioxidative bioactive glass reinforced injectable hydrogel with reactive oxygen species scavenging capacity for diabetic wounds treatment - Hao Chang; Pengfei Tian; Liuzhi Hao; Chengwei Hu; Bo Liu; Fengzhen Meng; Xin Yi; Xiaohua Pan; Xiaohua Hu; Huan Wang; Xinyun Zhai; Xu Cui; et al. (Chemical Engineering Journal, 2024)

Piperlongumine inhibits esophageal squamous cell carcinoma in vitro and in vivo by triggering NRF2/ROS/TXNIP/NLRP3-dependent pyroptosis - Yue Cui; Xiao-bo Chen; Ying Liu; Qian Wang; Jie Tang; Man-jun Chen (Chemico-Biological Interactions, 2024)

Quantifying metallic components in aerosol filter samples using micro-synchrotron radiation X-ray fluorescence: With quartz filter as an example - Yidan Zhang; Yifan Xu; Bo Peng; Wu Chen; Xiaoyu Cui; Tianle Zhang; Xi Chen; Yuan Yao; Mingjin Wang; Junyi Liu; Mei Zheng; Tong Zhu (Atmospheric Environment, 2024)

Emissions of nitrated and oxygenated polycyclic aromatic hydrocarbons bound to coarse particles from solid fuel combustion - Yaoxing Feng; Jinze Wang; Jie Sun; Zhanpeng Cui; Qi Chen; Kang Mao; Yali Lei; Peng Zhang; Wei Du; Jianwu Shi; Bo Pan (Chemosphere, 2024)

Lipid characteristics of lung tissue in silicosis rat model were studied based on lipid metabolomics - Hailan He; Rong Qi; Jie Cui; Mingming Liu; Bo Guan; Yufan Zhou; Yingshu Zhang; Xiaohui Hao; Hongli Wang; Heliang Liu (Toxicology Letters, 2024)

Whole-body aging mediates the association between exposure to volatile organic compounds and osteoarthritis among U.S. middle-to-old-aged adults - Hao-long Zhou; Dong-sheng Di; Zhang-bo Cui; Ting-ting Zhou; Ting-ting Yuan; Qian Liu; Jian-li Zhang; Xiao Luo; Dan-yang Ling; Qi Wang (Science of The Total Environment, 2024)

Restoring degraded coral colony using two coral transplantation techniques: A case study from Dapeng Bay, Shenzhen, China - Bo Yang; Huina Zheng; Zhouping Cui; Hao Sun; Baolin Liao; Ziqiang Xie; Bogui Chen; Jin Zhou; Baohua Xiao (Regional Studies in Marine Science, 2024)

Insight into the enhancement effect of humic acid on microbial degradation of triclosan in anaerobic sediments - Juan Chen; Bo Zhang; Chao Wang; Peifang Wang; Ge Cui; Han Gao; Bingbing Feng; Jingjing Zhang (Journal of Hazardous Materials, 2024)

A preliminary study on the quality evaluation of coking coal from its structure thermal transformation: Applications of fluidity and swelling indices - Beibei Cui; Bo Wu; Meijun Wang; Xin Jin; Yanfeng Shen; Liping Chang (Fuel, 2024)

Effect of sesbania gum on the rheological, textural, and microstructural characteristics of CaSO4-induced soy protein isolate gels - Ran Yang; Bin Yu; Laixue Ni; Yungang Cao; Qingqing Chai; Haiteng Tao; Zheng Zhang; Guimei Liu; Yunhui Cheng; Haibo Zhao; Bo Cui; Zhengzong Wu (Food Hydrocolloids, 2024)

Authigenic clay mineral constraints on spatiotemporal evolution of restricted, evaporitic conditions during deposition of the Ediacaran Doushantuo Formation - Shujun Han; Stefan C Löhr; April N Abbott; Andre Baldermann; Graham A. Shields; Huan Cui; Alan J Kaufman; Bo Chen; Bingsong Yu (Earth and Planetary Science Letters, 2024)

Thermo-responsive liposome nano-vesicles for co-delivery of emamectin benzoate and nitenpyram with synergistic pest control - Qian Du; Xi-Quan Ding; Fei Gao; Bo Cui; Ting-Yu Wang; Fang-Yuan Chen; Long Chen; Hong-Yan Chen; Hai-Xin Cui; Yan Wang; Zhang-Hua Zeng (Chemical Engineering Journal, 2024)

Spatial patterns and predictors of seed plants' extinction risks in Asian countries - Lijing Zhou; Keping Ma; Li Zhu; Guoke Chen; Bo Liu; Hongfeng Wang; Cui Xiao; Yuying Zhao (Biological Conservation, 2024)

Hydrodynamic Interactions between Ships in a Fleet - Zhengyuan Liu; Changming Dai; Xiaohui Cui; Yu Wang; Hui Liu; Bo Zhou (Journal of Marine Science and Engineering, 2023)
There has always been a concern about the hydrodynamic interaction between ships in a flow field. In this study, the RANS method is utilized, and the hydrodynamic interference between two KRISO Container Ships (KCS) operating in still water with identical parameters and sailing at the same speed is investigated. Overlapping grids are used to simulate ship motion, and the VOF method is used to simulate the free surface. A KCS ship model of 1:1 size without propeller is used in the study. In order to study the change principle of the Kelvin flow field created by a single ship, the resistance coefficient and the flow field surrounding the ship are first calculated for the monohull case. Then the influence of interference between two ships is examined at various speeds and intervals and compared with the monohull case. It is discovered that the resistance coefficient of the following ship is reduced in a certain speed interval under the influence of the leading ship, where the maximum reduction can be up to 24.3%. The reason for this phenomenon may be that the wave around the following ship is superimposed on the transverse wave behind the leading ship. When the height of the wave is suppressed, the following ship’s resistance is reduced.

The protective immunity induced by Trichinella spiralis galectin against larval challenge and the potential of galactomannan as a novel adjuvant - Ru Zhang; Xin Zhuo Zhang; Xin Guo; Lu Lu Han; Bo Ning Wang; Xi Zhang; Ruo Dan Liu; Jing Cui; Zhong Quan Wang (Research in Veterinary Science, 2023)

Synergistic modulation of chitosan on the mechanical and disintegration properties of pre-gelatinized waxy corn starch orally disintegrating film - Yuhang Li; Wentao Ma; Bo Cui; Chao Yuan; Meng Zhao (Food Bioscience, 2023)

Insight into the formation mechanism of soy protein isolate films improved by dialdehyde starch with different degrees of aldehyde substitution - Yuan Zhao; Ran Tian; Mengqi Cui; Yan Zhang; Lianzhou Jiang; Bo Tian; Xiaonan Sui (Food Hydrocolloids, 2023)

Effects of polyols with different hydroxyl numbers on the structure and properties of starch straws - Chenyu Ma; Haiteng Tao; Congping Tan; Shijun Gao; Zehua Wu; Li Guo; Bo Cui; Fang Yuan; Feixue Zou; Pengfei Liu; Lu Lu (Carbohydrate Polymers, 2023)

Association Between Wnt Target Genes and Cortical Volumes in Alzheimer’s Disease - Liling Dong; Bo Hou; Caiyan Liu; Chenhui Mao; Xinying Huang; Li Shang; Shanshan Chu; Bin Peng; Liying Cui; Feng Feng; Jing Gao (Journal of Molecular Neuroscience, 2023)
The disproportionate cortical atrophy is an established biomarker for the pathophysiological process of Alzheimer’s disease (AD). However, the genetic basis underlying the cortical atrophy remains poorly defined. Herein, we aim to illustrate the effect of the Wnt target genes on the cortical volumes of AD patients. 82 sporadic AD patients were recruited. All the subjects had history survey, blood biochemical examination, cognitive assessment, MRI morphometry and whole exome sequencing. This report focused on 84 common variants (minor allele frequency > 0.01) of 32 Wnt target genes, including the APC , DAAM1 , DACT1 , DISC1 , LATS2 , TLR2 , WDR61 , and the AXIN , DVL , FZD , LRP , TCF/LEF , WNT family genes. The Wnt target genes showed asymmetric effects on the cortical volumes of AD patients. The right temporal/parietal/occipital cortices were more affected than left temporal/parietal/occipital cortices. Nevertheless, the reverse applied to the frontal cortex. The DACT1 affected the cortical thickness most, followed by the TCF3 and APC . The DACT1 rs698025-GG genotype displayed greater right temporal pole and left medial orbito-frontal gyrus than rs698025-GA genotype (2.4 ± 0.4 vs. 2.0 ± 0.6, P = 0.005; 5.2 ± 0.6 vs. 5.0 ± 0.6, P = 0.001). The brain region most influenced by the Wnt target genes was the right calcarine cortex. In conclusion, the common variants of the Wnt target genes exert asymmetric effects on the cortical volumes of AD patients. The Wnt signaling pathway may play a role in the cortical atrophy of AD patients.

Dynamic characteristics and erosion effect of a landslide-induced debris flow which occurred in Pingwu, southwest China - Bo Liu; Kun He; Xiewen Hu; Yufang Zhang; Kun Yuan; Jian Cui; Chuanjie Xi; Ruichen Zhou (Bulletin of Engineering Geology and the Environment, 2023)

Federated learning with SARIMA-based clustering for carbon emission prediction - Tianxu Cui; Ying Shi; Bo Lv; Rijia Ding; Xianqiang Li (Journal of Cleaner Production, 2023)

Multi-dimensional research on brown rice fracture characteristics and mechanism under quasi-static compression - Xuan Xiao; Liu Yang; Zihao Wang; Yang Luo; Bo Cui; Shaoyun Song; Yonglin Zhang; Houchang Pei (Journal of Cereal Science, 2023)

Influence of hot-air drying on the starch structure and physicochemical properties of two corn cultivars cultivated in East China - Xiaofeng Wang; Yunjie Wang; Haibo Zhao; Haiteng Tao; Wei Gao; Zhengzong Wu; Kuidong Zhang; Bin Yu; Bo Cui (Journal of Cereal Science, 2023)

Pore connectivity and microfracture characteristics of Longmaxi shale in the Fuling gas field: Insights from mercury intrusion capillary pressure analysis - Xiang Zhao; Mengdi Sun; Chima Finnian Ukaomah; Mehdi Ostadhassan; Ziang Cui; Bo Liu; Zhejun Pan (Gas Science and Engineering, 2023)

T4PPVB-COP composite-driven innovative electrochemiluminescence aptasensor for ultra-sensitive detection of chlorpyrifos - Yanping Li; Qiong Hu; Jihui Zhang; Hong Zhou; Na Wang; Yishan Fang; Bo Cui (Food Chemistry, 2023)

Efficient production of biosurfactant surfactin by a newly isolated Bacillus subtilis (sp.) 50499 strain from oil-contaminated soil - Yulu Du; Yue Wang; Tianyou Cui; Lianpeng Ge; Fan Yu; Mengqian Zhao; Qihang Xu; Mingjie Jin; Bo Chen; Xuwei Long (Food and Bioproducts Processing, 2023)

Impacts of autochthonous dissolved organic matter on the accumulation of methylmercury by phytoplankton and zooplankton in a eutrophic coastal ecosystem - Bo Shao; Zhike Li; Zhengyu Wu; Ning Yang; Xiaoyu Cui; Huiming Lin; Yiwen Liu; Wei He; Yingxin Zhao; Xuejun Wang; Yindong Tong (Environmental Pollution, 2023)

Functional separator with 1 T/2H-MoSe2 nanosheets decorated nitrogen and sulfur co-doped mesoporous hollow carbon spheres for high-performance Li-S batteries - Qidong Sheng; Hui Liu; Yaning Liu; Bo Jin; Mengyang Cui; Yiyang Li; Nan Gao; Xingyou Lang; Qing Jiang (Chemical Engineering Journal, 2023)

Starch/polyvinyl alcohol with ionic liquid/graphene oxide enabled highly tough, conductive and freezing-resistance hydrogels for multimodal wearable sensors - Xueting Li; Shiqing Zhang; Xiaonan Li; Lu Lu; Bo Cui; Chao Yuan; Li Guo; Bin Yu; Qingqing Chai (Carbohydrate Polymers, 2023)

Maltogenic amylase: Its structure, molecular modification, and effects on starch and starch-based products - Pengfei Liu; Li Ma; Wenmin Duan; Wei Gao; Yishan Fang; Li Guo; Chao Yuan; Zhengzong Wu; Bo Cui (Carbohydrate Polymers, 2023)

Single particle tracking reveals SARS-CoV-2 regulating and utilizing dynamic filopodia for viral invasion - Yue Zhang; Xiaowei Zhang; Zhongyi Li; Weisong Zhao; Hui Yang; Shuangshuang Zhao; Daijiao Tang; Qian Zhang; Zonghong Li; Huisheng Liu; Haoyu Li; Bo Li; et al. (Science Bulletin, 2023)

Bioactive ellagitannins and phenylpropanoid glycosides from the seed of Torreya grandis - Xue-Hui Wang; Xiao-Jing Shao; Yi-Ran Jiang; Tian-Tian Bei; Wen-Hui Xu; Bo-Wen Ren; Hyun-Sun Lee; Long Cui (Phytochemistry Letters, 2023)

A method for improving the hydrostatic pressure testing of the compressive strength of solid buoyancy materials used at full ocean depth - Jingze Wang; Bo Gao; Weicheng Cui (Ocean Engineering, 2023)

Vehicle-bridge dynamic response analysis under copula-coupled wind and wave actions - Chen Guo; Bo Zhang; Hong Guo; Shengai Cui; Bing Zhu (Ocean Engineering, 2023)

De-carbonization and carbon utilization for subsurface energy transition: Introduction - Guodong Cui; Zhonghe Pang; Guiling Wang; Xiangzeng Wang; Bo Ren (Gondwana Research, 2023)

High-temperature hydrothermal resource exploration and development: Comparison with oil and gas resource - Guodong Cui; Zheng Niu; Difei Zhao; Yanlong Kong; Bo Feng (Gondwana Research, 2023)

Pollution characteristics, ecological and health risks of herbicides in a drinking water source and its inflowing rivers in North China - Yilin Li; Ruiyao Guo; Xiaoge Liang; Bo Yao; Shuwen Yan; Yanan Guo; Yonghui Han; Jiansheng Cui (Environmental Pollution, 2023)

Construction of submicro rhombic RDX lamellae and the critical size effect on desensitivity originated from slipping energy dissipation - Yuxin Cui; Xun Liu; Liangyou Zhao; Yuanyuan Deng; Yuting Li; Xiaohui Duan; Bo Wu; Chonghua Pei (Chemical Engineering Journal, 2023)

Population genomics of Lacticaseibacillus paracasei: pan-genome, integrated prophage, antibiotic resistance, and carbohydrate utilization - Zhangming Pei; Xiaoshu Li; Shumao Cui; Bo Yang; Wenwei Lu; Jianxin Zhao; Bingyong Mao; Wei Chen (World Journal of Microbiology and Biotechnology, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Deciphering the turnover of bacterial groups in winter agricultural soils - Xinlin Zhang; Yu Li; Kunxue Cui; Yiwen Sun; Xu Zhang; Guangren Zheng; Meiyang Zhao; Bo Wang; Hongyu Yang (Science of The Total Environment, 2023)

Chronic intermittent hypobaric hypoxia improves iron metabolism disorders via the IL-6/JAK2/STAT3 and Epo/STAT5/ERFE signaling pathways in metabolic syndrome rats - Fang Cui; Jie Sun; Haichao Mi; Bo Li; Longmei Tang; Ruotong Wang; Yutao Du; Bingyan Guo; Yongjun Li; Min Shi (Journal of Trace Elements in Medicine and Biology, 2023)

“Mini-community” simulation revealed the differences of endophytic fungal communities between the above- and below-ground tissues of Ephedra sinica Stapf - Xi Liu; Jin-Long Cui; Zhong-Ya Zhou; Zong-Bao Zhang; Xuan-Ge Cui; Bo Han; Jun-Hong Wang; Meng-Liang Wang; Yi-Min Li (Fungal Biology, 2023)

Water-in-oil oleogel with biphasic stabilization for fabrication of low-fat salad dressing - Fuying Wang; Li Guo; Han Liu; Hongxun Tao; Bin Yu; Haibo Zhao; Jianpeng Li; Haiteng Tao; Bo Cui; Yuxiao Wang (Food Hydrocolloids, 2023)

Two strategies for rapid and sensitive detection of procalcitonin using carbon dots-encapsulated nanocapsule and magnetic carbon dots as coupled labels - Bo Liu; Siyu Lu; Kun Yang; Xuechen Dou; Xiangling Feng; Haoran Cui; Fan Li; Feng Tian (Chemical Engineering Journal, 2023)

Generation, activation, and recycling of ammonium persulfate for the remediation of organic-contaminated soil: System construction, process, and mechanisms - Xian Zhu; Wei Sun; Chen Li; Zhenzhen Wang; Xiangfen Cui; Bo Li; Senlin Tian (Chemical Engineering Journal, 2023)

Profiling of single-vesicle surface proteins via droplet digital immuno-PCR for multi-subpopulation extracellular vesicles counting towards cancer diagnostics - Chunchen Liu; Huixian Lin; Jingyun Guo; Chao Yang; Jing Chen; Weilun Pan; Binbin Cui; Junjie Feng; Ye Zhang; Bo Li; Shuhuai Yao; Lei Zheng (Chemical Engineering Journal, 2023)

Dual cross-linked starch hydrogel for eugenol encapsulation and the formation of hydrogen bonds on textural hydrogel - Ruikang Lin; Ruoxuan Xu; Huiyi Chen; Bo Liu; Chao Yuan; Li Guo; Bo Cui; Yishan Fang (Carbohydrate Polymers, 2023)

Declines in nutrient losses from China’s rice paddies jointly driven by fertilizer application and extreme rainfall - Jin Fu; Chengjie Wang; Wulahati Adalibieke; Yiwei Jian; Yan Bo; Xiaoqing Cui; Feng Zhou (Agriculture, Ecosystems & Environment, 2023)

Ultrasonication effects on physicochemical properties of biopolymer-based films: A comprehensive review - Tongtong Mi; Xiaolei Zhang; Pengfei Liu; Wei Gao; Jianpeng Li; Nuo Xu; Chao Yuan; Bo Cui (Critical Reviews in Food Science and Nutrition, 2023)

Effects of TCPP and TCEP exposure on human corneal epithelial cells: Oxidative damage, cell cycle arrest, and pyroptosis - Zhen-Ning Zhang; Dan-Lei Yang; Hai Liu; Jue Bi; Ya-Bo Bao; Jiao-Yang Ma; Qin-Xiang Zheng; Dao-Lei Cui; Wei Chen; Ping Xiang (Chemosphere, 2023)

Multi-omics analyses of serum metabolome, urine metabolome and gut microbiome reveal dysregulated glycerophospholipid metabolism in subacute cadmium-exposed wistar rats - Caihong Wu; Fang Fang; Yang Yu; Bo Wang; Haicheng Gao; Weiwei Cui (Toxicology, 2023)

Polyethylene/poly (N, N-dimethyl acrylamide) hybrid hydrogel membrane for total heat exchanger - Ailin Gao; Yang Yang; Changchao Jia; Jian Cui; Bo Wang; Yehai Yan (Chemical Engineering Journal, 2023)

Digestibility, structural and physicochemical properties of microcrystalline butyrylated pea starch with different degree of substitution - Fuyue Dong; Wei Gao; Pengfei Liu; Xuemin Kang; Bin Yu; Bo Cui (Carbohydrate Polymers, 2023)

Source analysis of metals in the tea plant using linear correlation analysis combined with a lead-strontium isotope tracer - Yan Cong; Rui-lian Yu; Yu Yan; Bo-sen Weng; Gong-ren Hu; Jing-wei Sun; Jian-yong Cui; YanYan; Yao-yi Huang (CATENA, 2023)

Evaluation of the respective contribution of anode and cathode for triclosan degradation in a bioelectrochemical system - Min-Hua Cui; Qian Zhang; John Justo Ambuchi; Lan-Ying Liu; Lei Chen; Shi-Ming Niu; Chao Zhang; Hong-Bo Liu; Chao Tie; Xue-Juan Bi; He Liu; Ai-Jie Wang (Bioresource Technology, 2023)

Identification of key odor-active compounds and development of odor wheels in rubber product industries using TD/GC-O-MS, OAV, and statistical analysis - Jing Wang; Meng Han; Jie Meng; Gen Wang; Fulei Lu; Zengxiu Zhai; Boyu Jing; Bo Ma; Xiande Xiao; Huanwen Cui; Zhiqiang Lu; Weifang Li (Atmospheric Pollution Research, 2023)

Understanding the spatial heterogeneity of grazing pressure in the Three-River-Source Region on the Tibetan Plateau - Changjun Gu; Linshan Liu; Yili Zhang; Bo Wei; Bohao Cui; Dianqing Gong (Journal of Geographical Sciences, 2023)

Risk of plant invasions and management planning in the Tibetan Plateau, China - Bo Wei; Yili Zhang; Linshan Liu; Changjun Gu; Zhaofeng Wang; Haibin Yu; Bohao Cui; Dianqing Gong (Journal of Biogeography, 2023)
Aims Mountain environments have high biodiversity and face an accelerating plant invasion risk. Given the enormous ecological and economic value of these ecosystems, there is an urgent need to detect and rapidly respond to invasive species risk. Here, the Tibetan Plateau (TP) in China was selected to examine distribution patterns of invasive alien plants (IAPs) and propose management strategies. Location The Tibetan Plateau in China. Methods Based on native and non‐native occurrences of 123 IAPs alongside environmental variables, we assembled species distribution models and the MIGCLIM model to simulate suitable growth and dispersal areas under current climatic conditions. All IAPs were classified based on the predicted suitable area size, occurrence number and harm level to propose various management strategies. Results There was a significant separation between the climate niches of most IAPs and the climatic conditions of the TP, meaning the areas suitable for most IAPs were limited to low latitudes and elevations. These areas also have further dispersal risks and risks for new IAPs being introduced. Among 123 IAPs, 23 species had above‐average occurrences and suitable distribution areas; in the remaining 100 occurrences and distributions, at least one IAP was less than the average. Main Conclusions Suitable areas for IAPs in the TP are currently limited to low‐elevation regions, which are also at a higher risk of further expansion. Management measures should focus on potential high‐risk areas and diffusion pathways where IAPs can spread further. Efforts should prevent species that have not been established but have large potential suitable areas from being introduced, eradicate established IAPs with limited suitable areas, and control established IAPs. These results can provide a reference for developing more efficient and cost‐effective management strategies.

Geochemical characteristics and ecotoxicological risk of arsenic in water-level-fluctuation zone soils of the Three Gorges Reservoir, China - Meng Cui; Yanyan Li; Dongyu Xu; Jin Lu; Bo Gao (Science of The Total Environment, 2023)

Highly oxygenated germacrane-type sesquiterpenoids from the whole plant of Salvia cavaleriei H.Lév. and their biological activities - Xiao-Han Chen; Xu Liu; Wen-Bo Cui; Feng-Li An; Li Liu; Qian Wu; Jian-Ning Yu; Jian-Ye Dai; Zhan-Xin Zhang; Dong-Qing Fei (Phytochemistry, 2023)

Enhancing simultaneous nitrate and phosphate removal in sulfur‑iron (II) autotrophic denitrification biofilters by endogenous magnetic fields: Performance and mechanism - Shi-Cai Han; You-Wei Cui; Hui-Juan Yan; Yu-Bo Cui; Zhao-Bo Chen (Journal of Water Process Engineering, 2023)

High-quality petroleum-like fuels and/or profitable value-added platform chemicals manufactured via a solid acid-catalyzed two-stage fast oil shale pyrolysis - Guojing Xu; Zhaoyang Ren; Lijie Cui; Zhenpeng Wang; Nannan Wang; Peng Li; Bo Guan; Xujin Qin; Penglei Chen (Fuel, 2023)

Rheological and microstructural characterisation of lotus seed milks and their glucono-δ-lactone induced acid-set milk gels: 1. Effect of protein content - Zhao Li; Tingting Li; Meng Zhao; Bo Cui; Yacine Hemar (Food Hydrocolloids, 2023)

A photothermal cellulose-based material for rapid anti-bacteria and HCHO removal via sequential formation of MnO2 coatings and amine-quinone networks - Xueming Bao; Leilei Wu; Yuanyuan Yu; Bo Xu; Li Cui; Man Zhou; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2023)

Identification and characterization of the gene BraANS.A03 associated with purple leaf color in pak choi (Brassica rapa L. ssp. chinensis) - Chen Tan; Haidong Chen; Guoqiang Dai; Yi Liu; Wenjie Shen; Chenchen Wang; Duannv Liu; Sijia Liu; Shuqi Xu; Bo Zhu; Daozong Chen; Cheng Cui (Planta, 2023)

A Curvelet-Transform-Based Image Fusion Method Incorporating Side-Scan Sonar Image Features - Xinyang Zhao; Shaohua Jin; Gang Bian; Yang Cui; Junsen Wang; Bo Zhou (Journal of Marine Science and Engineering, 2023)
Current methods of fusing side-scan sonar images fail to tackle the issues of shadow removal, preservation of information from adjacent strip images, and maintenance of image clarity and contrast. To address these deficiencies, a novel curvelet-transform-based approach that integrates the complementary attribute of details from side-scan sonar strip images is proposed. By capitalizing on the multiple scales and orientations of the curvelet transform and its intricate hierarchical nature, myriad fusion rules were applied at the corresponding frequency levels, enabling a more-tailored image fusion technique for side-scan sonar imagery. The experimental results validated the effectiveness of this method in preserving valuable information from side-scan sonar images, reducing the presence of shadows and ensuring both clarity and contrast in the fused images. By meeting the aforementioned challenges encountered in existing methodologies, this approach demonstrated great practical significance.

Invasion patterns of Spartina alterniflora: Response of clones and seedlings to flooding and salinity—A case study in the Yellow River Delta, China - Bo Pang; Tian Xie; Zhonghua Ning; Baoshan Cui; Hanxu Zhang; Xinyan Wang; Fang Gao; Shuyan Zhang; Yuming Lu (Science of The Total Environment, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

A new late Katian (Late Ordovician) trilobite association from Zhenxiong, northeastern Yunnan, Southwest China and its palaeoecological implications - Xin Wei; Kai Wang; Zhi-Qiang Zhou; Yu-Nong Cui; Zhu-Tong Zhang; Jian-Bo Liu (Palaeoworld, 2023)

Does seed industry innovation in developing countries contribute to sustainable development of grain green production? Evidence from China - Siyu Gong; Bo Wang; Zhigang Yu; Zhaoda Cui (Journal of Cleaner Production, 2023)

Enrichment of antiplatelet peptides and removal of fishy odor from silver carp skin collagen hydrolysates by macroporous resins: pH value of loading sample affects the peptides separation - Liyuan Cui; Bo Li (Food Chemistry, 2023)

First observed dolphin fall in the South China sea: Implications for the biogeography - Wei Xie; Yadong Zhou; Chunsheng Wang; Bo Lu; Rongfeng Cui; Dongsheng Zhang; Kedong Yin (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

N-Fluorobenzenesulfonimide as a multifunctional electrolyte additive for co-stabilizing dual-electrodes of lithium metal batteries with enhanced electrochemical performance - Xianjun Weng; Yanyang Qin; Xinyu Da; Yuanjun Zhao; Xuetian Deng; Bo Wen; Manying Cui; Xiangkai Yin; Yaqiong Su; Jiangxuan Song; Shujiang Ding; Xiaofei Hu; et al. (Chemical Engineering Journal, 2023)

Toward a better understanding of uncertainty for satellite precipitation products over complex terrain with sparse rain gauge data - Yingying Gai; Xunjian Long; Zhihao Wei; Xinxin Sui; Bo Jiang; Xi Chen; Dingfeng Yu; Shengguang Qin; Yaokui Cui (Atmospheric Research, 2023)

Vancomycin Pretreatment on MPTP-Induced Parkinson’s Disease Mice Exerts Neuroprotection by Suppressing Inflammation Both in Brain and Gut - Chun Cui; Hui Hong; Yun Shi; Yu Zhou; Chen-Meng Qiao; Wei-Jiang Zhao; Li-Ping Zhao; Jian Wu; Wei Quan; Gu-Yu Niu; Yi-Bo Wu; Chao-Sheng Li; et al. (Journal of Neuroimmune Pharmacology, 2023)

Microscopic Analysis of Natural Fracture Properties in Organic-Rich Continental Shale Oil Reservoirs: A Case Study from the Lower Jurassic in the Sichuan Basin, China - Xuefeng Bai; Saipeng Huang; Xiandong Wang; Zhiguo Wang; Youzhi Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Xiaofei Fu; Lijuan Cheng; Likai Cui; et al. (Journal of Marine Science and Engineering, 2023)
Natural fractures are of paramount importance in storing carbon in shale oil reservoirs, where ultra-low porosity and permeability necessitate their essentiality for enhanced oil recovery. Therefore, comprehensively clarifying the characteristics of natural fractures in shale oil reservoirs is imperative. This paper focuses on investigating the microscopic features of natural fractures in organic-rich continental shale oil reservoirs that are commonly found in the Lower Jurassic strata of the Sichuan Basin, employing them as a representative example. Multiple methods were utilized, including mechanical testing, Kaiser testing, multi-scale CT scanning (at 2 mm, 25 mm, and 100 mm scales), and a numerical simulation of fluid seepage in fracture models. The results revealed that the in situ stress of the target seam displays the characteristic of σH > σv > σh, with σv and σh being particularly similar. The relatively high lateral stress coefficient (ranging from 1.020 to 1.037) indicates that the horizontal stresses are higher than the average level. Although the 2 mm CT scan provides a more detailed view of fractures and connected pores, it primarily exhibited more pore information due to the high resolution, which may not fully unveil additional information about the fractures. Thus, the 25 mm shale core is a better option for studying natural fractures. The tortuosity of the different fractures indicated that the morphology of larger fractures is more likely to remain stable, while small-scale fractures tend to exhibit diverse shapes. The simulations demonstrated that the stress sensitivity of fracture permeability is approximately comparable across different fracture scales. Therefore, our research can enhance the understanding of the properties of natural fractures, facilitate predicting favorable areas for shale oil exploration, and aid in evaluating the carbon storage potential of shale oil reservoirs.

A comprehensive health effects assessment of the use of sanitizers and disinfectants during COVID-19 pandemic: a global survey - Fallah Hashemi; Lori Hoepner; Farahnaz Soleimani Hamidinejad; Daniela Haluza; Sima Afrashteh; Alireza Abbasi; Elma Omeragić; Belma Imamović; Narin A. Rasheed; Taqi M. J. Taher; Fitri Kurniasari; Dhuha Youssef Wazqar; et al. (Environmental Science and Pollution Research, 2023)

Magnetic field delays the senescence of strawberries by maintaining energy state and regulating respiratory metabolism - Fan Liu; Na Yang; Lingtao Zhang; Bo Cui; Yamei Jin; Zhengyu Jin; Xueming Xu (Postharvest Biology and Technology, 2023)

Polysulfide-derived anion heterogeneous interfaces engineering to facilitate high-efficiency sodium ion storage - Jian Wang; Jing Cui; Zhaojin Li; Di Zhang; Huilan Sun; Huan Wang; Qiujun Wang; H.J. Woo; S. Ramesh; Bo Wang (Chemical Engineering Journal, 2023)

Metatranscriptomic insights into the microbial electrosynthesis of acetate by Fe2+/Ni2+ addition - Jie Zhang; He Liu; Yan Zhang; Bo Fu; Chao Zhang; Min-Hua Cui; Ping Wu; Zi-Wei Guan (World Journal of Microbiology and Biotechnology, 2023)

Distribution and dissipation laws of excess pore water pressure based on pile-soil interface during pile-sinking in saturated clay - Yonghong Wang; Jiamin Jin; Bo Han; Yishun Jiang; Dongsheng Jeng; Huining Liu; Zuodong Liang; Lin Cui (Soil Dynamics and Earthquake Engineering, 2023)

Debris flow characteristics of the compound channels with vegetated floodplains - Wen-rong Cui; Jian-gang Chen; Xiao-qing Chen; Jin-bo Tang; Ke Jin (Science of The Total Environment, 2023)

Stability mechanism of Pickering emulsions co-stabilized by protein nanoparticles and small molecular emulsifiers by two-step emulsification with different adding sequences: From microscopic to macroscopic scales - Song Cui; Zhenyu Yang; David Julian McClements; Xingfeng Xu; Xin Qiao; Liyang Zhou; Qingjie Sun; Bo Jiao; Qiang Wang; Lei Dai (Food Hydrocolloids, 2023)

Effect of molecular structure changes during starch gelatinization on its rheological and 3D printing properties - Yue Cheng; Kexin Liang; Yifan Chen; Wei Gao; Xuemin Kang; Tianze Li; Bo Cui (Food Hydrocolloids, 2023)

Coupling effect of freeze–thaw cycles and multiaxial compression on concrete-filled steel tube (CFST): Insights from simplified meso-scale axisymmetric finite element model - Facheng Wang; Bo Li; Zhengqing Cheng; Tao Cui (Engineering Structures, 2023)

Effects of different rapid cooling temperatures and annealing on functional properties of starch straws after thermoplastic extrusion - Kun Wang; Feixue Zou; Haiteng Tao; Wei Gao; Li Guo; Bo Cui; Chao Yuan; Pengfei Liu; Lu Lu; Zhengzong Wu (Carbohydrate Polymers, 2023)

Genetic and enzymatic characterization of two novel blaNDM-36, -37 variants in Escherichia coli strains - Wanshan Ma; Bo Zhu; Wen Wang; Qian Wang; Xiaodi Cui; Yujiao Wang; Xiutao Dong; Xiaofeng Li; Jianping Ma; Fang Cheng; Xiaohong Shi; Liang Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
The widespread of different NDM variants in clinical Enterobacterales isolates poses a serious public health concern, which requires continuous monitoring. In this study, three E. coli strains carrying two novel bla NDM variants of bla NDM-36, -37 were identified from a patient with refractory urinary tract infection (UTI) in China. We conducted antimicrobial susceptibility testing (AST), enzyme kinetics analysis, conjugation experiment, whole-genome sequencing (WGS), and bioinformatics analysis to characterize the bla NDM-36, -37 enzymes and their carrying strains. The bla NDM-36, -37 harboring E. coli isolates belonged to ST227, O9:H10 serotype and exhibited intermediate or resistance to all β-lactams tested except aztreonam and aztreonam/avibactam. The genes of bla NDM-36, -37 were located on a conjugative IncHI2-type plasmid. NDM-37 differed from NDM-5 by a single amino acid substitution (His261Tyr). NDM-36 differed from NDM-37 by an additional missense mutation (Ala233Val). NDM-36 had increased hydrolytic activity toward ampicillin and cefotaxime relative to NDM-37 and NDM-5, while NDM-37 and NDM-36 had lower catalytic activity toward imipenem but higher activity against meropenem in comparison to NDM-5. This is the first report of co-occurrence of two novel bla NDM variants in E. coli isolated from the same patient. The work provides insights into the enzymatic function and demonstrates the ongoing evolution of NDM enzymes.

Stress response of fresh-cut potatoes to laser irradiation before processing can prevent discoloration and maintain overall quality - Bo Wen; Shijiang Cui; Xiaoyu Suo; Suriyan Supapvanich (Postharvest Biology and Technology, 2023)

Biomimetic cellulose-nanocrystalline-based composite membrane with high flux for efficient purification of oil-in-water emulsions - Jianfei Wu; Ziwei Cui; Yuxuan Su; Yang Yu; Bo Yue; Jundie Hu; Jiafu Qu; Dan Tian; Xianxu Zhan; Jianzhang Li; Yahui Cai (Journal of Hazardous Materials, 2023)

Pickering emulsion stabilized by linear dextrins: Effect of the chain length - Yuechun Zhu; Chao Yuan; Bo Cui; Li Guo; Meng Zhao (Food Hydrocolloids, 2023)

The combined effects of NaCl-pH and urea-pH on the phase separation of type-A gelatin and dextran - Qi Wang; Bo Cui; Li Guo; Zhao Li; Qingqing Chai; Na Wang; Die Dong; Katsuyoshi Nishinari; Meng Zhao (Food Hydrocolloids, 2023)

Arsenic metabolism, N6AMT1 and AS3MT single nucleotide polymorphisms, and their interaction on gestational diabetes mellitus in Chinese pregnant women - Xiaoshan Liang; Guanshuai Guo; Yiyun Wang; Meng Wang; Xi Chen; Jingran Zhang; Shuying Li; Liangpo Liu; Qingyu Huang; Bo Cui; Ming Zhang; Guifan Sun; et al. (Environmental Research, 2023)

Trends in elemental Pb concentrations within atmospheric PM2.5 and associated risk to human health in major cities of China - Qian Cui; Liangzhong Li; Yaqiang Cao; Bo Yang; Lindou Liu; Xiaoyan Dong; Yu'e Cha; Hongjie Ruan; Song Tang; Qiong Wang (Environmental Pollution, 2023)

One-dimensional non-linear rheological consolidation of clayey soils with Swartzendruber's flow law - Peng-lu Cui; Wen-Gui Cao; Zan Xu; Yun-bo Wei; Huixin Li (Computers and Geotechnics, 2023)

Effects of mesylate-/tartrate-based ionic liquids-water mixtures on the phase transition behaviors and stability of corn starch: A comparative study - Zunxiang Huang; Lu Lu; Xueting Li; Ziling Zhang; Jingmin Shen; Bo Cui; Li Guo; Chao Yuan; Shiqing Zhang (Carbohydrate Polymers, 2023)

A preliminary study on the acoustic properties of seafloor sediment in the southern U-boundary of the South China Sea - Zhengyu Hou; Danling Tang; Yao Xiao; Jingqiang Wang; Bo Zhang; Xiaoming Cui; Peng Hao (Journal of Oceanology and Limnology, 2023)

A Mechanistic Study of Goethite-Based Fenton-Like Reactions for Imidacloprid Degradation - Bo Ye; Hongbiao Cui; Ning Chen; Guodong Fang; Juan Gao; Yujun Wang (Bulletin of Environmental Contamination and Toxicology, 2023)

Application of logistic regression model for hazard assessment of landslides caused by the 2012 Yiliang Ms 5.7 earthquake in Yunnan Province, China - Jia-le Jin; Yu-long Cui; Chong Xu; Jun Zheng; Hai-bo Miao (Journal of Mountain Science, 2023)

Highly selective adsorption of Hg (II) from aqueous solution by three-dimensional porous N-doped starch-based carbon - Chao Geng; Ruikang Lin; Peilin Yang; Pengfei Liu; Li Guo; Bo Cui; Yishan Fang (Environmental Science and Pollution Research, 2023)

A GIS-based method for modeling methane emissions from paddy fields by fusing multiple sources of data - Linhua Ma; Yuanlai Cui; Bo Liu; Bin Liao; Jun Wei; Huanhao Han; Wenxiang Tian (Science of The Total Environment, 2023)

Evaluating the social license to operate of waste-to-energy incineration projects: A case study from the Yangtze River Delta of China - Xinyao He; Min Xu; Caiyun Cui; Bo Xia; Yongjian Ke; Martin Skitmore; Yong Liu (Journal of Cleaner Production, 2023)

A high-efficient anisotropic continuum model for the optimization of heat transfer and chemical reaction in a packed-bed water gas shift reactor - Bo Jiang; Haonan Wang; Kewei Yu; Jing Ma; Wang Si-ma; Yuming Gao; Lin Li; Xinwei Zhang; Huiru Cui; Dawei Tang (Fuel, 2023)

Effects of water/ionic liquid ratios on the physicochemical properties of high amylose maize starch-lauric acid complex - Pengfei Liu; Yuhan Dong; Wei Gao; Zhengzong Wu; Bin Yu; Chao Yuan; Bo Cui (Food Hydrocolloids, 2023)

Improvement of myocardial injury and gut microbiota disturbance in type 2 diabetic mice by inulin with various degrees of polymerization - Siqiang Jia; Jianpeng Li; Bin Yu; Mengjie Li; Bo Cui (Food Bioscience, 2023)

Structure, Intracellular Localisation and Expression Analysis of Sucrose Nonfermenting-Related Kinase ShSnRK1α in Sugarcane - Ting-ting Zhao; Jun-gang Wang; Wen-zhi Wang; Cui-lian Feng; Xiao-yan Feng; Lin-bo Shen; Shu-zhen Zhang (Sugar Tech, 2023)

Evaluation of Copper Levels in Dental Calculus of OSF Patients with Chewing Dried Areca-Nut Quids in Hunan Province of Mainland China - Xi-Fan He; Hui Wang; Ye Tian; Te Zhang; Zhi-Peng Qiu; Xiao-Jiao Cui; Jing-Sha Zhou; Xin-Lan Yan; Yi-Wei Wu; Yi-Sha Pan; Yang-Bo Ning; Lin Chen; et al. (Biological Trace Element Research, 2023)

Spatio-Temporal Variations in the Potential Habitat Distribution of Pacific Sardine (Sardinops sagax) in the Northwest Pacific Ocean - Yongchuang Shi; Bo Kang; Wei Fan; Lingling Xu; Shengmao Zhang; Xuesen Cui; Yang Dai (Fishes, 2023)
Pacific sardine (Sardinops sagax) is a commercially important species and supports important fisheries in the Northwest Pacific Ocean (NPO). Understanding the habitat distribution patterns of Pacific sardine is of great significance for fishing ground prediction and stock management. In this study, both single-algorithm and ensemble distribution models were established through the Biomod2 package for Pacific sardine by combining the species occurrence data, sea surface temperature (SST), sea surface height (SSH), sea surface salinity (SSS) and chlorophyll-a concentration (Chla) in the NPO during the main fishing season (June–November) from 2015 to 2020. The results indicated that the key environmental variables affecting the habitat distribution of Pacific sardine were the SSH and SST. The suitable habitat area for Pacific sardine showed significant monthly changes: the suitable habitat range in June was larger than that in July and August, while the suitable habitat range gradually increased from September to November. Furthermore, the monthly geometric centers of habitat suitability index (HSI) for Pacific sardine presented a counterclockwise pattern, gradually moving to the northeast from June, and then turning back to the southwest from August. Compared with single-algorithm models, the ensemble model had higher evaluation metric values and better spatial correspondence between habitat prediction and occurrence records data, which indicated that the ensemble model can provide more accurate prediction and is a promising tool for potential habitat forecasting and resource management.

Bioactive diterpenoids and sesquiterpenoids with different skeletons from Salvia digitaloides Diels - Xu Liu; Xiao-Qing Zhan; Mei-Jie Wang; Wen-Bo Cui; Xiao-Han Chen; Feng-Ming Qi; Jian-Ning Yu; Jian-Ye Dai; Dong-Qing Fei; Zhan-Xin Zhang (Phytochemistry, 2023)

Social acceptance of NIMBY facilities: A comparative study between public acceptance and the social license to operate analytical frameworks - Min Xu; Yong Liu; Caiyun Cui; Bo Xia; Yongjian Ke; Martin Skitmore (Land Use Policy, 2023)

Distribution of per- and poly-fluoroalkyl substances and their precursors in human blood - Daxi Liu; Bo Tang; Saisai Nie; Nan Zhao; Li He; Jiansheng Cui; Weili Mao; Hangbiao Jin (Journal of Hazardous Materials, 2023)

In situ generated PtNPs to enhance electrochemiluminescence of multifunctional nanoreactor COP T4VTP6 for AFB1 detection - Xiaoyi Lv; Fei Tan; Tian Miao; Bo Cui; Jianguo Zhang; Yishan Fang; Yizhong Shen (Food Chemistry, 2023)

Interfacial behavior of cyclodextrins at the oil-water interface of Pickering emulsion - Caiyun Cheng; Chao Yuan; Bo Cui; Lu Lu; Jianpeng Li; Haojie Sha (Food Hydrocolloids, 2023)

The pH-dependent phase separation kinetics of type-A gelatin and dextran with different initial microstructures - Qi Wang; Zhongqiu Han; Bo Cui; Chao Yuan; Jianpeng Li; Katsuyoshi Nishinari; Meng Zhao (Food Hydrocolloids, 2023)

Millennial-scale glacier fluctuations on the southeastern Tibetan Plateau during MIS 2 - Jie Wang; Weicheng Wang; Bo Cao; Hang Cui; Xiaojing Chen; Jinkun Qiu; Manhong Lei; Jingsheng Liao (Earth and Planetary Science Letters, 2023)

Self-healing properties of retrograded starch films with enzyme-treated waxy maize starch as healing agent - Li Guo; Na Yang; Wei Gao; Haiteng Tao; Bo Cui; Pengfei Liu; Feixue Zou; Lu Lu; Yishan Fang; Zhengzong Wu (Carbohydrate Polymers, 2023)

Influence of thermal hydrolysis on sludge anaerobic digestion: Release of humic acid promotes electron transport of methanogen - Cheng Zhao; Hongbo Liu; He Liu; Xinmin Zhan; Xuedong Zhang; Bo Fu; Mingze Shi; Shuailing Lu; Fang Huang; Minhua Cui; Yajie Li (Chemical Engineering Journal, 2023)

Mechanisms of PiT2-loop7 Missense Mutations Induced Pi Dyshomeostasis - Hao Sun; Xuan Xu; Junyu Luo; Tingbin Ma; Jiaming Cui; Mugen Liu; Bo Xiong; Shujia Zhu; Jing-Yu Liu (Neuroscience Bulletin, 2023)

Life-course exposure to ambient fine particulate matter and hypertension in adulthood: a longitudinal cohort study - Cui Guo; Ly-yun Chang; Yacong Bo; Changqing Lin; Alexis K. H. Lau; Tony Tam; Xiang Qian Lao (Environmental Science and Pollution Research, 2023)

Response adaptive mechanisms of three mangrove (Avicennia marina, Aegiceras corniculatum, and Bruguiera gymnorrhiza) plants to waterlogging stress revealed by transcriptome analysis - Bo-Yu Su; You-Shao Wang; Cui-Ci Sun (Frontiers in Marine Science, 2022)
Distributed in different elevations of the intertidal zone, mangrove plants suffer different periods of flooding, and with varied adaptability to waterlogging from the physiological structure to the metabolic mechanism. Associated with species distribution, transcriptome sequencing was performed to explore the interspecific differences of molecular response mechanisms among Avicennia marina , Aegiceras corniculatum , and Bruguiera gymnorrhiza under waterlogging stress. Results showed that the counts of differentially expressed genes (DEGs) in A. Marina were the highest after stress, followed by Ae. corniculatum and B. gymnorrhiza . It was found that the functions of genes with high differential expression folds (more than eight folds) in the three plants could be classified into four categories: structural regulation, transport, biosynthesis, and protection. It was also found that A. Marina has strong regulation ability in the metabolic process, which can guarantee energy supply and maintain active biosynthesis under waterlogging conditions. In addition, A. Marina was activated in the ethylene synthesis pathway to promote aerenchyma formation and to avoid root tissue hypoxia. Being different from A. Marina and B. gymnorrhiza , Ae. corniculatum down-regulated the XET , SAMS , and ACCO genes, which were involved in the cell wall regulation or ethylene formation that might indicate a different adaptive mechanism. Alcohol dehydrogenase ( ADH ) and lactate dehydrogenase ( LDH ) were cloned from A. Marina , Ae. corniculatum , and B. gymnorrhiza . The cloned genes were named as AmADH , AmLDH , AcADH , AcLDH , BgADH , and BgLDH , respectively. qRT-PCR detection verified that LDH s and ADH s were involved in the response of mangrove plants to waterlogging stress, and interspecific difference was observed. The expressions of AcADH and AcLDH were the most prominent. Combined with transcriptome, it was considered that Ae. corniculatum was more dependent on the expression of AcADH and AcLDH that might compensate the weakness of cell wall regulation, whereas A. Marina was more dependent on the regulation of cell structure reversely.

Effects of perceived stress on public acceptance of waste incineration projects: evidence from three cities in China - Jiabin Chen; Xinyao He; Caiyun Cui; Bo Xia; Martin Skitmore; Yong Liu (Environmental Science and Pollution Research, 2022)

Insight into different adsorption behaviors of two fluoroquinolone antibiotics by sediment aggregation fractions - Bo Zhang; Juan Chen; Chao Wang; Peifang Wang; Ge Cui; Jingjing Zhang; Yu Hu; Han Gao (Environmental Science and Pollution Research, 2022)

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

A novel method for fabrication of coated microneedles with homogeneous and controllable drug dosage for transdermal drug delivery - Bo Zhi Chen; Meng Chan He; Xiao Peng Zhang; Wen Min Fei; Yong Cui; Xin Dong Guo (Drug Delivery and Translational Research, 2022)

Cumulative risk assessment of dietary exposure to phthalates in pregnant women in Beijing, China - Danping Shan; Tao Zhang; Ludi Li; Yuqing Sun; Di Wang; Yingzi Li; Zheng Yang; Kanglong Cui; Shaowei Wu; Lei Jin; Bo Hong; Xuejun Shang; et al. (Environmental Science and Pollution Research, 2022)

An update on microneedle-based systems for diabetes - Wen Xuan Li; Xiao Peng Zhang; Bo Zhi Chen; Wen Min Fei; Yong Cui; Can Yang Zhang; Xin Dong Guo (Drug Delivery and Translational Research, 2022)

Control, Treatment and Restoration of Contaminated Soils - Hong-Bo Li; Changsheng Qu; Xinyi Cui; Yang Song; Chao Wang; Cheng Gu (Bulletin of Environmental Contamination and Toxicology, 2022)

Brain structural and perfusion changes in amyotrophic lateral sclerosis-frontotemporal dementia patients with cognitive and motor onset: a preliminary study - Yanying Wang; Dongchao Shen; Bo Hou; Xiaohan Sun; Xunzhe Yang; Jing Gao; Mingsheng Liu; Feng Feng; Liying Cui (Brain Imaging and Behavior, 2022)

DOA tracking using an improved direction lock loop based on a three-element L-shaped array - Bin Yang; Weijia Cui; Yongjun Liu; Bo Gao; Fengtong Mei; Haiyun Xu (GPS Solutions, 2022)

Screening for SH3TC2 variants in Charcot–Marie–Tooth disease in a cohort of Chinese patients - Bo Sun; Zheng-Qing He; Yan-Ran Li; Jiong-Ming Bai; Hao-Ran Wang; Hong-Fen Wang; Fang Cui; Fei Yang; Xu-Sheng Huang (Acta Neurologica Belgica, 2022)

Reconstruction of ocean temperature and salinity profiles in the Northern South China Sea using satellite observations - Bo Tang; Dandan Zhao; Chaoran Cui; Xinhua Zhao (Frontiers in Marine Science, 2022)
Based on historical temperature and salinity (T–S) profiles, the correlation between the sea surface temperature (SST) anomaly, sea surface dynamic height (SSH) anomaly, and temperature profile anomaly is constructed by regression analysis. A three-dimensional temperature field is reconstructed in the northern South China Sea by satellite SST and SSH, with daily temporal and 0.25°×0.25° spatial resolutions. The three-dimensional salinity field is also reconstructed based on the correlation between salinity and temperature. Compared with the observational T–S profiles, the reconstructed T–S field reflects the characteristics and structure and accurately describes the mesoscale variability of the ocean temperature field. The new expanded T–S field can be used as the initial field in numerical models and be assimilated into numerical reanalysis and prediction systems, improving their output.

Efficient capture of U(VI) by magnetic Zr(IV)-ethylenediamine tetramethylene phosphonic acid inorganic-organic hybrid - Qie Luo; Wenzheng Cui; Huan Wang; Bo Xiao; Lei Chen; Youqun Wang; Zhibin Zhang; Yunhai Liu; Xiaohong Cao (Environmental Science and Pollution Research, 2022)

NGF/TrkA promotes the vitality, migration and adhesion of bone marrow stromal cells in hypoxia by regulating the Nrf2 pathway - Cui-Ni Fang; Hai-Qun Tan; Ao-Bo Song; Ni Jiang; Qian-Rong Liu; Tao Song (Metabolic Brain Disease, 2022)

Trachyte reservoir characteristics and favorable reservoir identification and prediction in the J34 block, Eastern Sag - Chenglong Ma; Ying Wu; Tuan Gu; Bin Zhang; Yu Gang Li; Ying Jie Zhang; Wen Bo Dong; Jie Cui (Acta Geophysica, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Landslides triggered by the 1970 Ms 7.7 Tonghai earthquake in Yunnan, China: an inventory, distribution characteristics, and tectonic significance - Yu-long Cui; Jun-hong Hu; Chong Xu; Hai-bo Miao; Jun Zheng (Journal of Mountain Science, 2022)

Human motor learning is robust to control-dependent noise - Bo Pang; Leilei Cui; Zhong-Ping Jiang (Biological Cybernetics, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

An overview on plasticized biodegradable corn starch-based films: the physicochemical properties and gelatinization process - Bin Wang; Bin Yu; Chao Yuan; Li Guo; Pengfei Liu; Wei Gao; Dapeng Li; Bo Cui; A. M. Abd El-Aty (Critical Reviews in Food Science and Nutrition, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Depth-resolved numerical model of dam break mud flows with Herschel-Bulkley rheology - Jin-bo Tang; Peng-zhi Lin; Peng Cui (Journal of Mountain Science, 2022)

Dissolving microneedle rollers for rapid transdermal drug delivery - Xiao Peng Zhang; Bao Li Zhang; Bo Zhi Chen; Ze Qiang Zhao; Wen Min Fei; Yong Cui; Xin Dong Guo (Drug Delivery and Translational Research, 2022)

A Case Study on the Rapid Rain-to-Snow Transition in Late Spring 2018 over Northern China: Effects of Return Flows and Topography - Wenlong Zhang; Xiaopeng Cui; Bolong Duan; Bo Yu; Runxia Guo; Haiwen Liu (Journal of Meteorological Research, 2022)

Rapid visual detection of porcine reproductive and respiratory syndrome virus via recombinase polymerase amplification combined with a lateral flow dipstick - Xiao-Xiao Tian; Tao Wang; Xing-Yang Cui; Xin-Yi Huang; Yue Sun; Da-Song Xia; Yong-Bo Yang; Xue-Hui Cai; Tong-Qing An (Archives of Virology, 2022)

A procedure for interaction between rock mass and liner for deep circular tunnel based on new solution of longitudinal displacement profile - Qiang Shen; Jun-Jie Zheng; Lan Cui; Yu Pan; Bo Cui (European Journal of Environmental and Civil Engineering, 2022)

Characteristics and Environmental Response of White Secondary Mineral Precipitate in the Acid Mine Drainage From Jinduicheng Mine, Shaanxi, China - Cong Lu; Bo Yang; Xing Cui; Sichang Wang; Chengtun Qu; Weiwei Zhang; Bo Zhou (Bulletin of Environmental Contamination and Toxicology, 2021)

Understanding the Yanshan volcano eruption in the Chaihe–Arxan volcanic field, northeastern China - Xiao-ge Cui; Jian-dong Xu; Hong-mei Yu; Bo Zhao; Wen-jian Yang (Arabian Journal of Geosciences, 2021)

Research progress of disaster factors and a prevention alarm index of coal and gas outbursts - Fakai Wang; Pan Zhang; Bo Cui; Zhongguang Sun; Kaizhi Zhang (Arabian Journal of Geosciences, 2021)

Transient silencing of VvCSN5 enhances powdery mildew resistance in grapevine (Vitis vinifera) - Kai-Cheng Cui; Min Liu; Gui-Hua Ke; Xing-Yuan Zhang; Bo Mu; Min Zhou; Yang Hu; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Microbial characteristics response to the soil quality of newly created farmland on the Loess Plateau - Chen Xu; Yi-ping Chen; Cui-cui Su; Ji-fu Ma; Jun-hua Wu; Kai-bo Wang; Yi Wang; Yao Jiang (Environmental Science and Pollution Research, 2021)

A catastrophic natural disaster chain of typhoon-rainstorm-landslide-barrier lake-flooding in Zhejiang Province, China - Yu-long Cui; Jun-hong Hu; Chong Xu; Jun Zheng; Jiang-bo Wei (Journal of Mountain Science, 2021)

Fusarium solani G6, a novel vitexin-producing endophytic fungus: characterization, yield improvement and osteoblastic proliferation activity - Pei-jia Tang; Zhi-hui Zhang; Li-li Niu; Cheng-bo Gu; Wen-yi Zheng; Hai-chao Cui; Xiao-han Yuan (Biotechnology Letters, 2021)

Occurrence and cycle of dimethyl sulfide in the western Pacific Ocean - Feng Xu; Shi‐Bo Yan; Hong‐Hai Zhang; Ying‐Cui Wu; Qian‐Yao Ma; Yu‐Chen Song; Guang‐Chao Zhuang; Gui‐Peng Yang (Limnology and Oceanography, 2021)
Oceanic production and occurrence of dimethyl sulfide (DMS) and its subsequent ventilation to the atmosphere significantly contribute to the global sulfur cycle and impact the climate regulation. Spatial distributions of DMS, dimethylsulfoniopropionate (DMSP, precursor of DMS), and dimethyl sulfoxide (DMSO, oxidation product of DMS), production and removal processes of DMS (including biological production, microbial consumption, photo‐degradation, and sea‐to‐air exchange), and biogenic contributions to the atmospheric sulfate burden were simultaneously studied in the western Pacific Ocean during winter. Sea surface DMS, DMSP, and DMSO were strongly correlated and had similar distribution patterns. The DMS photo‐degradation efficiency ratio (normalized using incident photon flux density) for ultraviolet B radiation (UVB): ultraviolet A radiation (UVA): photosynthetically active radiation (PAR) was 391: 36: 1. However, considering the solar spectral composition, the actual contributions of UVB, UVA, and PAR to DMS photo‐degradation in surface waters were 40.6% ± 10.7%, 41.2% ± 15.6%, and 18.2% ± 7.2%, respectively. When integrated across the entire mixed layer, UVA and PAR became the dominant drivers, accounting for 45.2% ± 18.0% and 38.0% ± 17.3% of DMS photo‐degradation, respectively, as UVB was significantly attenuated in seawater. The DMS budget of the entire mixed layer indicated that microbial consumption, photo‐degradation, and ventilation accounted for about 74.3% ± 11.9%, 19.3% ± 9.3%, and 6.5% ± 4.0% of total DMS removal, respectively. Even if ventilation was a minor DMS removal pathway, DMS emissions still contributed approximately 45.2% ± 25.6% of the atmospheric non‐sea‐salt sulfate burden over the western Pacific Ocean.

Retrieval of sea surface temperature from the scanning microwave radiometer aboard HY-2B - Shu-Bo Liu; Xin-Dong Cui; Yi-Nan Li; Xu Jin; Wu Zhou; Hong-Xing Dang; Hao Li (International Journal of Remote Sensing, 2021)

Identification of differentially expressed genes associated with aluminum resistance in the soybean plant - Jing-xuan Wang; Bo Wang; Lu-bin Cui; Hao Xie; Run-zhi Li; Cheng Wang; Zhang-jie Nan; Yu-shu Liu; Jing-yu Ma; Yun-jin Sun; Wei-yu Li (Physiology and Molecular Biology of Plants, 2021)

Ziziphus jujuba Mill., a plant used as medicinal food: a review of its phytochemistry, pharmacology, quality control and future research - Shi-Jun Liu; Yan-Ping Lv; Zhi-Shu Tang; Yu Zhang; Hong-Bo Xu; Dong-Bo Zhang; Chun-Li Cui; Hong-Bo Liu; Huan-Huan Sun; Zhong-Xing Song; Si-Min Wei (Phytochemistry Reviews, 2021)

Experimental study on adsorption promotion and desorption restrain of gas-containing coal in low-temperature environment - Fakai Wang; Xuelong Li; Bo Cui; Jian Hao; Xin Gao; Kun Long; Peng Chen; Sheng Wang (Arabian Journal of Geosciences, 2021)

Design, synthesis and evaluation of dihydrotriazine derivatives-bearing 5-aryloxypyrazole moieties as antibacterial agents - Tian-Yi Zhang; Chun-Shi Li; Ming-Yue Cui; Xue-Qian Bai; Jiang-Hui Chen; Ze-Wen Song; Bo Feng; Xue-Kun Liu (Molecular Diversity, 2021)

A classifier-combined method based on D-S evidence theory for the land cover classification of the Tibetan Plateau - Shuang Hao; Yongfu Chen; Bo Hu; Yuhuan Cui (Environmental Science and Pollution Research, 2021)

Increased resting state functional irregularity of T2DM brains with high HbA1c: sign for impaired verbal memory function? - Xin Zhang; Ying Yu; Zhe-Sheng Shi; Ke Xu; Jia-Hao Feng; Ze-Yang Li; Xiang-Nan Zhang; Shu-Ning Shen; Yang Yang; Lin-Feng Yan; Jin Zhang; Qian Sun; et al. (Brain Imaging and Behavior, 2021)

Docosahexaenoic Acid (DHA) Supplementation Alters Phospholipid Species and Lipid Peroxidation Products in Adult Mouse Brain, Heart, and Plasma - Grace Y. Sun; Michael K. Appenteng; Runting Li; Taeseon Woo; Bo Yang; Chao Qin; Meixia Pan; Magdalena Cieślik; Jiankun Cui; Kevin L. Fritsche; Zezong Gu; Matthew Will; et al. (NeuroMolecular Medicine, 2021)

Sigma-1 receptor ligands improves ventricular repolarization-related ion remodeling in rats with major depression disorder - Yan Guo; Cui Zhang; Xiuhuan Chen; Xin Liu; Tianxin Ye; Yuhong Fo; Shaobo Shi; Chuan Qu; Jinjun Liang; Bo Shen; Bo Yang (Psychopharmacology, 2021)

Current Progress in Understanding the Structure and Function of Sweet Taste Receptor - Liu Yang; Meng Cui; Bo Liu (Journal of Molecular Neuroscience, 2021)

Molecular evolution and pathogenicity of chicken anemia virus isolates in China - Yue Li; Nana Yan; Yongqiang Wang; Aijing Liu; Changjun Liu; Xingge Lan; Bo Yang; Yulong Gao; Honglei Gao; Xiaole Qi; Hongyu Cui; Kai Li; et al. (Archives of Virology, 2021)

Design and Characterization of a Novel Hybrid Antimicrobial Peptide OM19R Based on Oncocin and MDAP-2 - Lei Liu; Jie Liu; Qi Cui; Bo-Yan Jia; Zhi-Hua Pei; Kokou Ayefounin Odah; Yi-Ming Wang; Wen-Long Dong; Ling-Cong Kong; Hong-Xia Ma (International Journal of Peptide Research and Therapeutics, 2020)

Induced sputum metabolomic profiles and oxidative stress are associated with chronic obstructive pulmonary disease (COPD) severity: potential use for predictive, preventive, and personalized medicine - Tao Zhu; Shanqun Li; Jiajia Wang; Chunfang Liu; Lei Gao; Yuzhen Zeng; Ruolin Mao; Bo Cui; Hong Ji; Zhihong Chen (EPMA Journal, 2020)
Chronic obstructive pulmonary disease (COPD) is a highly heterogeneous disease, and metabolomics plays a hub role in predictive, preventive, and personalized medicine (PPPM) related to COPD. This study thus aimed to reveal the role of induced sputum metabolomics in predicting COPD severity. In this pilot study, a total of 20 COPD patients were included. The induced sputum metabolites were assayed using a liquid chromatography-mass spectrometry (LC-MS/MS) system. Five oxidative stress products (myeloperoxidase (MPO), superoxide dismutase (SOD), glutathione (GSH), neutrophil elastase (NE), and 8-iso-PGF2α) in induced sputum were measured by ELISA, and the metabolomic profiles were distinguished by principal component analysis (PCA) and orthogonal projections to latent structures discriminant analysis (OPLS-DA). The Kyoto Encyclopedia of Genes and Genomes (KEGG) was used for pathway enrichment analysis, and a significant difference in induced sputum metabolomics was observed between moderate and severe COPD. The KEGG analysis revealed that the glycerophospholipid metabolism pathway was downregulated in severe COPD. Due to the critical role of glycerophospholipid metabolism in oxidative stress, significant negative correlations were discovered between glycerophospholipid metabolites and three oxidative stress products (SOD, MPO, and 8-iso-PGF2α). The diagnostic values of SOD, MPO, and 8-iso-PGF2α in induced sputum were found to exhibit high sensitivities and specificities in the prediction of COPD severity. Collectively, this study provides the first identification of the association between induced sputum metabolomic profiles and COPD severity, indicating the potential value of metabolomics in PPPM for COPD management. The study also reveals the correlation between glycerophospholipid metabolites and oxidative stress products and their value for predicting COPD severity.

Altered spontaneous functional activity of the right precuneus and cuneus in patients with persistent postural-perceptual dizziness - Kangzhi Li; Lihong Si; Bin Cui; Xia Ling; Bo Shen; Xu Yang (Brain Imaging and Behavior, 2020)

Microalgal Cultivation in Secondary Effluents: Enhancement of Algal Biomass, Nutrient Removal, and Lipid Productivity - Bo Zhang; Fanping Meng; Hongwu Cui; Xiang Dou; Shuhao Du; Xiaoling Peng (Journal of Ocean University of China, 2020)

A pair of new neo -clerodane diterpenoid epimers from the roots of Croton crassifolius and their anti-inflammatory - Dong-Bo Zhang; Zhi-Shu Tang; Pei Xie; Yan-Ni Liang; Jin-Gao Yu; Zhen Zhang; Dong-Zhu Duan; Chun-Li Cui; Zhong-Xing Song; Li Ren; Zheng Wang; Dao-Geng Yu (Natural Product Research, 2020)

Establishment of a chloroplast transformation system in Tisochrysis lutea - Yuntai Bo; Kang Wang; Yuanyuan Wu; Haiyang Cao; Yulin Cui; Lan Wang (Journal of Applied Phycology, 2020)

Genome-wide identification of WD40 genes reveals a functional diversification of COP1-like genes in Rosaceae - Yi-Bo Sun; Xiao-Jia Zhang; Mi-Cai Zhong; Xue Dong; Dong-Mei Yu; Xiao-Dong Jiang; Dan Wang; Wei-Hua Cui; Jiang-Hua Chen; Jin-Yong Hu (Plant Molecular Biology, 2020)

Multiplex RT–PCR Assay for the Simultaneous Detection and Identification of Five Sugarcane Viruses - Xiao-Yan Feng; Wen-Zhi Wang; Lin-Bo Shen; Jun-Gang Wang; Guo-Ru Xiong; Cui-Lian Feng; Ting-Ting Zhao; Shu-Zhen Zhang (Sugar Tech, 2020)

Comprehensive analysis of miRNA-gene regulatory network with clinical significance in human cancers - Xiuliang Cui; Yang Liu; Wen Sun; Jin Ding; Xiaochen Bo; Hongyang Wang (Science China Life Sciences, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Harpagophytum procumbens Extract Ameliorates Allodynia and Modulates Oxidative and Antioxidant Stress Pathways in a Rat Model of Spinal Cord Injury - Garrett Ungerer; Jiankun Cui; Tina Ndam; Mikeala Bekemeier; Hailong Song; Runting Li; Heather R. Siedhoff; Bo Yang; Michael K. Appenteng; C. Michael Greenlief; Dennis K. Miller; Grace Y. Sun; et al. (NeuroMolecular Medicine, 2020)

Haplogroup Structure and Genetic Variation Analyses of 60 Mitochondrial DNA Markers in Southern Shaanxi Han Population - Yuan-Yuan Wei; Zhan-Ping Ren; Xiao-Ye Jin; Wei Cui; Chong Chen; Yu-Xin Guo; Hao-Tian Meng; Bo-Feng Zhu (Biochemical Genetics, 2020)

Ancestry informative DIP loci for dissecting genetic structure and ancestry proportions of Qinghai Tibetan and Tibet Tibetan groups - Xiao-Ye Jin; Chun-Mei Shen; Chong Chen; Yu-Xin Guo; Wei Cui; Yi-Jie Wang; Wen-Qing Zhang; Ting-Ting Kong; Bo-Feng Zhu (Molecular Biology Reports, 2020)

Exercise enhances cardiac function by improving mitochondrial dysfunction and maintaining energy homoeostasis in the development of diabetic cardiomyopathy - Shawn Yongshun Wang; Siyu Zhu; Jian Wu; Maomao Zhang; Yousheng Xu; Wei Xu; Jinjin Cui; Bo Yu; Wei Cao; Jingjin Liu (Journal of Molecular Medicine, 2020)

Can reanalysis products with only surface variables assimilated capture Madden–Julian oscillation characteristics? - Jingxuan Cui; Lu Wang; Tim Li; Bo Wu (International Journal of Climatology, 2020)
The Madden–Julian Oscillation (MJO), as a dominant mode of tropical intraseasonal oscillation, plays an important role in the variability of global weather and climate. However, current state‐of‐the‐art atmospheric circulation models have difficulty in reproducing observed MJO characteristics when forced by observed daily sea surface temperature alone. An important practical question is how much data a model needs in assimilation to reproduce real MJO events? By analysing ERA‐20C and NOAA‐20CR reanalysis data, the authors tried to figure out whether a model could reproduce observed MJO events by assimilating the observed surface signal alone. The phase propagation and vertical structure associated with MJO were compared between the reanalysis data and observations during 1979–2010. A total skill score considering both temporal correlation and spatial standard deviation were defined. The result showed that both ERA‐20C and NOAA‐20CR could reproduce the observed MJO characteristics very well, with the former superior to the latter, regardless of MJO intensity. Thus, a minimum requirement for an operational atmospheric model for MJO prediction is the assimilation of the observed surface signals.

Characteristics, Expression Pattern and Intracellular Localisation of Sugarcane Cytoplasmic Hexokinase Gene ShHXK8 - Jun-gang Wang; Ting-ting Zhao; Ben-peng Yang; Wen-zhi Wang; Cui-lian Feng; Xiao-yan Feng; Lin-bo Shen; Shu-zhen Zhang (Sugar Tech, 2019)

Carbon emissions accounting for China’s coal mining sector: invisible sources of climate change - Bing Wang; Chao-Qun Cui; Yi-Xin Zhao; Bo Yang; Qing-Zhou Yang (Natural Hazards, 2019)

Experimental study on the physical modeling of loess tunnel-erosion rate - Li Wang; Xi-An Li; Lin-Cui Li; Bo Hong; Jia Liu (Bulletin of Engineering Geology and the Environment, 2019)

Mass movement and formation process analysis of the two sequential landslide dam events in Jinsha River, Southwest China - Hai-bo Li; Shun-chao Qi; Hao Chen; Hai-mei Liao; Yi-fei Cui; Jia-wen Zhou (Landslides, 2019)

Weakened growth of cropland‐N 2 O emissions in China associated with nationwide policy interventions - Ziyin Shang; Feng Zhou; Pete Smith; Eri Saikawa; Philippe Ciais; Jinfeng Chang; Hanqin Tian; Stephen J. Del Grosso; Akihiko Ito; Minpeng Chen; Qihui Wang; Yan Bo; et al. (Global Change Biology, 2019)
China has experienced rapid agricultural development over recent decades, accompanied by increased fertilizer consumption in croplands; yet, the trend and drivers of the associated nitrous oxide (N 2 O) emissions remain uncertain. The primary sources of this uncertainty are the coarse spatial variation of activity data and the incomplete model representation of N 2 O emissions in response to agricultural management. Here, we provide new data‐driven estimates of cropland‐N 2 O emissions across China in 1990–2014, compiled using a global cropland‐N 2 O flux observation dataset, nationwide survey‐based reconstruction of N‐fertilization and irrigation, and an updated nonlinear model. In addition, we have evaluated the drivers behind changing cropland‐N 2 O patterns using an index decomposition analysis approach. We find that China's annual cropland‐N 2 O emissions increased on average by 11.2 Gg N/year 2 ( p 2 , p = .02), consistent with the output from an ensemble of process‐based terrestrial biosphere models. The slowdown of the increase in cropland‐N 2 O emissions after 2003 was pervasive across two thirds of China's sowing areas. This change was mainly driven by the nationwide reduction in N‐fertilizer applied per area, partially due to the prevalence of nationwide technological adoptions. This reduction has almost offset the N 2 O emissions induced by policy‐driven expansion of sowing areas, particularly in the Northeast Plain and the lower Yangtze River Basin. Our results underline the importance of high‐resolution activity data and adoption of nonlinear model of N 2 O emission for capturing cropland‐N 2 O emission changes. Improving the representation of policy interventions is also recommended for future projections.

microRNA-7 inhibition protects human osteoblasts from dexamethasone via activation of epidermal growth factor receptor signaling - Jian-bo Fan; Wei Liu; Xin-hui Zhu; Sheng-yu Cui; Zhi-ming Cui; Jian-ning Zhao (Molecular and Cellular Biochemistry, 2019)

Experimental study on the disintegration of loess in the Loess Plateau of China - Xi-An Li; Li Wang; Yong-li Yan; Bo Hong; Lin-Cui Li (Bulletin of Engineering Geology and the Environment, 2019)

Comparison of evapotranspiration measurements between eddy covariance and lysimeters in paddy fields under alternate wetting and drying irrigation - Bo Liu; Yuanlai Cui; Yuanzhi Shi; Xueliang Cai; Yufeng Luo; Lei Zhang (Paddy and Water Environment, 2019)

GIS-Supported Airfield Selection near Zhongshan Station, East Antarctica, based on Multi-Mission Remote Sensing Data - Xiangbin Cui; Jiaxin Liu; Yixiang Tian; Bo Sun; Rongxing Li; Alexey Markov; Da Lv; Gang Hai; Gang Qiao; Tiantian Feng (Marine Geodesy, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

Genetic distribution and forensic evaluation of multiplex autosomal short tandem repeats in the Chinese Xinjiang Mongolian group - Yuan-Yuan Wei; Xiao-Ye Jin; Qiong Lan; Wei Cui; Chong Chen; Ting-Ting Kong; Yu-Xin Guo; Jian-Gang Chen; Bo-Feng Zhu (Journal of Zhejiang University-SCIENCE B, 2019)

Levels of phthalate acid esters and sex hormones and their possible sources in traffic-patrol policemen in Chongqing - Lu Lu; Honghui Rong; Chong Wu; Bo Cui; Yujing Huang; Yao Tan; Ling Zhang; Yi Peng; Jose M. Garcia; Ji-an Chen (Environmental Science and Pollution Research, 2019)

Prediction of curtain grouting efficiency based on ANFIS - Xiaochao Li; Denghua Zhong; Bingyu Ren; Guichao Fan; Bo Cui (Bulletin of Engineering Geology and the Environment, 2019)

Correction to: Ready player one? Autophagy shapes resistance to photodynamic therapy in cancers - Xian Duan; Bo Chen; Yanan Cui; Lin Zhou; Chenkai Wu; Zhulin Yang; Yu Wen; Xiongying Miao; Qinglong Li; Li Xiong; Jun He (Apoptosis, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

Development of a Reverse Transcription-Recombinase Polymerase Amplification Assay for Detection of Sugarcane Yellow Leaf Virus - Xiao-Yan Feng; Lin-Bo Shen; Wen-Zhi Wang; Jun-Gang Wang; Zheng-Ying Cao; Cui-Lian Feng; Ting-Ting Zhao; Shu-Zhen Zhang (Sugar Tech, 2018)

Ready player one? Autophagy shapes resistance to photodynamic therapy in cancers - Xian Duan; Bo Chen; Yanan Cui; Lin Zhou; Chenkai Wu; Zhulin Yang; Yu Wen; Xiongying Miao; Qinglong Li; Li Xiong; Jun He (Apoptosis, 2018)

Solubilization of Nitrogen Heterocyclic Compounds Using Different Surfactants - Zuoyi Yang; Jiahao Cui; Bo Yin (Water, Air, & Soil Pollution, 2018)

Source apportionment of nitrogen and phosphorus from non-point source pollution in Nansi Lake Basin, China - Bao-lei Zhang; Bo-hao Cui; Shu-min Zhang; Quan-yuan Wu; Lei Yao (Environmental Science and Pollution Research, 2018)

Effects of Different Sources and Levels of Zinc on Growth Performance, Nutrient Digestibility, and Fur Quality of Growing-Furring Male Mink (Mustela vison) - Hu Cui; Tietao Zhang; Hao Nie; Zhongcheng Wang; Xuelei Zhang; Bo Shi; Xiumei Xing; Fuhe Yang; Xiuhua Gao (Biological Trace Element Research, 2018)

Simultaneous purifying of Hg0, SO2, and NOx from flue gas by Fe3+/H2O2: the performance and purifying mechanism - Yi Xing; Liuliu Li; Pei Lu; Jiansheng Cui; Qianli Li; Bojun Yan; Bo Jiang; Mengsi Wang (Environmental Science and Pollution Research, 2018)

New phenanthrene and 9, 10-dihydrophenanthrene derivatives from the stems of Dendrobium officinale with their cytotoxic activities - Gui-Yun Zhao; Bo-Wen Deng; Chong-Yu Zhang; Yi-Da Cui; Jia-Yi Bi; Guo-Gang Zhang (Journal of Natural Medicines, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Inhibition of protein kinase CK2 sensitizes non-small cell lung cancer cells to cisplatin via upregulation of PML - Bo Yang; Jinhong Yao; Bai Li; Guoguang Shao; Yongsheng Cui (Molecular and Cellular Biochemistry, 2017)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Constituents from solid-cultured Antrodia camphorata - Zong-Bo Tong; Xu-Hong Cui; Jie Wang; Cun-Li Zhang; Yan-Yan Zhang; Zhan-Jun Ren (Natural Product Research, 2017)

Glucocorticoid-Potentiated Spinal Microglia Activation Contributes to Preoperative Anxiety-Induced Postoperative Hyperalgesia - Rao Sun; Zhibin Zhao; Jiying Feng; Jinhua Bo; Hui Rong; Yishan Lei; Cui’e Lu; Xiaobao Zhang; Bailing Hou; Yu’e Sun; Yue Liu; Zhengliang Ma; et al. (Molecular Neurobiology, 2017)

Low diversity, activity, and density of transposable elements in five avian genomes - Bo Gao; Saisai Wang; Yali Wang; Dan Shen; Songlei Xue; Cai Chen; Hengmi Cui; Chengyi Song (Functional & Integrative Genomics, 2017)

Phytochemicals and biological activities of Artemisia sieversiana - Shi-Jun Liu; Zhi-Xin Liao; Zhi-Shu Tang; Chun-Li Cui; Hong-Bo Liu; Yan-Ni Liang; Yu Zhang; Huan-Xian Shi; Yao-Run Liu (Phytochemistry Reviews, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Effects of Spartina alterniflora Invasion on the Abundance, Diversity, and Community Structure of Sulfate Reducing Bacteria along a Successional Gradient of Coastal Salt Marshes in China - Jun Cui; Xueping Chen; Ming Nie; Shubo Fang; Boping Tang; Zhexue Quan; Bo Li; Changming Fang (Wetlands, 2017)

A novel lectin from Artocarpus lingnanensis induces proliferation and Th1/Th2 cytokine secretion through CD45 signaling pathway in human T lymphocytes - Bo Cui; Lu Li; Qiyan Zeng; Faquan Lin; Lijun Yin; Liejun Liao; Min Huang; Jingping Wang (Journal of Natural Medicines, 2017)

Mitigating cadmium accumulation in greenhouse lettuce production using biochar - Ruilun Zheng; Guoxin Sun; Cui Li; Brian J. Reid; Zubin Xie; Bo Zhang; Qinghai Wang (Environmental Science and Pollution Research, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Expression patterns of endogenous avian retrovirus ALVE1 and its response to infection with exogenous avian tumour viruses - Xuming Hu; Wenqi Zhu; Shihao Chen; Yangyang Liu; Zhen Sun; Tuoyu Geng; Chengyi Song; Bo Gao; Xiaoyan Wang; Aijian Qin; Hengmi Cui (Archives of Virology, 2017)

The accumulation and health risk of heavy metals in vegetables around a zinc smelter in northeastern China - Bo Li; Yanhong Wang; Yong Jiang; Guochen Li; Jiehua Cui; Ying Wang; Hong Zhang; Shicheng Wang; Sheng Xu; Ruzhen Wang (Environmental Science and Pollution Research, 2016)

An all-season sample database for improving land-cover mapping of Africa with two classification schemes - Congcong Li; Peng Gong; Jie Wang; Cui Yuan; Tengyun Hu; Qi Wang; Le Yu; Nicholas Clinton; Mengna Li; Jing Guo; Duole Feng; Conghong Huang; et al. (International Journal of Remote Sensing, 2016)

Transcriptome analysis of sika deer in China - Bo-Yin Jia; Heng-Xing Ba; Gui-Wu Wang; Ying Yang; Xue-Zhe Cui; Ying-Hua Peng; Jun-Jun Zheng; Xiu-Mei Xing; Fu-He Yang (Molecular Genetics and Genomics, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Phytotoxicity mechanisms of two coumarin allelochemicals from Stellera chamaejasme in lettuce seedlings - Zhiqiang Yan; Dandan Wang; Haiyan Cui; Denghong Zhang; Yuhe Sun; Hui Jin; Xiuzhuang Li; Xiaoyan Yang; Hongru Guo; Xiaofeng He; Le Pan; Xia Ren; et al. (Acta Physiologiae Plantarum, 2016)

Computational identification and characterization of novel microRNA in the mammary gland of dairy goat (Capra hircus) - BO QU; YOUWEN QIU; ZHEN ZHEN; FENG ZHAO; CHUNMEI WANG; YINGJUN CUI; QIZHANG LI; LI ZHANG (Journal of Genetics, 2016)

Erratum to: Progressive changes of orexin system in a rat model of 6-hydroxydopamine-induced Parkinson’s disease - Long-Biao Cui; Bo-Wei Li; Xiao-Hang Jin; Lin Zhao; Juan Shi (Neuroscience Bulletin, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Comparative proteomic analysis of Phalaenopsis leaves in the vegetative and flowering phase - Xiu-Yun Yuan; Shen-Ping Xu; Fang Liang; Su-Hua Jiang; Mo-Fei Wang; Jie Ma; Xian-Yun Zhang; Bo Cui (Acta Physiologiae Plantarum, 2016)

Expression of the env gene from the avian endogenous retrovirus ALVE and regulation by miR-155 - Xuming Hu; Wenqi Zhu; Shihao Chen; Yangyang Liu; Zhen Sun; Tuoyu Geng; Xiaoyan Wang; Bo Gao; Chengyi Song; Aijian Qin; Hengmi Cui (Archives of Virology, 2016)

The effect of calcitriol on high mobility group box 1 expression in periodontal ligament cells during orthodontic tooth movement in rats - Jian Cui; Juan Li; Wei Wang; Xiuchun Han; Juan Du; Jing Sun; Wei Feng; Bo Liu; Hongrui Liu; Norio Amizuka; Minqi Li (Journal of Molecular Histology, 2016)

Wetland economic valuation approaches and prospects in China - Bo Jiang; Christina P. Wong; Lijuan Cui; Zhiyun Ouyang (Chinese Geographical Science, 2016)

Transgenic NfFeSOD Sedum alfredii plants exhibited profound growth impairments and better relative tolerance to long-term abiotic stresses - Xiang Gao; Wen-Li Ai; Huan Gong; Li-Juan Cui; Bo-Xia Chen; Hong-Yi Luo; Zhong-Chun Zhang; Bao-Sheng Qiu (Plant Biotechnology Reports, 2016)

Ice thickness, internal layers, and surface and subglacial topography in the vicinity of Chinese Antarctic Taishan station in Princess Elizabeth Land, East Antarctica - Xue-Yuan Tang; Jing-Xue Guo; Bo Sun; Tian-Tian Wang; Xiang-Bin Cui (Applied Geophysics, 2016)

Distribution of ice thickness and subglacial topography of the “Chinese Wall” around Kunlun Station, East Antarctica - Xiang-Bin Cui; Bo Sun; Xiao-Gang Su; Jing-Xue Guo (Applied Geophysics, 2016)

Effects of spillway types on debris flow trajectory and scour behind a sabo dam - Hua-yong Chen; Peng Cui; Jian-gang Chen; Jin-bo Tang (Journal of Mountain Science, 2016)

Trends in the prevalence of heart diseases over a ten-year period from single-center observations based on a large echocardiographic database - Hao Lu; Wen-zhi Pan; Quan Wan; Lei-lei Cheng; Xian-hong Shu; Cui-zhen Pan; Ju-ying Qian; Jun-bo Ge (Journal of Zhejiang University-SCIENCE B, 2016)

Slowly Digestible Starch—A Review - Ming Miao; Bo Jiang; Steve W. Cui; Tao Zhang; Zhengyu Jin (Critical Reviews in Food Science and Nutrition, 2015)

Advancing Wetland Policies Using Ecosystem Services – China’s Way Out - Bo Jiang; Christina P. Wong; Yuanyuan Chen; Lijuan Cui; Zhiyun Ouyang (Wetlands, 2015)

Surface mass balance and its climate significance from the coast to Dome A, East Antarctica - MingHu Ding; CunDe Xiao; ChuanJin Li; DaHe Qin; Bo Jin; GuiTao Shi; AiHong Xie; XiangBin Cui (Science China Earth Sciences, 2015)

Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

The effect of long-term historical habitat fragmentation on genetic diversity of the relictual conifer Calocedrus macrolepis (Cupressaceae) in China - Shengxi Liao; Kai Cui; Bo Tian; Zhiyong Zhang; Aizhong Liu; Kun Li; Xuedong Lang (Brazilian Journal of Botany, 2015)

Phytotoxicity assessment of atrazine on growth and physiology of three emergent plants - Qinghai Wang; Xiaoe Que; Ruilun Zheng; Zuo Pang; Cui Li; Bo Xiao (Environmental Science and Pollution Research, 2015)

Histochemical evidence of zoledronate inhibiting c-src expression and interfering with CD44/OPN-mediated osteoclast adhesion in the tibiae of mice - Hongrui Liu; Jian Cui; Jing Sun; Juan Du; Wei Feng; Bao Sun; Juan Li; Xiuchun Han; Bo Liu; Yimin; Kimimitsu Oda; Norio Amizuka; et al. (Journal of Molecular Histology, 2015)

Altered distribution of HMGB1 in the periodontal ligament of periostin-deficient mice subjected to Waldo’s orthodontic tooth movement - Juan Li; Wei Feng; Bo Liu; Bao Sun; Xiuchun Han; Juan Du; Jing Sun; Yimin; Jian Cui; Jie Guo; Akira Kudo; Norio Amizuka; et al. (Journal of Molecular Histology, 2015)

Thyroid hormone responsive protein spot 14 enhances lipogenesis in bovine mammary epithelial cells - Yingjun Cui; Zhiyu Liu; Xia Sun; Xiaoming Hou; Bo Qu; Feng Zhao; Xuejun Gao; Zhe Sun; Qingzhang Li (In Vitro Cellular & Developmental Biology - Animal, 2015)

Up-regulation of integrin α6β4 expression by mitogens involved in dairy cow mammary development - Feng Zhao; Chang Liu; Yu-Meng Hao; Bo Qu; Ying-Jun Cui; Na Zhang; Xue-Jun Gao; Qing-Zhang Li (In Vitro Cellular & Developmental Biology - Animal, 2015)

Effect of zero-valent iron on the start-up performance of anaerobic ammonium oxidation (anammox) process - Long-Fei Ren; Shou-Qing Ni; Cui Liu; Shuang Liang; Bo Zhang; Qiang Kong; Ning Guo (Environmental Science and Pollution Research, 2015)

EGFR-AKT-mTOR activation mediates epiregulin-induced pleiotropic functions in cultured osteoblasts - Jian-bo Fan; Wei Liu; Xin-hui Zhu; Kun Yuan; Da-wei Xu; Jia-jia Chen; Zhi-ming Cui (Molecular and Cellular Biochemistry, 2015)

Evaluation of the Protective Potential of Brain Microvascular Endothelial Cell Autophagy on Blood–Brain Barrier Integrity During Experimental Cerebral Ischemia–Reperfusion Injury - Haiying Li; Anju Gao; Dongxia Feng; Yang Wang; Li Zhang; Yonghua Cui; Bo Li; Zhong Wang; Gang Chen (Translational Stroke Research, 2014)

Cassiterite LA-MC-ICP-MS U/Pb and muscovite 40Ar/39Ar dating of tin deposits in the Tengchong-Lianghe tin district, NW Yunnan, China - Xiao-Cui Chen; Rui-Zhong Hu; Xian-Wu Bi; Hui-Min Li; Jiang-Bo Lan; Cheng-Hai Zhao; Jing-Jing Zhu (Mineralium Deposita, 2014)

Functional analysis of FABP3 in the milk fat synthesis signaling pathway of dairy cow mammary epithelial cells - Meng-yao Liang; Xiao-ming Hou; Bo Qu; Na Zhang; Nan Li; Ying-jun Cui; Qing-zhang Li; Xue-jun Gao (In Vitro Cellular & Developmental Biology - Animal, 2014)

Expression, cloning, and IgE-binding of the full-length dust mite allergen Der f 8 - Yu-bao Cui; Ying Zhou; Nan Wang; Fei-xiang Teng; Li-li Yu; Yong-hua Bian; Jin-xia Song; Li Yang; Cheng-bo Zhang (Immunologic Research, 2014)

Assessment of gene flow from glyphosate-resistant transgenic soybean to conventional soybean in China - Wen-Kun Huang; Huan Peng; Gao-Feng Wang; Jiang-Kuan Cui; Lin-Feng Zhu; Hai-Bo Long; De-Liang Peng (Acta Physiologiae Plantarum, 2014)

Effect of heat stress and recovery on viability, oxidative damage, and heat shock protein expression in hepatic cells of grass carp (Ctenopharyngodon idellus) - Yanting Cui; Bo Liu; Jun Xie; Pao Xu; H-Michael Habte-Tsion; Yuanyuan Zhang (Fish Physiology and Biochemistry, 2014)

Numerical approach for thermal history modelling in multi-episodic rifting basins - Bo Kang; Xinong Xie; Tao Cui (Journal of Earth Science, 2014)

Effect of enrofloxacin and emodin on heat-shock proteins’ expression in hepatic cells of grass carp (Ctenopharyngodon idellus) - Yanting Cui; Bo Liu; Jun Xie; Pao Xu; Yuanyuan Zhang; Jianhua Ming (Aquaculture International, 2014)

Effects of straw carbon input on carbon dynamics in agricultural soils: a meta‐analysis - Chang Liu; Meng Lu; Jun Cui; Bo Li; Changming Fang (Global Change Biology, 2014)
Straw return has been widely recommended as an environmentally friendly practice to manage carbon (C) sequestration in agricultural ecosystems. However, the overall trend and magnitude of changes in soil C in response to straw return remain uncertain. In this meta‐analysis, we calculated the response ratios of soil organic C ( SOC ) concentrations, greenhouse gases ( GHG s) emission, nutrient contents and other important soil properties to straw addition in 176 published field studies. Our results indicated that straw return significantly increased SOC concentration by 12.8 ± 0.4% on average, with a 27.4 ± 1.4% to 56.6 ± 1.8% increase in soil active C fraction. CO 2 emission increased in both upland (27.8 ± 2.0%) and paddy systems (51.0 ± 2.0%), while CH 4 emission increased by 110.7 ± 1.2% only in rice paddies. N 2 O emission has declined by 15.2 ± 1.1% in paddy soils but increased by 8.3 ± 2.5% in upland soils. Responses of macro‐aggregates and crop yield to straw return showed positively linear with increasing SOC concentration. Straw‐C input rate and clay content significantly affected the response of SOC . A significant positive relationship was found between annual SOC sequestered and duration, suggesting that soil C saturation would occur after 12 years under straw return. Overall, straw return was an effective means to improve SOC accumulation, soil quality, and crop yield. Straw return‐induced improvement of soil nutrient availability may favor crop growth, which can in turn increase ecosystem C input. Meanwhile, the analysis on net global warming potential ( GWP ) balance suggested that straw return increased C sink in upland soils but increased C source in paddy soils due to enhanced CH 4 emission. Our meta‐analysis suggested that future agro‐ecosystem models and cropland management should differentiate the effects of straw return on ecosystem C budget in upland and paddy soils.

Phytotoxicity of Atrazine to Emergent Hydrophyte, Iris pseudacorus L. - Qinghai Wang; Xiaoe Que; Cui Li; Bo Xiao (Bulletin of Environmental Contamination and Toxicology, 2014)

Characterizing the mode of action of Brevibacillus laterosporus B4 for control of bacterial brown strip of rice caused by A. avenae subsp. avenae RS-1 - Kaleem Ullah Kakar; Zarqa Nawaz; Z. Cui; Abdlwareth A. Almoneafy; Bo Zhu; Guan-Lin Xie (World Journal of Microbiology and Biotechnology, 2014)

Biocompatibility of nano-hydroxyapatite/Mg-Zn-Ca alloy composite scaffolds to human umbilical cord mesenchymal stem cells from Wharton’s jelly in vitro - FangXia Guan; ShanShan Ma; XinYi Shi; Xun Ma; LianKai Chi; Shuo Liang; YuanBo Cui; ZhiBin Wang; Ning Yao; ShaoKang Guan; Bo Yang (Science China Life Sciences, 2014)

Full-length sequence analysis of hepatitis E virus isolates: showing potential determinants of virus genotype and identity - Dong Yang; Mei Jiang; Min Jin; Zhigang Qiu; Weihong Cui; Zhiqiang Shen; Bo Li; Lianfeng Gong; Zhaoli Chen; Xinwei Wang; Jun-Wen Li (Virus Genes, 2013)

Age and Dark Rearing Bidirectionally Regulate the Level and Laminar Pattern of Expression of Abelson Interacting Protein 2 (Abi-2): a Novel Candidate Visual Cortical Plasticity Gene - Cui Bo Yang; Paul J. Kiser; Yu Ting Zheng; George D. Mower (Journal of Molecular Neuroscience, 2013)

3-O-Acetyloleanolic acid exhibits anti-angiogenic effects and induces apoptosis in human umbilical vein endothelial cells - En-Ji Cui; Jeon Hwang-Bo; Jong-Hwa Park; Nam-In Baek; Jiyoung Kim; Seong Gil Hong; In Sik Chung (Biotechnology Letters, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

A DEM-based residual kriging model for estimating groundwater levels within a large-scale domain: a study for the Fuyang River Basin - Kui Zhu; Zengdi Cui; Bo Jiang; Guoyong Yang; Zhengjie Chen; Qian Meng; Yuan Yao (Clean Technologies and Environmental Policy, 2013)

Reducing the oxidative stress mediates the cardioprotection of bicyclol against ischemia-reperfusion injury in rats - Jie Cui; Zhi Li; Ling-bo Qian; Qin Gao; Jue Wang; Meng Xue; Xiao-e Lou; Iain C. Bruce; Qiang Xia; Hui-ping Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Changes in photosynthesis, chlorophyll fluorescence, and antioxidant enzymes of mulberry (Morus ssp.) in response to salinity and high-temperature stress - Cui Yu; Shujun Huang; Xingming Hu; Wen Deng; Chao Xiong; Chuhua Ye; Yong Li; Bo Peng (Biologia, 2013)

Late Quaternary glacial chronology on the eastern slope of Gongga Mountain, eastern Tibetan Plateau, China - Jie Wang; BaoTian Pan; GuoLiang Zhang; Hang Cui; Bo Cao; HaoPeng Geng (Science China Earth Sciences, 2013)

Development of InDel markers for Brassica rapa based on whole-genome re-sequencing - Bo Liu; Yan Wang; Wen Zhai; Jie Deng; Hui Wang; Yang Cui; Feng Cheng; Xiaowu Wang; Jian Wu (Theoretical and Applied Genetics, 2013)

RNAi knockdown of rice SE5 gene is sensitive to the herbicide methyl viologen by the down-regulation of antioxidant defense - Sheng Xu; Lijuan Wang; Bo Zhang; Bin Han; Yanjie Xie; Jie Yang; Weigong Zhong; Huiping Chen; Ren Wang; Ning Wang; Weiti Cui; Wenbiao Shen (Plant Molecular Biology, 2012)

Relationships between edema degree and clinical and biochemical parameters in posterior reversible encephalopathy syndrome: a preliminary study - Gao Bo; Liang Hui; Liu Feng-li; Lv Cui (Acta Neurologica Belgica, 2012)

Transcriptome profiling and methyl homeostasis of an Arabidopsis mutant deficient in S-adenosylhomocysteine hydrolase1 (SAHH1) - Bo Ouyang; Zhangjun Fei; Je-Gun Joung; Allan Kolenovsky; Chushin Koh; Jacek Nowak; Allan Caplan; Wilfred A. Keller; Yuhai Cui; Adrian J. Cutler; Edward W. T. Tsang (Plant Molecular Biology, 2012)

Statin use and risk of pancreatic cancer: a meta-analysis - Xiaobing Cui; Yue Xie; Min Chen; Jun Li; Xiaoming Liao; Jian Shen; Meng Shi; Wenjing Li; Haoxuan Zheng; Bo Jiang (Cancer Causes & Control, 2012)

Regulation of colon cancer cell migration and invasion by CLIC1-mediated RVD - Pan Wang; Chao Zhang; PeiWu Yu; Bo Tang; Tao Liu; Hao Cui; JianHua Xu (Molecular and Cellular Biochemistry, 2012)

Gene cloning, expression and functional characterization of a proliferation-inducing ligand (APRIL) from hedgehog (Erinaceus europaeus) - Xian-wei Cui; Wen Xiao; Chen-bo Ji; Ai-ying Tian; Jie Zhang; Shuang-quan Zhang (Molecular Biology Reports, 2012)

Ethyl pyruvate reduces myocardial ischemia and reperfusion injury by inhibiting high mobility group box 1 protein in rats - Xiaorong Hu; Bo Cui; Xiaoya Zhou; Changwu Xu; Zhibing Lu; Hong Jiang (Molecular Biology Reports, 2012)

A Promising CdSe@CdS-Quantum Dots-Cysteine for the Determination of Trace IgE by Solid Substrate Room Temperature Phosphorescence Immunoassay - Jia-Ming Liu; Li-ping Lin; Zhen-Bo Liu; Min-Lan Yang; Xin-xing Wang; Li-hong Zhang; Ma-lin Cui; Li Jiao (Journal of Fluorescence, 2012)

Complete genomic sequence analysis of a highly virulent isolate revealed a novel strain of Sugarcane mosaic virus - Bo Gao; Xiao-Wen Cui; Xiang-Dong Li; Chun-Qing Zhang; Hong-Qin Miao (Virus Genes, 2011)

Shifted first arrival point travel time NMO inversion - Chen-Qing Tan; Yan-Gang Wu; Li-Guo Han; Xiang-Bo Gong; Jie Cui (Applied Geophysics, 2011)

Effectiveness of maintenance treatments with atypical and typical antipsychotics in stable schizophrenia with early stage: 1-year naturalistic study - Xiaofeng Guo; Maosheng Fang; Jinguo Zhai; Bo Wang; Chuanyue Wang; Bin Hu; Xueli Sun; Luxian Lv; Zheng Lu; Cui Ma; Tiansheng Guo; Shiping Xie; et al. (Psychopharmacology, 2011)

Analysis and characterization of the complete genome of a member of a new species of kobuvirus associated with swine - Jie-mei Yu; Zi-qian Xu; Bo-wen Li; Qing Zhang; Shu-xian Cui; Miao Jin; Zhao-jun Duan (Archives of Virology, 2011)

Fluid Dynamics Analysis of a Novel Micropatterned Cell Bioreactor - Yuhong Cui; Bo Huo; Shujin Sun; Fan Yang; Yuxin Gao; Jun Pan; Mian Long (Annals of Biomedical Engineering, 2011)

Analysis of time-course gene expression profiles of sinusoidal endothelial cells during liver regeneration in rats - Cun-shuan Xu; Xiao-guang Chen; Cui-fang Chang; Gai-ping Wang; Wen-bo Wang; Lian-xing Zhang; Qiu-shi Zhu; Lei Wang (Molecular and Cellular Biochemistry, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

Structure of the internal isochronous layers at Dome A, East Antarctica - XueYuan Tang; Bo Sun; ZhanHai Zhang; XiangPei Zhang; XiangBin Cui; Xin Li (Science China Earth Sciences, 2011)

Progressive changes of orexin system in a rat model of 6-hydroxydopamineinduced Parkinson’s disease - Cui Long-Biao; Li Bo-Wei; Jin Xiao-Hang; Zhao Lin; Shi Juan (Neuroscience Bulletin, 2010)

Characteristics and sources of atmospheric polycyclic aromatic hydrocarbons (PAHs) in Shanghai, China - Xian Yu Wang; Qing Bo Li; Yong Ming Luo; Qian Ding; Lian Min Xi; Jian Min Ma; Yan Li; Yi Peng Liu; Cui Li Cheng (Environmental Monitoring and Assessment, 2010)

Isolation of high quality RNA and construction of a suppression subtractive hybridization library from ramie (Boehmeria nivea L. Gaud.) - Xu-xia Wang; Bo Wang; Li-jun Liu; Xiao-ping Cui; Jin-yu Yang; Hui Wang; Hui Jiang; Bei-bei Luo; Zhu Long; Wen-xiang Dou; Na Zhang; Ding-xiang Peng (Molecular Biology Reports, 2010)

Accumulation of 1-deoxynojirimycin in silkworm, Bombyx mori L. - Hao Yin; Xin-qin Shi; Bo Sun; Jing-jing Ye; Zu-an Duan; Xiao-ling Zhou; Wei-zheng Cui; Xiao-feng Wu (Journal of Zhejiang University-SCIENCE B, 2010)

Sanchi ginseng (Panax notoginseng (Burkill) F. H. Chen) in China: distribution, cultivation and variations - Hong Bo Guo; Xiu Ming Cui; Na An; Ge Ping Cai (Genetic Resources and Crop Evolution, 2010)

Cloning and characterization of a wheat β-1,3-glucanase gene induced by the stripe rust pathogen Puccinia striiformis f. sp. tritici - Bo Liu; Xiaodan Xue; Suping Cui; Xiaoyu Zhang; Qingmei Han; Lin Zhu; Xiaofei Liang; Xiaojie Wang; Lili Huang; Xianming Chen; Zhensheng Kang (Molecular Biology Reports, 2010)

Finger-vein image recognition combining modified Hausdorff distance with minutiae feature matching - Cheng-Bo Yu; Hua-Feng Qin; Yan-Zhe Cui; Xiao-Qian Hu (Interdisciplinary Sciences: Computational Life Sciences, 2009)

Hypoglycemic Activity of Grifola frondosa Rich in Vanadium - Bo Cui; Linna Han; Jingran Qu; Yingtao Lv (Biological Trace Element Research, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

Arthrobacter halodurans sp. nov., a new halotolerant bacterium isolated from sea water - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhao-Yang Li; Lang-Bo Yi; Yong-Xia Wang; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Comparison of Vanadium-Rich Activity of Three Species Fungi of Basidiomycetes - Chunchao Han; Bo Cui; Jingran Qu (Biological Trace Element Research, 2009)

Ecological Water Requirement (EWR) Analysis of High Mountain and Steep Gorge (HMSG) River—Application to Upper Lancang–Mekong River - Hu Bo; Cui Baoshan; Dong Shikui; Zhai Hongjuan; Liu Zhaoyang (Water Resources Management, 2009)

Genetic structure and diversity of cultivated soybean (Glycine max (L.) Merr.) landraces in China - Yinghui Li; Rongxia Guan; Zhangxiong Liu; Yansong Ma; Lixia Wang; Linhai Li; Fanyun Lin; Weijiang Luan; Pengyin Chen; Zhe Yan; Yuan Guan; Li Zhu; et al. (Theoretical and Applied Genetics, 2008)

Vanadium Uptake by Biomass of Coprinus comatus and Their Effect on Hyperglycemic Mice - Chunchao Han; Bo Cui; Yingzi Wang (Biological Trace Element Research, 2008)

Molecular characterization and phylogenetic analysis of membrane protein genes of porcine epidemic diarrhea virus isolates in China - Jian-Fei Chen; Dong-Bo Sun; Cheng-Bao Wang; Hong-Yan Shi; Xiao-Chen Cui; Sheng-Wang Liu; Hua-Ji Qiu; Li Feng (Virus Genes, 2008)

Identification and Characterization of the Human SCAN Domain Zinc-Finger Gene ZNF449 - Kuntian Luo; Jie Li; Yanhui Cui; Meng Xu; Jian Yuan; Wenwen Tang; Bo Wan; Long Yu (Molecular Biology Reports, 2006)

Paragonimus skrjabini Chen, 1959 (Digenea: Paragonimidae) and related species in eastern Asia: a combined molecular and morphological approach to identification and taxonomy - David Blair; Chang Zhengshan; Chen Minggang; Cui Aili; Wu Bo; Takeshi Agatsuma; Moritoshi Iwagami; David Corlis; Fu Chengbin; Zhan Ximei (Systematic Parasitology, 2005)

Epoxypropane biosynthesis by Methylomonas sp. GYJ3: batch and continuous studies - Jia-Ying Xin; Jun-Ru Cui; Li-Min Zhu; Jian-Bo Chen; Chun-Gu Xia; Shu-Ben Li (World Journal of Microbiology and Biotechnology, 2002)

Cloning of human myeloid-associated differentiation marker (MYADM) gene whose expression was up-regulated in NB4 cells induced by all-trans retinoic acid - Wanchang Cui; Long Yu; Hua He; Yaya Chu; Jie Gao; Bo Wan; Lisha Tang; Shouyuan Zhao (Molecular Biology Reports, 2001)

Assessment on the commonweal values of wetlands - Li-juan Cui; Li-li Pan; Yan-bo Zhang (Chinese Geographical Science, 2000)

Changes in ganglioside contents, plasma sialic acid and cAMP levels in experimental hepatoma in mice - Can Qun Lu; Jun Lu; Bo Liang Wang; Yao Zong Cui (Molecular and Cellular Biochemistry, 2000)